Laminated film

By using a cured resin layer (A) and a cured resin layer (B) with a specific structure in the surface protection film, the problem of difficulty in taking into account both the wipe resistance, repeated bending characteristics and antistatic properties in the prior art is solved, and the problem of the problem of wiping resistance, repeated bending characteristics and anti-static properties is realized. High-performance surface protection effect.

CN119421788APending Publication Date: 2025-02-11MITSUBISHI CHEM CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202380049383.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-05
Filing Date
2023-07-03
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing surface protection films are difficult to take into account the wipe resistance, repeated bending characteristics and anti-static properties under high hardness, and are prone to interference fringes, affecting the visibility of the display.

Method used

The cured resin layer (A) and the cured resin layer (B) have a specific structure laminated film. The cured resin layer (A) contains a binder, a crosslinker and particles. The cured resin layer (B) contains a carbam methacrylate. Acid esters and compounds with a cyclic siloxane backbone.

Benefits of technology

High wipe resistance, repeated bending characteristics and anti-static properties are achieved, while suppressing the generation of interference fringes and improving the overall performance of the surface protection film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205294910000241
    Figure BDA0005205294910000241
  • Figure BDA0005205294910000381
    Figure BDA0005205294910000381
  • Figure BDA0005205294910000391
    Figure BDA0005205294910000391
Patent Text Reader

Abstract

The present invention is a laminated film provided with a configuration in which a cured resin layer (A) and a cured resin layer (B) are laminated in this order on at least one surface of a base film, the cured resin layer (A) is a cured product of a curable resin composition (A ') containing (A-a) a binder, and the cured resin layer (B) is a cured product of a curable resin composition (B') containing (X) a urethane (meth) acrylate and (Y) a compound having a cyclic siloxane skeleton. According to the present invention, it is possible to propose a laminated film which has excellent repeated bending characteristics and wiping resistance in practical use, is not susceptible to interference fringes, has good antistatic properties, and also has both antistatic properties and antifouling properties, and also has excellent wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated film having a substrate film and a cured resin layer, a laminated film having excellent scratch resistance, repeated folding characteristics, and antistatic properties, and a laminated film having excellent antistatic properties, antifouling properties, and abrasion resistance. Background Art

[0002] In recent years, with the miniaturization and lightness of electronic devices, there is a tendency to use flexible substrates and flexible printed circuit boards. In addition, along with this tendency, there is also a tendency to increase the demand for flexibility in display applications. In addition, the surface protection film for display screens used for this purpose requires not only surface protection properties such as high hardness, scratch resistance, pollution resistance, and abrasion resistance, but also requires high durability with respect to bendability, and it is expected that the performance will be further improved.

[0003] Therefore, in recent years, many proposals have been made regarding surface protection films in order to improve flexibility and bendability while maintaining scratch resistance at high hardness.

[0004] For example, Patent Document 1 discloses a hard coating film, characterized in that it is a hard coating film having a hard coating layer formed on at least one side of a transparent substrate, and that two or more hard coating layers are formed, the elastic modulus of the hard coating layer formed closest to the transparent substrate is higher than the elastic modulus of the hard coating layer on the surface, and the content of inorganic particles in the hard coating layer formed closest to the transparent substrate is higher than that in the hard coating layer on the surface.

[0005] In addition, Patent Document 2 discloses a method for producing a hard coating film, which is characterized in that a UV-curable coating (a) having an elongation of 80% or more of the cured coating is applied to a film substrate, and a UV-curable coating (b) having a pencil scratch value of 4H or more of the cured coating is applied to the UV-curable coating, followed by ultraviolet irradiation to form a cured coating.

[0006] Furthermore, Patent Document 3 discloses a hard coating film having a base film and a hard coating layer, which can be used as a surface material of a touch panel that meets specific conditions.

[0007] As described above, development of flexible mobile terminals having image display screens (displays) that can be bent or folded has been carried out, and the surface protection films used for such image display screens are also required to have the performance of being able to be bent repeatedly in practical applications (for example, the durability of being able to be bent repeatedly more than 200,000 times), as well as the resistance to scratching in practical applications (for example, no scratches will be generated when steel wool #0000 is used to reciprocate 2000 times under a load of 1 kg).

[0008] In recent years, the demand for image display devices with liquid crystal displays such as smart phones and tablet terminals has further increased. In order to protect the screen display part or image display body of these displays, a protective film obtained by coating on a base film is used.

[0009] From the viewpoint of optical properties such as transparency, plastic films such as triacetylcellulose films, cycloolefin films, polyester films, acrylic films, polycarbonate films, and transparent polyimide films are used as protective films for screen display parts or image display bodies such as displays. However, these plastic films are easily charged due to their high electrical insulation properties, and dirt easily adheres to the surface.

[0010] Furthermore, in order to form a coating layer having antistatic properties, some coating agent compositions containing a polymer containing a quaternary ammonium salt group have been proposed (Patent Documents 4 to 6).

[0011] Patent Document 4 describes a resin composition for forming a hard coat layer. The resin composition for forming a hard coat layer contains: a (meth)acrylic copolymer; a polyurethane oligomer having a vinyl group and having trifunctional or higher functions; and an acrylic monomer having a vinyl group and having bifunctional to hexafunctional functions, wherein the (meth)acrylic copolymer is obtained by copolymerizing a vinyl-containing monomer having a quaternary ammonium group and a (meth)acrylic monomer copolymerizable therewith.

[0012] Patent Document 5 describes an antistatic hard coating resin composition, which contains: a compound having a (meth)acryloyl group; a polymer containing a quaternary ammonium salt group; acetone; and a mixed solvent of acetone and at least one alcohol selected from the group consisting of methanol, ethanol, and isopropanol.

[0013] Patent Document 6 describes a surface-cured article comprising a substrate and a cured coating film formed on the surface of the substrate. The cured coating film contains a quaternary ammonium salt group-containing polymer and metal oxide fine particles having an average particle size of 5 to 500 nm.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: Japanese Patent No. 4574766

[0017] Patent Document 2: Japanese Patent No. 4569807

[0018] Patent Document 3: Japanese Patent Application Publication No. 2021-7016

[0019] Patent Document 4: Japanese Patent Application Publication No. 2008-56872

[0020] Patent Document 5: Japanese Patent Application Publication No. 2013-91698

[0021] Patent Document 6: Japanese Patent Application Publication No. 2013-132784 Summary of the invention

[0022] Problem that the invention aims to solve

[0023] The inventions described in the above-mentioned patent documents 1 to 3 all have excellent surface hardness, but do not fully consider the scratch resistance in practical use. In particular, in patent document 3, although a scratch resistance test in practical use is assumed, the softness of the hard coating is not assumed, and the repeated bending characteristics when incorporated into the device are assumed to be insufficient.

[0024] Furthermore, depending on the required characteristics, it may be necessary to make the interference fringes less visible.

[0025] In addition, surface protection films used for applications such as flexible displays sometimes generate interference fringes due to various factors. If interference fringes are generated in the surface protection film, the appearance is reduced and the visibility of the display is reduced. Therefore, for the surface protection film, it is sometimes necessary to make the interference fringes difficult to see as a required characteristic.

[0026] Furthermore, it is difficult to achieve both antistatic properties and antifouling properties in the inventions described in Patent Documents 4 to 6. Furthermore, depending on the required properties, it may be necessary to make interference fringes less visible.

[0027] In addition, with regard to surface protection films for display screens such as displays, there is a trend towards using flexible substrates and flexible printed circuit boards as electronic devices become smaller and lighter. In addition to surface protection properties such as high hardness, scratch resistance, and contamination resistance, high durability is also required for bending properties. In recent years, further requirements have been placed on hardness properties such as scratch resistance and wear resistance for elastic bodies such as rubber, requiring further improvement.

[0028] Therefore, an object of the present invention is to provide a novel laminated film which is excellent in repeated folding characteristics and scratch resistance for practical use, is excellent in abrasion resistance, and has less visible interference fringes (first object).

[0029] The present invention also proposes a novel laminated film having moderate softness of a hard coat layer, excellent repeated folding characteristics and abrasion resistance for practical use, good antistatic properties, and hardly visible interference fringes (second problem).

[0030] Furthermore, the present invention proposes a novel laminated film which has both antistatic and antifouling properties, and further has excellent abrasion resistance, and hardly sees interference fringes, and also satisfies the repeated bending characteristics and scratch resistance required for practical use (third subject).

[0031] Solutions for solving problems

[0032] In view of the above-mentioned actual situation, the present inventors have repeatedly conducted intensive studies and found that the first problem can be solved by a structure in which a cured resin layer (A) and a cured resin layer (B) having a specific structure are stacked, thereby completing the present invention. That is, the present invention provides the following [1-1] to [1-18].

[0033] Furthermore, the present invention has been completed by finding that the second problem can be easily solved by a structure in which a cured resin layer (C), a cured resin layer (A), and a cured resin layer (B) having a specific structure are stacked. That is, the present invention provides the following [2-1] to [2-16].

[0034] Furthermore, the inventors have found that the above-mentioned problems can be easily solved by a structure having a specific structure in which a cured resin layer (A) and a cured resin layer (D) are laminated, thereby completing the present invention. That is, the present invention provides the following [3-1] to [3-16].

[0035] The gist of the present invention is as follows.

[0036] [1-1] A laminated film comprising a cured resin layer (A) and a cured resin layer (B) laminated in sequence on at least one side of a substrate film, wherein the cured resin layer (A) is a cured product of a curable resin composition (A') comprising (a) a binder, (b) a crosslinking agent and (c) particles, and the cured resin layer (B) is a cured product of a curable resin composition (B') comprising (X) (meth)acrylic urethane and (Y) a compound having a cyclic siloxane skeleton, wherein the (a) binder comprises a compound having a condensed polycyclic aromatic structure.

[0037] [1-2] The laminated film according to [1-1], wherein the compound (Y) having a cyclic siloxane skeleton is a fluorine compound having a perfluoroether structure.

[0038] [1-3] The laminated film according to [1-1] or [2-1], wherein, when the surface of the cured resin layer (B) is subjected to the following steel wool resistance test, the change rate of the film haze after 2000 reciprocating cycles is less than 1%;

[0039] (Steel wool resistance test)

[0040] Using a friction tester and #0000 steel wool, a load of 1 kg was applied to the outermost surface of the cured resin layer (B) in a 2 cm square, and the layer was rubbed back and forth 2000 times at a speed of 50 mm / sec. The haze value of the laminated film before and after friction was measured, and the rate of change compared to the initial film haze (film haze before friction) was calculated.

[0041] Change rate (%) = (film haze after friction - initial film haze) / initial film haze × 100

[0042] [1-4] The laminated film according to any one of [1-1] to [1-3], wherein the number of repeated folding times in the following repeated folding test is 200,000 times or more;

[0043] (Repeated bending test)

[0044] The laminate film was subjected to a bending test using a bending tester with the cured resin layer side as the inner surface at a minimum radius of R = 1.5, and the presence or absence of cracks in the cured resin layer on the inner surface was visually confirmed. The number of repeated bendings until cracks occurred was measured.

[0045] [1-5] The laminated film according to any one of [1-1] to [1-4], wherein the film haze is 1.0% or less.

[0046] [1-6] The laminated film according to any one of [1-1] to [1-5], wherein the elongation at break of the cured resin layer (A) and the cured resin layer (B) is 0.5% or more.

[0047] [1-7] The laminated film according to any one of [1-1] to [1-6], wherein the light transmittance at a wavelength of 380 nm on the surface of the cured resin layer (B) is 3% or less.

[0048] [1-8] The laminated film according to any one of [1-1] to [1-7], wherein the base film contains a UV absorber.

[0049] [1-9] The laminated film according to any one of [1-1] to [1-8], wherein the (c) particles include two types of particles having different particle sizes.

[0050] [1-10] The laminate film according to any one of [1-1] to [1-9], wherein the compound having a condensed polycyclic aromatic structure is a polyester resin having a condensed polycyclic aromatic structure.

[0051] [1-11] The laminated film according to any one of [1-1] to [1-10], wherein the base film is a polyester film.

[0052] [1-12] The laminated film according to any one of [1-1] to [1-11], wherein the base film is a polyethylene terephthalate (PET) film.

[0053] [1-13] The laminated film according to [1-11] or [1-12], wherein the retardation (Re) when light having a wavelength of 590 nm is incident on the polyester film surface at an angle of 0° is 1400 nm or less.

[0054] [1-14] A laminate film according to any one of [1-11] to [1-13], wherein the change in retardation (Re) in the fast axis direction when light with a wavelength of 590 nm is incident on the polyester film surface at an angle of 0° is greater than 10 nm / m and less than 600 nm / m.

[0055] [1-15] The laminated film according to any one of [1-11] to [1-14], wherein the thickness of the cured resin layer (B) is 10.0 μm or less.

[0056] [1-16] The laminated film according to any one of [1-11] to [1-15], which is for surface protection.

[0057] [1-17] The laminated film according to any one of [1-11] to [1-16], which is for use in displays.

[0058] [1-18] The laminated film according to any one of [1-11] to [1-17], which is for a front panel.

[0059] [2-1] A laminated film comprising a cured resin layer (A), a cured resin layer (B) and a cured resin layer (C) laminated in sequence on at least one side surface of a substrate film, wherein the cured resin layer (A) is a cured product of a curable resin composition A containing an antistatic agent, the cured resin layer (B) is a cured product of a curable resin composition (B') containing a binder (Ba), and the cured resin layer (C) is a cured product of a curable resin composition (C') containing (X) (meth)acrylic acid urethane and (Y) a fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure.

[0060] [2-2] The laminated film according to [2-1] above, wherein, when a steel wool resistance test is performed on the surface of the cured resin layer (C), the change rate of the film haze after 2000 reciprocating cycles is less than 1%;

[0061] (Steel wool resistance test)

[0062] Using a friction tester and #0000 steel wool, a load of 1 kg was applied to the surface of the cured resin layer (C) in a 2 cm square and the layer was rubbed back and forth 2000 times at a speed of 50 mm / sec. The haze value of the laminated film before and after friction was measured, and the rate of change compared to the initial film haze (film haze before friction) was calculated.

[0063] Change rate (%) = (film haze after friction - initial film haze) / initial film haze × 100

[0064] [2-3] The laminated film according to [2-1] or [2-2] above, which can be folded 200,000 times or more in repeated folding evaluation (inward folding, under the condition of R=1.5).

[0065] (Repeated bending test)

[0066] The laminate film was subjected to a bending test using a bending tester with the cured resin layer side as the inner surface at a minimum radius of R = 1.5, and the presence or absence of cracks in the cured resin layer on the inner surface was visually confirmed. The number of repeated bendings until cracks occurred was measured.

[0067] [2-4] The laminated film according to any one of [2-1] to [2-3] above, wherein the film haze is 1.0% or less.

[0068] [2-5] The laminated film according to any one of [2-1] to [2-4] above, wherein the light transmittance at a wavelength of 380 nm on the surface of the cured resin layer (C) is 3% or less.

[0069] [2-6] The laminated film according to any one of [2-1] to [2-5] above, wherein the maximum reflectance difference at a wavelength of 500 to 600 nm on the surface of the cured resin layer (C) is 1.5% or less.

[0070] [2-7] The laminated film according to any one of [2-1] to [2-6] above, wherein the base film contains a UV absorber.

[0071] [2-8] The laminated film according to any one of [2-1] to [2-7] above, wherein the cured resin layer (B) contains (Bc) particles, and the (Bc) particles are two types of particles having different particle sizes.

[0072] [2-9] The laminated film according to any one of [2-1] to [2-8] above, wherein the base film is a polyester film.

[0073] [2-10] The laminated film according to any one of [2-1] to [2-9] above, wherein the base film is a polyethylene terephthalate (PET) film.

[0074] [2-11] The laminated film according to [2-9] or [2-10] above, wherein the retardation (Re) of the polyester film is 1400 nm or less.

[0075] [2-12] The laminated film according to any one of [2-9] to [2-11] above, wherein the variation in retardation (Re) in the width direction of the polyester film is 10 nm / m or more and 600 nm / m or less.

[0076] [2-13] The laminated film according to any one of [2-1] to [2-12] above, wherein the thickness of the cured resin layer (C) is 10.0 μm or less.

[0077] [2-14] The laminated film according to any one of [2-1] to [2-13] above, which is for surface protection.

[0078] [2-15] The laminated film according to [2-14] above, which is for use in displays.

[0079] [2-16] The laminated film according to [2-15] above, which is for use in a front panel.

[0080] [3-1] A laminated film comprising a cured resin layer (A) and a cured resin layer (D) laminated in sequence on at least one side surface of a substrate film, wherein the cured resin layer (A) is a cured product of a curable resin composition (A') comprising (Aa) a binder, (Ab) a crosslinking agent and (Ac) particles, and the cured resin layer (D) is a cured product of a curable resin composition (D') comprising (Da) a (meth)acrylate having three or more functional groups, (Db) a polymer containing a quaternary ammonium salt group, and (Dc) a compound having a fluorine atom structure and a cyclic siloxane structure.

[0081] [3-2] The laminated film according to [3-1] above, wherein, when the surface of the cured resin layer (D) is subjected to the following steel wool resistance test, the change rate of the film haze after 1000 reciprocating cycles is less than 1%.

[0082] (Steel wool resistance test)

[0083] Using a friction tester and #0000 steel wool, a load of 1 kg was applied to the outermost surface of the cured resin layer (D) in a 2 cm square, and the layer was rubbed back and forth 1000 times at a speed of 50 mm / sec. The haze value of the laminated film before and after friction was measured, and the rate of change compared to the initial film haze (film haze before friction) was calculated.

[0084] Change rate (%) = (film haze after friction - initial film haze) / initial film haze × 100

[0085] [3-3] The laminated film according to [3-1] or [3-2] above, wherein the film haze is 1.0% or less.

[0086] [3-4] The laminated film according to any one of [3-1] to [3-3] above, wherein the light transmittance at a wavelength of 380 nm on the side of the cured resin layer (D) is 3% or less.

[0087] [3-5] The laminated film according to any one of [3-1] to [3-4] above, wherein the maximum reflectance difference at a wavelength of 500 to 600 nm on the surface of the cured resin layer (D) is 1.5% or less.

[0088] [3-6] The laminated film according to any one of [3-1] to [3-5] above, wherein the base film contains a UV absorber.

[0089] [3-7] The laminated film according to any one of [3-1] to [3-6] above, wherein the (Ac) particles are two types of particles having different particle sizes.

[0090] [3-8] The laminated film according to any one of [3-1] to [3-7] above, wherein the binder (Aa) contains a compound having a condensed polycyclic aromatic structure.

[0091] [3-9] The laminated film according to any one of [3-1] to [3-8] above, wherein the base film is a polyester film.

[0092] [3-10] The laminated film according to any one of [3-1] to [3-9] above, wherein the base film is a polyethylene terephthalate (PET) film.

[0093] [3-11] The laminated film according to [3-9] above, wherein the retardation (Re) of the polyester film is 1400 nm or less.

[0094] [3-12] The laminated film according to [3-9] above, wherein the variation in retardation (Re) in the width direction of the polyester film is 10 nm / m or more and 600 nm / m or less.

[0095] [3-13] The laminated film according to any one of [3-1] to [3-12] above, wherein the thickness of the cured resin layer (D) is 10.0 μm or less.

[0096] [3-14] The laminated film according to any one of [3-1] to [3-13] above, which is for surface protection.

[0097] [3-15] The laminated film according to any one of [3-1] to [3-14] above, which is for use in displays.

[0098] [3-16] The laminated film according to any one of [3-1] to [3-15] above, which is for use in a front panel.

[0099] Effects of the Invention

[0100] According to the present invention, it is possible to provide a laminated film which is excellent in repeated folding characteristics and scratch resistance for practical use and in which interference fringes are hardly observed.

[0101] In addition, a laminated film can be proposed which has moderate flexibility of a hard coat layer, is excellent in practical repeated folding characteristics and scratch resistance, has good antistatic properties, and has hardly visible interference fringes.

[0102] Furthermore, a laminated film can be proposed which can achieve both antistatic and antifouling properties, has little visible interference fringes, is excellent in abrasion resistance, and has repeated folding characteristics and scratch resistance that satisfy practical use. BRIEF DESCRIPTION OF THE DRAWINGS

[0103] Figure 1 This is a cross-sectional view for explaining the structure of a laminated thin film. DETAILED DESCRIPTION

[0104] Next, the present invention will be described based on an embodiment example. However, the present invention is not limited to the embodiment described below.

[0105] The laminated film of the present invention is characterized in that it has a structure in which a cured resin layer (A) and a cured resin layer (B) are sequentially laminated on at least one side of a substrate film, wherein the cured resin layer (A) is a cured product of a curable resin composition (A') containing a binder (Aa), and the cured resin layer (B) is a cured product of a curable resin composition (B') containing (X) (meth)acrylic acid urethane and (Y) a compound having a cyclic siloxane skeleton.

[0106] Hereinafter, three embodiments will be described in detail.

[0107] [First embodiment]

[0108] The laminated film of the first embodiment of the present invention has a structure in which a cured resin layer (A) and a cured resin layer (B) are sequentially laminated on at least one side of a substrate film (hereinafter, sometimes referred to as "the present substrate film"). The cured resin layer (A) is a cured product of a curable resin composition (A') containing (Aa) a binder, (Ab) a crosslinking agent, and (Ac) particles, and the cured resin layer (B) is a cured product of a curable resin composition (B') containing (X) (meth)acrylic acid urethane and (Y) a compound having a cyclic siloxane skeleton. In addition, the (Aa) binder contained in the cured resin layer (A) contains a compound having a condensed polycyclic aromatic structure.

[0109] It should be noted that the present laminated film may include other layers as long as it has the above-mentioned configuration.

[0110] Figure 1 2 is a cross-sectional view for explaining the structure of the laminated film. Figure 1 As shown, the laminated film 10 includes a base film 2 , and a cured resin layer (A) 4 and a cured resin layer (B) 6 are sequentially provided on the base film 2 . Figure 1 In the figure, a structure in which a cured resin layer (A) 4 and a cured resin layer (B) 6 are sequentially provided on one side of a substrate film 2 is shown, and the cured resin layer (A) 4 and the cured resin layer (B) 6 may also be provided on both sides of the substrate film 2. It should be noted that other layers may be provided between the substrate film 2 and the cured resin layer (A) 4, and between the cured resin layer (A) 4 and the cured resin layer (B) 6, respectively, and the substrate film 2 and the cured resin layer (A) 4, and the cured resin layer (A) 4 and the cured resin layer (B) 6 are preferably stacked in a directly contacting manner.

[0111] Since the laminated film of the present invention has the above-mentioned structure, it has excellent repeated bending characteristics (bending resistance) and scratch resistance in actual use. In the laminated film of the present invention, it becomes a structure in which a cured resin layer (A) and a cured resin layer (B) are sequentially laminated on at least one side of the base film, and the cured resin layer (B) is a cured product formed by curing a curable resin composition containing (X) acrylic acid carbamate and (Y) a compound having a cyclic siloxane skeleton, so the cured resin layer has flexibility and can also take into account both scratch resistance (SW resistance, for example, more than 2000 times) and repeated bending (under the condition of R = 1.5, it can be bent 200,000 times) at a high level. The (Y) compound having a cyclic siloxane skeleton in the cured resin layer (B) is different from the usual particle addition system, and can improve the sliding property of the surface of the cured resin layer, resulting in less adhesion (resistance) to pressure from the outside, which can be avoided smoothly, so it is speculated that the scratch resistance of the laminated film is improved.

[0112] In addition, the laminated film of the present invention has the above-mentioned structure, so the generation of interference fringes is suppressed. In the laminated film of the present invention, a cured resin layer (A) and a cured resin layer (B) are sequentially stacked on at least one side of the base film. Since the cured resin layer (A) and the cured resin layer (B) having a specified composition are sequentially stacked, the light interference becomes smaller and the generation of interference fringes is suppressed. The generation of interference fringes tends to be easily generated when the refractive index difference between the base film and the cured resin layer is large. In the present invention, by containing particles in the cured resin layer (A), the refractive index difference between the base film and the cured resin layer (A) can be reduced, and by using a compound with a specific structure as the (Aa) binder contained in the curable resin composition (A'), the generation of interference fringes can be suppressed.

[0113] Hereinafter, the laminated film according to the first embodiment of the present invention will be described in further detail.

[0114] <Base film>

[0115] The laminated film of the present invention has a substrate film. The material and structure of the substrate film are not limited as long as it can obtain the required sufficient rigidity and repeated bending property, but from the viewpoint of having appropriate flexibility and excellent repeated bending property and scratch resistance in practical use, it is preferably a polyester film or a polyimide film, more preferably a polyester film, and particularly preferably a polyethylene terephthalate (PET) film.

[0116] The base film may have a single-layer structure or a multi-layer structure.

[0117] When the substrate film is a multilayer structure, it may be a multilayer structure of 4 or more layers, in addition to a 2-layer or 3-layer structure, as long as it does not exceed the gist of the present invention. In a preferred embodiment, the substrate film is a multilayer structure, and a 3-layer structure is particularly preferred.

[0118] When the substrate film is a single-layer or multi-layer structure, the main component resin of each layer is preferably polyester or polyimide (PI). A film whose main component resin is polyester or polyimide is called "polyester film" or "polyimide film".

[0119] At this time, "main component resin" refers to the resin with the largest content in the resin constituting the substrate film. The content of the main component resin is preferably 50% by mass or more, more preferably 70% by mass or more, and further preferably 80% by mass or more relative to the total mass of the resin constituting the substrate film. In addition, the content of the main component resin may also be 100% by mass of the resin constituting the substrate film.

[0120] It should be noted that each layer constituting the base film may contain other resins other than polyester or polyimide or components other than resin as long as the main component resin thereof is polyester or polyimide.

[0121] (Polyester)

[0122] The polyester (hereinafter referred to as "the present polyester") which is the main component resin constituting the base film may be a homopolyester or a copolyester.

[0123] When the polyester includes a homopolyester, the polyester is preferably obtained by polycondensing an aromatic dicarboxylic acid and an aliphatic diol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalene dicarboxylic acid. Examples of the aliphatic diol include ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol.

[0124] In addition, when the polyester is a copolyester, it is preferably a copolymer containing 30 mol% or less of the third component. Examples of the dicarboxylic acid component of the copolyester include isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalene dicarboxylic acid, and sebacic acid. On the other hand, examples of the diol component include ethylene glycol, diethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, and neopentyl glycol. One or more of these third components may be used.

[0125] As the polymerization catalyst in the polyester polycondensation, known catalysts such as antimony compounds, germanium compounds, titanium compounds, and aluminum compounds can be used. Among these, it is preferred to use at least one selected from antimony compounds and titanium compounds as the catalyst in the present invention.

[0126] Specific examples of representative polyesters include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polybutylene naphthalate (PBN), polyethylene furanoate (PEF), etc. Among them, PET and PEN are preferred from the viewpoint of ease of handling, and PET is most preferred.

[0127] When the main component resin constituting the base film is polyethylene terephthalate, for example, the film is referred to as a “polyethylene terephthalate film.” The same applies when other resins are the main component resins.

[0128] (Polyimide)

[0129] As the substrate film, a polyimide film is also suitable in addition to a polyester film. Regarding the imidization of polyimide, the following method is exemplified: for example, a diamine and a dianhydride, particularly an aromatic dianhydride and an aromatic diamine are polymerized in a 1:1 equivalent ratio to form a polyamic acid, followed by imidization.

[0130] Examples of the aromatic dianhydride include 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA), 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride (TDA), pyromellitic dianhydride (1,2,4,5-benzenetetracarboxylic dianhydride, PMDA), benzophenonetetracarboxylic dianhydride (BTDA), biphenyltetracarboxylic dianhydride (BPDA), and dicarboxyphenyldimethylsilane dianhydride (SiDA). These may be used alone or in combination of two or more.

[0131] In addition, as aromatic diamines, oxydiphenylamine (ODA), p-phenylenediamine (pPDA), m-phenylenediamine (mPDA), p-methylenedianiline (pMDA), m-methylenedianiline (mMDA), bistrifluoromethylbenzidine (TFDB), cyclohexanediamine (13CHD, 14CHD), bisaminohydroxyphenylhexafluoropropane (DBOH), etc. are exemplified. These may be used alone or in combination of two or more.

[0132] (Other resin components)

[0133] The main component resin of each layer constituting the substrate film is preferably polyester or polyimide (PI), but the substrate film may also have a layer with other resins other than polyester and polyimide as the main component resin. As the main component resin in this case, for example, epoxy resin, polyarylate, polyether sulfone, polycarbonate, polyether ketone, polysulfone, polyphenylene sulfide, polyester liquid crystal polymer, triacetyl cellulose, cellulose derivatives, polypropylene, polyamides, polycycloolefins, etc. can be exemplified.

[0134] (Particles)

[0135] The base film may contain particles mainly for the purpose of imparting lubricity to the film surface and preventing scratches from being generated in each process.

[0136] The type of the particles is not particularly limited as long as they can impart lubricity. For example, inorganic particles such as silicon dioxide, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide; organic particles such as acrylic resin, styrene resin, urea-formaldehyde resin, phenolic resin, epoxy resin, and benzoguanamine resin, etc., can be listed. These can be used alone or in combination of two or more.

[0137] Furthermore, as the particles, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst in a polyester production process may be used.

[0138] The shape of the particles is not particularly limited and may be, for example, spherical, blocky, rod-like, flat, or the like.

[0139] In addition, there are no particular restrictions on the hardness, specific gravity, color, etc. of the particles. These series of particles can be used in combination of two or more types as needed.

[0140] The average particle size of the particles is preferably 5 μm or less, more preferably 3 μm or less, and further preferably 2.5 μm or less. By setting the average particle size of the particles to be below the upper limit, the surface roughness of the substrate film can be within a suitable range, and undesirable conditions such as when a cured resin layer containing various curing compositions is formed in a subsequent process can be prevented. On the other hand, the average particle size of the particles is preferably 0.01 μm or more, and further preferably 0.5 μm or more.

[0141] The content of the particles is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less relative to the total mass of the substrate film. In addition, the content of the particles is preferably 0.0003% by mass or more, more preferably 0.001% by mass or more, and further preferably 0.01% by mass or more relative to the total mass of the substrate film. If the average particle size of the particles is within the above range, the surface roughness of the substrate film can be within a suitable range, which can prevent the formation of a cured resin layer containing various cured compositions in subsequent steps.

[0142] There is no particular limitation on the method of adding particles to the substrate film, and a conventionally known method can be used. For example, the particles can be added at any stage of manufacturing a raw resin such as polyester. When the substrate film is polyester, the particles are preferably added after the esterification or transesterification reaction is completed.

[0143] (Other ingredients)

[0144] The base film may contain other components such as conventionally known antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, ultraviolet absorbers, etc. as required. In particular, in order to ensure the weather resistance of the laminated film, the base film preferably contains an ultraviolet absorber.

[0145] (thickness)

[0146] From the viewpoint of being able to obtain the required sufficient rigidity and repeated bending properties, the thickness of the substrate film is, for example, preferably 9 μm or more, more preferably 12 μm or more, further preferably 15 μm or more, and particularly preferably 20 μm or more. In addition, the thickness of the substrate film is preferably 125 μm or less, more preferably 100 μm or less, and further preferably 75 μm or less. It should be noted that when the substrate film is a multilayer structure, the total thickness of all layers is preferably within the above range.

[0147] (Method for producing substrate film)

[0148] The substrate film can be formed by, for example, a resin composition by a melt film forming method or a solution film forming method. In the case of a multilayer structure, coextrusion may be used.

[0149] The substrate film may be uniaxially stretched or biaxially stretched, but is preferably a biaxially stretched film from the viewpoint of rigidity.

[0150] Hereinafter, a method for producing a polyester film as an example of a substrate film is described. Generally speaking, first, an undried or dried polyester sheet is supplied to a melt extrusion device using a known method, and heated to a temperature above the melting point of each polymer to melt it. Next, the molten polymer is extruded from a die head, and quenched and solidified on a rotating cooling drum in a manner to reach a temperature below the glass transition temperature, thereby obtaining a substantially amorphous non-oriented sheet. At this time, in order to improve the planarity of the sheet, it is preferred to improve the adhesion between the sheet and the rotating cooling drum. In the present invention, it is preferred to use an electrostatic application densification method and / or a liquid coating densification method.

[0151] From the viewpoint of film strength, the sheet obtained in the above manner is preferably stretched in biaxial directions to form a film. Specifically, the stretching conditions are described, and the unstretched sheet is preferably stretched in the longitudinal direction (machine direction) at 70 to 145° C., preferably at 80 to 120° C. at a stretching ratio of 2.0 to 4.5 times, preferably 3.0 to 4.0 times, to form a uniaxially stretched film.

[0152] Next, the film is stretched in the transverse direction (width direction) which is a direction perpendicular to the longitudinal direction (machine direction) at 90 to 160° C. at a stretching ratio of 3.0 to 6.5 times and 3.5 to 6.0 times to prepare a biaxially stretched film.

[0153] Next, heat treatment (heat setting) is preferably performed at 210 to 260° C. for 10 to 600 seconds under tension or under relaxation within 30%. Furthermore, relaxation of 1 to 10% is preferably performed in the longitudinal and / or transverse directions in the highest temperature zone of the heat treatment and / or the cooling zone at the heat treatment outlet.

[0154] It should be noted that, when the retardation (hereinafter, sometimes simply recorded as "Re") of the substrate film is desired to be suppressed to a small value, the difference between the longitudinal and transverse stretching ratios is preferably small, and the difference is preferably 0.5 times or less, and more preferably 0.3 times or less. In addition, it can also be a low heat treatment temperature, which can be preferably 200°C or less, more preferably 180°C or less, and further preferably 160°C or less. By satisfying the above range, a substrate film having a Re below a certain level can be obtained regardless of the extraction position in the width direction of the film.

[0155] It should be noted that the longitudinal direction (machine direction) of the film refers to the direction in which the film moves during the film manufacturing process, that is, the winding direction of the film roll. The transverse direction (width direction) refers to the direction parallel to the film surface and orthogonal to the longitudinal direction, that is, the direction parallel to the central axis of the roll when the film is rolled.

[0156] (Substrate film properties)

[0157] From the viewpoint of being able to obtain the required sufficient rigidity and repeated bending properties, the tensile elastic modulus of the substrate film (JIS K 7161: 2014) is preferably 2.0 GPa or more, more preferably 2.5 GPa or more, and further preferably 3.0 GPa or more. In addition, the tensile elastic modulus of the substrate film is preferably 9.0 GPa or less, more preferably 8.0 GPa or less, and further preferably 7.0 GPa or less.

[0158] (Delay (Re))

[0159] The retardation (Re) when light of a wavelength of 590 nm is incident on the substrate film, especially the polyester film surface, at an angle of 0° is preferably 1400 nm or less, more preferably 1200 nm or less, and particularly preferably 1000 nm or less. The closer the retardation (Re) when light of a wavelength of 590 nm is incident on the polyester film surface at an angle of 0°, the more preferably it is 0, and it can be 50 nm or more, and further can be 100 nm or more.

[0160] The change in retardation (Re) in the fast axis direction (width direction) when light with a wavelength of 590 nm is incident on the polyester film surface at an angle of 0° is preferably 5 nm / m or more, more preferably 10 nm / m or more, further preferably 20 nm / m or more, and particularly preferably 50 nm / m or more.

[0161] Furthermore, the variation of the retardation (Re) in the fast axis direction (width direction) when light of a wavelength of 590 nm is incident on the polyester film surface at an angle of 0° is preferably 600 nm / m or less, more preferably 550 nm / m or less.

[0162] Here, the change in the retardation (Re) in the fast axis direction (width direction) when light of a wavelength of 590 nm is incident on the polyester film surface at an angle of 0° is calculated as follows: the difference between the maximum and minimum retardation values ​​obtained from a 3.5 cm×3.5 cm film sample is calculated, and the difference is divided by the distance (m) in the fast axis direction (width direction) between the positions where the maximum and minimum values ​​are obtained in the film sample. Specifically, it is calculated by the following formula.

[0163] Change in the retardation (Re) in the fast axis direction (width direction) (nm / m) = (maximum retardation value - minimum retardation value) / distance between the maximum value position and the minimum value position in the fast axis direction (width direction) (m)

[0164] Furthermore, the width of the range satisfying the above Re condition is preferably 50% or more, more preferably 55% or more, and particularly preferably 60% or more relative to the total width of the film. It should be noted that the width of the range satisfying the above Re condition may also be 100% relative to the total width of the film.

[0165] In particular, the width of the range of the variation of the retardation (Re) in the fast axis direction (width direction) of 10 to 600 nm / m per 1 m width is preferably 50% or more, more preferably 60% or more, and further preferably 70% or more relative to the total width of the film. By setting the ratio of the variation of the retardation (Re) in the fast axis direction (width direction) of 10 to 600 nm / m to the above range, for example, in a wide film corresponding to a large-screen display of 40 inches or more, preferably 50 inches or more, the variation range of the retardation in the film surface can be suppressed, and the generation of rainbow spots can be reduced when used in combination with various light sources.

[0166] <Cured resin layer (A) and cured resin layer (B)>

[0167] The laminated film of the present invention comprises a cured resin layer (A) and a cured resin layer (B). The laminated film has a laminated structure in which a cured resin layer (A) is provided on at least one side of a substrate film, and a cured resin layer (B) is further provided on the surface side thereof. The cured resin layer (A) is a cured product of a curable resin composition (A') comprising a binder (Aa), a crosslinker (Ab) and particles (Ac), and the cured resin layer (B) is a cured product of a curable resin composition (B') comprising (X) (methyl) acrylic acid carbamate and (Y) a compound having a cyclic siloxane skeleton.

[0168] The thickness of the cured resin layer (A) is preferably 1.0 μm or less, more preferably 0.6 μm or less, further preferably 0.4 μm or less, and particularly preferably 0.2 μm or less. The lower limit of the thickness of the cured resin layer (A) is not particularly limited, and is, for example, 0.01 μm or more, preferably 0.03 μm or more.

[0169] The thickness of the cured resin layer (B) is preferably 10.0 μm or less, more preferably 8.0 μm or less, further preferably 6.0 μm or less, and particularly preferably 5.0 μm or less. The lower limit of the thickness of the cured resin layer (B) is not particularly limited, for example, preferably 1.0 μm or more. By setting the thickness of the cured resin layer (B) to be above the above lower limit, the cured resin layer (B) can be used to appropriately protect the substrate film. In addition, if the thickness of the cured resin layer (B) is set to be below the above upper limit, the laminated film having the cured resin layer (B) can prevent curling and heat wrinkling, and can ensure good planarity.

[0170] It should be noted that, from the viewpoint of bendability, the total thickness of the cured resin layer (A) and the cured resin layer (B) is preferably 10.0 μm or less, more preferably 8.0 μm or less, further preferably 6.0 μm or less, and particularly preferably 5.0 μm or less. The lower limit of the total thickness of the cured resin layer (A) and the cured resin layer (B) is not particularly limited, and is preferably 1.0 μm or more, for example.

[0171] The thickness of each of the cured resin layer (A) and the cured resin layer (B) can be measured, for example, using SAICAS (DN-01 type made by DAIPLA WINTESCO., LTD.). Specifically, first, a laminated film having a cured resin layer (A) and a cured resin layer (B) is bonded to a glass slide using the "Aron Alpha Series" made by Toa Synthetics Co., Ltd. to make a SAICS (SAICAS) sample. The obtained SAICS sample is set in SAICAS (DN-01 type made by DAIPLA WINTES CO., LTD.), and first a diamond tip is used to cut a cut of 300 μm in width and 1 μm in depth (when cutting the cut, a single crystal diamond knife with a V angle size of 80°, a front angle of 5°, and a back angle of 5° is used). The measurement was performed by placing a 300 μm wide boron nitride cutter on a sample with a pre-cut 300 μm wide cut, and measuring the film thickness of each cured resin layer at an arbitrary depth, a horizontal speed of 1 μm / s, and a vertical speed of 0.5 μm / s (a boron nitride cutter with a blade width of 0.3 mm, a front angle of 20°, and a back angle of 10° was used during the measurement). The material strength was measured based on the vertical displacement position and the cutting force, and the thickness of each layer was calculated.

[0172] The light transmittance at a wavelength of 380 nm on the surface of the cured resin layer (B) is preferably 3.0% or less, more preferably 2.8% or less. The lower limit of the light transmittance at a wavelength of 380 nm on the surface of the cured resin layer (B) is not particularly limited and may be 0%. By setting the light transmittance at a wavelength of 380 nm on the surface of the cured resin layer (B) to within the above range, the bonded counterpart member can be prevented from being degraded due to ultraviolet rays. When measuring the light transmittance at a wavelength of 380 nm, for example, a spectrophotometer (manufactured by Hitachi High-Tech Corporation., U-3900H) can be used.

[0173] The absolute reflectivity of the surface of the cured resin layer (B) at a wavelength of 550 nm is preferably 1% or more, more preferably 2% or more, and further preferably 3% or more. In addition, the absolute reflectivity of the surface of the cured resin layer (B) at a wavelength of 550 nm is preferably 10% or less, more preferably 8% or less, and further preferably 6% or less. By setting the absolute reflectivity of the surface of the cured resin layer (B) at a wavelength of 550 nm to within the above range, it is also possible to impart anti-glare properties when used as a cover film for a display screen.

[0174] The absolute reflectivity at a wavelength of 550 nm on the surface of the cured resin layer (B) is a value measured by the following method. First, a black tape is attached to the side of the laminated film on which the cured resin layer is not laminated, and the absolute reflectivity at a wavelength of 550 nm on the side of the cured resin layer is measured using a spectrophotometer. The absolute reflectivity is calculated by the ratio of the amount of light reflected by the cured resin layer of the laminated film to the amount of light obtained by directly measuring the light from the light source without using a reference plate.

[0175] Absolute reflectivity (%) = light reflected by the cured resin layer of the laminated film / light used × 100

[0176] In addition, the refractive index of the cured resin layer (B) can also be adjusted in advance in a manner that is not likely to affect light interference. For example, if a low refractive index layer is made of about 1.53, the desired scratch resistance and repeated bending properties can be achieved by adopting a structure that can achieve the low refractive index of the cured resin layer (B).

[0177] From the viewpoint of reducing interference unevenness, the refractive index of the cured resin layer (B) is preferably from 1.46 to 1.60, more preferably from 1.49 to 1.57.

[0178] The elongation at break of the cured resin layer (A) and the cured resin layer (B) (hereinafter, the cured resin layer (A) and the cured resin layer (B) are collectively referred to as the cured resin layer) is preferably 0.5% or more, more preferably 1.0% or more, and further preferably 1.5% or more. In addition, the elongation at break of the cured resin layer is preferably 3.0% or less, more preferably 2.5% or less, and further preferably 2.0% or less. By setting the elongation at break of the cured resin layer within the above range, it is easy to obtain a laminated film with excellent repeated bending characteristics (bending resistance) in practical use.

[0179] In addition, the elongation at break here is a value of the cured resin layer which laminated|stacked the cured resin layer (A) and the cured resin layer (B).

[0180] The elongation at break of the cured resin layer is a value measured by the following method. First, a laminated film having a cured resin layer (A) and a cured resin layer (B) laminated sequentially on the surface of a substrate film is cut into a strip having a width of 10 mm and a length of 150 mm to prepare a test piece, and the test piece is clamped by the clamp of a tensile testing machine in such a way that the initial distance between the clamps becomes 50 mm. Then, the sample is stretched at a stretching speed of 5 m / min, and the displacement of the cracks in the cured resin layer is visually confirmed, and the elongation is calculated by the following formula.

[0181] Elongation (%) = (length at break - initial length) / initial length × 100

[0182] (Surface conditions of each layer)

[0183] The surface of the cured resin layer (A) may be uneven or flat, but is preferably flat from the viewpoint of appearance (surface gloss).

[0184] In addition, the surface of the cured resin layer (B) may be concavoconvex or flat, preferably flat from the viewpoint of appearance (surface gloss). On the other hand, from the viewpoint of imparting anti-glare properties, it may be concavoconvex. It can be arbitrarily selected according to the required characteristics.

[0185] <Curable resin composition>

[0186] Hereinafter, the curable resin composition (A′) and the curable resin composition (B′) for forming the cured resin layer (A) and the cured resin layer (B) will be described.

[0187] (Curable resin composition (A'))

[0188] The curable resin composition (A') contains (Aa) a binder, and preferably further contains (Ab) a crosslinking agent and (Ac) particles. Hereinafter, each component will be described in detail.

[0189] (Aa) Binder

[0190] As the binder (Aa) used in the curable resin composition (A'), a resin can be used. As the resin constituting the binder, polyester resin, acrylic resin, carbamate resin, etc. can be listed. In addition, polyvinyl compounds (polyvinyl alcohol, polyvinyl chloride, vinyl chloride-vinyl acetate copolymer, etc.), polyalkylene glycol, polyalkylene imine, methyl cellulose, hydroxy cellulose, starch, etc. can also be used in combination as a binder. Among these binders, it is preferred to use at least one selected from the group consisting of polyester resin, acrylic resin and carbamate resin, and it is more preferred to use polyester resin.

[0191] The content of the binder (Aa) is preferably 1 to 90% by mass, more preferably 3 to 85% by mass, and even more preferably 5 to 80% by mass relative to the total nonvolatile content (total solid content) in the curable resin composition (A'). By setting the content of the binder within the above range, good film forming properties can be ensured.

[0192] (Polyester resin)

[0193] The polyester resin can be obtained by polycondensing the following polycarboxylic acids and polyhydroxy compounds as main components. Specifically, as the polycarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalate, 5-sodium sulfoisophthalate, 2,6-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, glutaric acid, succinic acid, trimellitic acid, pyromellitic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof can be used. As the polyvalent hydroxy compound, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, terephthalyol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene ether glycol, dimethylolpropionic acid, glycerol, trimethylolpropane, sodium dimethylolethylsulfonate, potassium dimethylolpropionate, etc. can be used. It is sufficient to select one or more of these compounds appropriately and synthesize the polyester resin by polycondensation reaction in a conventional method.

[0194] (Acrylic resin)

[0195] The acrylic resin is not particularly limited and may be appropriately selected within a range that allows the effects of the present invention to be achieved. For example, (meth)acrylate is preferred.

[0196] Examples of the monofunctional (meth)acrylate include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate; and hydroxyl-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutyl hydroxyfumarate, and monobutyl hydroxyitaconate.

[0197] In addition, examples of difunctional (meth)acrylates include: alkanediol di(meth)acrylates such as 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and tricyclodecane dihydroxymethyl di(meth)acrylate; bisphenol-modified di(meth)acrylates such as bisphenol A ethylene oxide-modified di(meth)acrylate and bisphenol F ethylene oxide-modified di(meth)acrylate; polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, urethane di(meth)acrylate, epoxy di(meth)acrylate, and the like.

[0198] In addition, examples of the trifunctional or higher polyfunctional (meth)acrylate include: dipentaerythritol hexa(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate; ethylene oxide-modified (meth)acrylates such as ethylene oxide-modified dipentaerythritol hexa(meth)acrylate and ethylene oxide-modified pentaerythritol tetra(meth)acrylate; and isocyanuric acid-modified tri(meth)acrylates such as isocyanuric acid ethylene oxide-modified tri(meth)acrylate and ε-caprolactone-modified isocyanuric acid tri(acryloyloxyethyl) ester.

[0199] Furthermore, examples of (meth)acrylates include (meth)acrylates having an epoxy group, such as glycidyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, etc. Among these, glycidyl (meth)acrylate is preferred, and glycidyl methacrylate is particularly preferred, especially in view of good reactivity and ease of use of the material.

[0200] In addition, the (meth)acrylates preferably include carboxyl group-containing (meth)acrylates such as acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, citraconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0201] (Urethane resin)

[0202] Urethane resin refers to a polymer compound having a urethane structure in the molecule. Urethane resin is usually prepared by the reaction of a polyol and a polyisocyanate. Examples of polyols include polycarbonate polyols, polyester polyols, polyether polyols, polyolefin polyols, and acrylic polyols. These compounds can be used alone or in combination.

[0203] Polycarbonate polyols can be obtained by a dealcoholization reaction between polyols and carbonate compounds. Examples of polyols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, and 3,3-dihydroxymethylheptane. Examples of carbonate compounds include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, and ethylene carbonate. Examples of polycarbonate polyols obtained by reactions thereof include poly(1,6-hexylene) carbonate and poly(3-methyl-1,5-pentylene) carbonate.

[0204] Examples of the polyester polyols include polycarboxylic acids (malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, isophthalic acid, etc.) or their anhydrides and polyols (ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, benzyl alcohol, bishydroxyethoxybenzene, alkyldialkanolamine, lactone diol, etc.

[0205] Examples of the polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.

[0206] As isocyanate compounds for obtaining urethane resins, there are exemplified aromatic diisocyanates such as toluene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and toluidine diisocyanate; aliphatic diisocyanates having aromatic rings such as α,α,α',α'-tetramethylxylylene diisocyanate; aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidene dicyclohexyl diisocyanate, etc. These may be used alone or in combination of a plurality of them.

[0207] A chain extender may be used when synthesizing the urethane resin. The chain extender is not particularly limited as long as it has two or more active groups that react with isocyanate groups. Generally, chain extenders having two hydroxyl groups or amino groups are mainly used.

[0208] Examples of the chain extender having two hydroxyl groups include diols such as aliphatic diols such as ethylene glycol, propylene glycol, and butanediol, aromatic diols such as benzyl alcohol and bishydroxyethoxybenzene, and ester diols such as neopentyl glycol hydroxypivalate. In addition, examples of the chain extender having two amino groups include aromatic diamines such as toluenediamine, xylylenediamine, and diphenylmethanediamine; aliphatic diamines such as ethylenediamine, propylenediamine, hexylenediamine, 2,2-dimethyl-1,3-propylenediamine, 2-methyl-1,5-pentanediamine, trimethylhexanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine; and alicyclic diamines such as 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, dicyclohexylmethanediamine, isopropylcyclohexyl-4,4′-diamine, 1,4-diaminocyclohexane, and 1,3-bisaminomethylcyclohexane.

[0209] (Compounds having a condensed polycyclic aromatic structure)

[0210] In the laminated film of the present invention, the binder (Aa) contained in the curable resin composition (A') forming the cured resin layer (A) preferably contains a compound having a condensed polycyclic aromatic structure. By including this compound, it becomes easy to adjust the refractive index of the cured resin layer (A).

[0211] Examples of the condensed polycyclic aromatic group include naphthalene, anthracene, phenanthrene, tetracene, benzo[a]anthracene, benzo[a]phenanthrene, pyrene, benzo[c]phenanthrene, and perylene as shown in the following formula.

[0212] The compound having a condensed polycyclic aromatic structure refers to a compound containing a condensed polycyclic aromatic as exemplified by the following formula, or a compound containing a structure derived from a condensed polycyclic aromatic as exemplified by the following formula.

[0213]

[0214] Considering the coating property on a base film such as a polyester film, the compound having a condensed polycyclic aromatic structure is preferably a polymer compound such as a polycyclic polyester resin. In particular, the compound having a condensed polycyclic aromatic structure is preferably a polycyclic polyester resin, which is preferred because more condensed polycyclic aromatics can be introduced into the polycyclic polyester resin. It should be noted that in this specification, the polycyclic polyester resin refers to a polyester resin having a condensed polycyclic aromatic structure.

[0215] As a method for incorporating a condensed polycyclic aromatic structure into a polyester resin, for example, there is a method of introducing two or more hydroxyl groups as substituents into the condensed polycyclic aromatic to form a diol component or a polyhydroxyl component, or introducing two or more carboxylic acid groups to use as a dicarboxylic acid component or a polycarboxylic acid component for polymerization of the polyester resin.

[0216] In the manufacturing process of the laminated film, from the viewpoint of being difficult to color, the compound having a condensed polycyclic aromatic structure contained in the cured resin layer (A) is preferably a compound having a naphthalene skeleton. In addition, from the viewpoint of good adhesion and transparency with the cured resin layer (B) formed on the cured resin layer (A), a resin having a naphthalene skeleton can be suitably used as a polyester constituent. As the naphthalene skeleton, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid and 2,7-naphthalene dicarboxylic acid can be cited as representatives.

[0217] It should be noted that by introducing a substituent containing a sulfur element, an aromatic substituent such as a phenyl group, a halogen group, etc., in addition to a hydroxyl group and a carboxylic acid group into the condensed polycyclic aromatic group, it is expected that the refractive index can be improved. From the viewpoint of coating properties and adhesion, substituents such as an alkyl group, an ester group, an amide group, a sulfonic acid group, a carboxylic acid group, and a hydroxyl group can also be introduced.

[0218] The proportion of the condensed polycyclic aromatic ring in the compound having a condensed polycyclic aromatic group is preferably 5 to 80% by mass, more preferably 10 to 60% by mass. The proportion of the condensed polycyclic aromatic ring refers to, for example, the content of naphthalene rings in a polyester resin having a condensed polycyclic aromatic group as a condensed polycyclic aromatic group.

[0219] The content of the compound having a condensed polycyclic aromatic group in the curable resin composition (A') is preferably 80% by mass or less, more preferably 5 to 70% by mass, and even more preferably 10 to 50% by mass, relative to the total nonvolatile content (total solid content) in the curable resin composition A.

[0220] By setting the content of the compound having fused polycyclic aromatic groups in the curable resin composition (A') to be within the above range, it becomes easy to adjust the refractive index of the cured resin layer (A) itself, and it is easy to reduce the generation of interference fringes after the formation of the cured resin layer (B). It should be noted that the content of the compound having fused polycyclic aromatic groups can be obtained, for example, by dissolving and extracting the cured resin layer (A) using an appropriate solvent or warm water, separating using chromatography, analyzing the structure using NMR and IR, and further analyzing using thermal decomposition GC-MS (gas chromatography mass spectrometry), optical analysis, etc.

[0221] (Ab) Cross-linking agent

[0222] As cross-linking agent, can list: oxazoline compound, melamine compound, epoxy compound, carbodiimide compound, isocyanate compound etc.Among these cross-linking agents, from the viewpoint of improving the adhesion with substrate film, preferably use at least one selected from the group consisting of oxazoline compound, epoxy compound, isocyanate compound, melamine compound and carbodiimide compound, more preferably use at least one selected from oxazoline compound, epoxy compound and isocyanate compound, further preferably use at least one selected from oxazoline compound and epoxy compound, particularly preferably use oxazoline compound and epoxy compound in combination.

[0223] The content of the crosslinking agent is preferably 2 to 80% by mass, more preferably 4 to 60% by mass, and further preferably 10 to 40% by mass relative to the total non-volatile content (total solid content) in the curable resin composition (A'). By setting the content of the crosslinking agent within the above range, the adhesion between the cured resin layer (A) and the cured resin layer (B) as a cured product can be more effectively improved.

[0224] (Oxazoline Compounds)

[0225] Oxazoline compound refers to the compound with oxazoline group in molecule, and is particularly preferably the polymer containing oxazoline group.The polymer containing oxazoline group can be made by the monomer homopolymerization of addition polymerization containing oxazoline group or the polymerization with other monomers.As the monomer containing oxazoline group of addition polymerization, can list: 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-ethyl-2-oxazoline etc., can use their one or more mixture of two kinds.Wherein, 2-isopropenyl-2-oxazoline is also easy to obtain industrially, therefore suitable. As other monomers, there are no restrictions as long as they are monomers copolymerizable with the addition polymerizable oxazoline group-containing monomer, and examples thereof include: (meth)acrylates such as alkyl (meth)acrylates (as the alkyl group, there are methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, cyclohexyl); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrenesulfonic acid and its salts (sodium salt, potassium salt, ammonium salt, tertiary amine salt, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylamide, N-alkyl ( Unsaturated amides such as (meth)acrylamide, N,N-dialkyl (meth)acrylamide (as the alkyl group, there are methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, cyclohexyl, etc.); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride, vinylidene chloride, and vinyl fluoride; α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene, etc., and one or more of these monomers can be used.

[0226] (Melamine compounds)

[0227] A melamine compound refers to a compound having a melamine skeleton in the compound. For example, a hydroxyalkylated melamine derivative, a compound obtained by reacting a hydroxyalkylated melamine derivative with an alcohol to partially or completely etherify it, and a mixture thereof can be used. As the alcohol used for etherification, methanol, ethanol, isopropanol, n-butanol, isobutanol, etc. can be suitably used. In addition, as the melamine compound, any one of a monomer or a multimer above a dimer can be used, and a mixture thereof can also be used. Furthermore, a compound obtained by co-condensing a part of melamine with urea or the like can also be used, and a catalyst can also be used to improve the reactivity of the melamine compound.

[0228] (Epoxides)

[0229] Epoxy compounds refer to compounds having epoxy groups in the molecule, and examples thereof include condensates of epichlorohydrin with hydroxyl groups or amino groups of ethylene glycol, polyethylene glycol, glycerol, polyglycerol, bisphenol A, etc., polyepoxy compounds, diepoxy compounds, monoepoxy compounds, glycidylamine compounds, etc. Examples of polyepoxy compounds include sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, etc. Examples of diepoxy compounds include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether. Examples of monoepoxy compounds include allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether. Examples of glycidylamine compounds include N,N,N',N',-tetraglycidyl-m-xylenediamine and 1,3-bis(N,N-diglycidylamino)cyclohexane.

[0230] (Carbodiimide compounds)

[0231] The carbodiimide compound refers to a compound having a carbodiimide structure, and is a compound having one or more carbodiimide structures in a molecule. For better adhesion and the like, a polycarbodiimide compound having two or more carbodiimide structures in a molecule is more preferable.

[0232] Carbodiimide compounds can be synthesized by conventionally known techniques, and generally, the condensation reaction of diisocyanate compounds can be used. As diisocyanate compounds, there are no particular limitations, and both aromatic and aliphatic systems can be used, and specifically, toluene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, dicyclohexylmethane diisocyanate, etc. can be cited.

[0233] Furthermore, to improve the water solubility and water dispersibility of the polycarbodiimide compound, a surfactant or a hydrophilic monomer such as polyalkylene oxide, a quaternary ammonium salt of a dialkylamino alcohol, or a hydroxyalkyl sulfonate may be added to the polycarbodiimide compound within a range that does not diminish the effects of the present invention.

[0234] (Isocyanate compounds)

[0235] Isocyanate compounds refer to isocyanates or compounds having an isocyanate derivative structure represented by blocked isocyanates. Examples of isocyanates include aromatic isocyanates such as toluene diisocyanate, xylylene diisocyanate, diphenylmethylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic isocyanates having an aromatic ring such as α,α,α',α'-tetramethylxylylene diisocyanate; aliphatic isocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; alicyclic isocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, methylenebis(4-cyclohexyl isocyanate), and isopropylidene dicyclohexyl diisocyanate. In addition, polymers or derivatives such as biuret compounds, isocyanurate compounds, uretdione compounds, carbodiimide modified bodies of these isocyanates can also be listed. These can be used alone or in combination. Among the above-mentioned isocyanates, in order to avoid yellowing due to ultraviolet rays, aliphatic isocyanates or alicyclic isocyanates are more preferably used than aromatic isocyanates.

[0236] When the isocyanate is used in a blocked state, examples of the blocking agent include: phenolic compounds such as bisulfites, phenol, cresol, and ethylphenol; alcohol compounds such as propylene glycol monomethyl ether, ethylene glycol, benzyl alcohol, methanol, and ethanol; active methylene compounds such as dimethyl malonate, diethyl malonate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone; thiol compounds such as butyl mercaptan and dodecanethiol; lactam compounds such as ε-caprolactam and δ-valerolactam; amine compounds such as diphenylaniline, aniline, and ethyleneimine; oxime compounds such as acetanilide and acetamide, formaldehyde, acetaldehyde oxime, acetone oxime, methyl ethyl ketone oxime, and cyclohexanone oxime, and these may be used alone or in combination of two or more.

[0237] (Ac) Particles

[0238] From the viewpoint of imparting a high refractive index to the cured resin layer (A), the curable resin composition (A') may also contain particles. Examples of the particles include inorganic particles such as silicon dioxide, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide; and organic particles such as acrylic resins, styrene resins, urea-formaldehyde resins, phenolic resins, epoxy resins, and benzoguanamine resins.

[0239] Among them, the cured resin layer (A) preferably contains a metal oxide as the (Ac) particles. When the cured resin layer (A) contains a metal oxide, its refractive index can be increased, and the generation of interference fringes can be more effectively suppressed.

[0240] (Metal Oxide)

[0241] As the metal oxide, it is preferred to use a metal oxide with a high refractive index, preferably a metal oxide with a refractive index of 1.7 or more. As specific examples of the metal oxide, for example, silicon dioxide, zirconium oxide, aluminum oxide (alumina), titanium oxide, tin oxide, yttrium oxide, antimony oxide, indium oxide, zinc oxide, antimony tin oxide, indium tin oxide, etc. can be listed, and these can be used alone or in combination. Among them, it is more suitable to use at least one selected from zirconium oxide and titanium oxide, and it is more suitable to use zirconium oxide from the viewpoint of weather resistance.

[0242] Metal oxide has the worry that adhesion is reduced due to different use forms, so it is preferably used in the state of particles. In addition, from the viewpoint of transparency, its average particle diameter is preferably below 100nm, more preferably below 50nm, and further preferably below 25nm. In addition, about the lower limit of average particle diameter, it is not particularly limited, from the viewpoint of dispersibility, it is preferably above 5nm, and further preferably above 10nm.

[0243] In addition, in order to improve the fixation and sliding properties in the cured resin layer (A), particles other than the above-mentioned metal oxides may also be contained. As specific examples of particles other than metal oxides, silicon dioxide, kaolin, calcium carbonate, organic particles, etc. can be listed, among which silicon dioxide is preferably used from the viewpoint of sliding properties. From the viewpoint of the transparency of the film, the average particle size of the particles other than the metal oxide is preferably less than 1.0 μm, more preferably less than 0.5 μm, and further preferably less than 0.2 μm. In addition, there is no particular limitation on the lower limit of the average particle size of the particles other than the metal oxide, but from the viewpoint of dispersibility, it is preferably more than 20 nm, and more preferably more than 40 nm.

[0244] In addition, from the viewpoint of imparting lubricity, it is preferred to use two kinds of particles having different particle sizes as the particles, and it is more preferred to use a combination of metal oxides having different particle sizes and particles other than metal oxides.

[0245] The average particle size is a value measured by, for example, laser diffraction / scattering, dynamic light scattering (DLS), centrifugal sedimentation, particle tracking analysis (PTA), scanning electron microscopy (SEM), etc. If it is a commercial product, the catalog value can be used.

[0246] The average particle size of the particles can be calculated by a sedimentation method based on the Stokes drag value. As a measuring device, for example, a centrifugal sedimentation particle size distribution measuring device SA-CP3 manufactured by Shimadzu Corporation can be used.

[0247] The content of (Ac) particles relative to the total non-volatile component amount (total solid content) in the curable resin composition (A') forming the cured resin layer (A) is preferably 3% by mass or more, more preferably 5% by mass or more, and further preferably 7% by mass or more. In addition, the content of (Ac) particles relative to the total non-volatile component amount (total solid content) in the curable resin composition (A') is preferably 70% by mass or less, more preferably 50% by mass or less, further preferably 40% by mass or less, and particularly preferably 30% by mass or less. By setting the content of (Ac) particles to within the above range, the transparency and low interference effect of the laminated film can be taken into account.

[0248] In this embodiment, in particular, by using the particles (Ac) of the metal compound or the like in combination with the polycyclic polyester resin (polyester resin having a condensed polycyclic aromatic structure) in the cured resin layer (A), a more excellent low interference effect can be obtained.

[0249] (Curable resin composition (B'))

[0250] Curable resin composition B contains (X) (meth)acrylic acid urethane and (Y) a compound having a cyclic siloxane skeleton.

[0251] The mass average molecular weight of the (X) urethane (meth)acrylate contained in the curable resin composition (B') is preferably 100 or more, preferably 200 or more, and more preferably 400 or more. On the other hand, the upper limit is preferably 500,000 or less, more preferably 400,000 or less, and more preferably 250,000 or less.

[0252] In addition, in the present invention, when the expression "(meth)acrylic acid" is used, it means one or both of "acrylic acid" and "methacrylic acid". The same applies to "(meth)acrylate" and "(meth)acryloyl".

[0253] ((X) (meth) acrylate urethane

[0254] Urethane (meth)acrylate is obtained by reacting an isocyanate compound and a hydroxyl-containing (meth)acrylate compound, or by reacting an isocyanate compound, a polyol compound, and a hydroxyl-containing (meth)acrylate compound. Urethane (meth)acrylate can be used alone or in combination of two or more.

[0255] As isocyanate compounds, for example, polyisocyanate compounds such as aromatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates can be cited. Among them, the isocyanate compounds are preferably diisocyanate compounds. In addition, as isocyanate compounds, isocyanate compounds having an isocyanurate skeleton obtained by isocyanurating diisocyanate compounds can also be used.

[0256] Examples of the aromatic polyisocyanate include tolylene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate.

[0257] As said aliphatic polyisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, lysine triisocyanate etc. are mentioned, for example.

[0258] Examples of the alicyclic polyisocyanate include hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, and 1,4-bis(isocyanatomethyl)cyclohexane.

[0259] Among these, from the viewpoint of excellent yellowing resistance, it is preferred to use aliphatic diisocyanates and alicyclic diisocyanates. In addition, it is also preferred to use isocyanate compounds having an isocyanurate skeleton. From the same viewpoint, it is also preferred to use aliphatic diisocyanates or isocyanurate compounds having an isocyanurate skeleton obtained by isocyanurating alicyclic diisocyanates. Among them, it is more preferred to use isocyanate compounds having an isocyanurate skeleton.

[0260] The isocyanate compounds may be used alone or in combination of two or more.

[0261] The hydroxyl-containing (meth)acrylate is a compound having a hydroxyl group and a (meth)acryloyl group, and examples thereof include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate; 2-hydroxyethyl acryloyl phosphate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, dipropylene glycol (meth)acrylate, fatty acid-modified glycidyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and (meth)acrylate. Monofunctional hydroxyl-containing (meth)acrylates containing one ethylenically unsaturated group, such as 2-hydroxy-3-(meth)acryloyloxypropyl ester; bifunctional hydroxyl-containing (meth)acrylates containing two ethylenically unsaturated groups, such as glycerol di(meth)acrylate and 2-hydroxy-3-acryloyloxypropyl methacrylate; trifunctional or higher hydroxyl-containing (meth)acrylates containing three or more ethylenically unsaturated groups, such as pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, and ethylene oxide-modified dipentaerythritol penta(meth)acrylate, etc. These can be used alone or in combination of two or more.

[0262] Among these, from the viewpoint of excellent reactivity and versatility, and excellent balance between the scratch resistance and the flexural properties of the cured resin layer, it is preferred to use a (meth)acrylate compound containing three or more ethylenically unsaturated groups, and it is particularly preferred to use pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate.

[0263] The polyol compound may be a compound having two or more hydroxyl groups (excluding the hydroxyl-containing (meth)acrylate).

[0264] Examples of the polyol compound include aliphatic polyols, alicyclic polyols, polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, polybutadiene polyols, polyisoprene polyols, (meth)acrylic polyols, and polysiloxane polyols.

[0265] Examples of the aliphatic polyol include aliphatic alcohols having two hydroxyl groups, such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, dimethylolpropane, neopentyl glycol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-tetramethylene glycol, 1,3-tetramethylene glycol, 2-methyl-1,3-trimethylene glycol, 1,5-pentamethylene glycol, 1,6-hexamethylene glycol, 3-methyl-1,5-pentamethylene glycol, 2,4-diethyl-1,5-pentamethylene glycol, pentaerythritol diacrylate, 1,9-nonanediol, and 2-methyl-1,8-octanediol; sugar alcohols, such as xylitol and sorbitol; and aliphatic alcohols having three or more hydroxyl groups, such as glycerol, trimethylolpropane, and trimethylolethane.

[0266] Examples of the alicyclic polyol include cyclohexanediols such as 1,4-cyclohexanediol and cyclohexyl dimethanol; hydrogenated bisphenols such as hydrogenated bisphenol A; and tricyclodecanedimethanol.

[0267] Examples of the polyether polyol include polyether polyols having an alkylene structure such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polybutylene glycol, polypentamethylene glycol, and polyhexamethylene glycol, and random or block copolymers of these polyalkylene glycols.

[0268] Examples of the polyester polyol include polycondensates of a polyol and a polycarboxylic acid; ring-opening polymers of cyclic esters (lactones); and reaction products of three components of a polyol, a polycarboxylic acid, and a cyclic ester.

[0269] Examples of the polyol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene glycol, 1,3-tetramethylene glycol, 2-methyl-1,3-trimethylene glycol, 1,5-pentamethylene glycol, neopentyl glycol, 1,6-hexamethylene glycol, 3-methyl-1,5-pentamethylene glycol, 2,4-diethyl-1,5-pentamethylene glycol, glycerol, trimethylolpropane, trimethylolethane, cyclohexanediols (such as 1,4-cyclohexanediol), bisphenols (such as bisphenol A), and sugar alcohols (such as xylitol and sorbitol).

[0270] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids such as malonic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 2,6-naphthalene dicarboxylic acid, terephthalic acid, and trimellitic acid.

[0271] Examples of the cyclic ester include propiolactone, β-methyl-δ-valerolactone, and ε-caprolactone.

[0272] Examples of the polycarbonate-based polyol include a reaction product of a polyol and phosgene, and a ring-opening polymer of a cyclic carbonate (such as an alkylene carbonate).

[0273] Examples of the polyol used in the polycarbonate polyol include the polyols exemplified in the description of the polyester polyol, and examples of the alkylene carbonate include ethylene carbonate, trimethylene carbonate, tetramethylene carbonate, and hexamethylene carbonate.

[0274] In addition, the polycarbonate polyol may be any compound as long as it has a carbonate bond in the molecule and a hydroxyl group at the terminal, and may have a carbonate bond and an ester bond.

[0275] Examples of the polyolefin polyol include a homopolymer or copolymer of ethylene, propylene, butene, etc. as a saturated hydrocarbon skeleton and a hydroxyl group at a molecular terminal thereof.

[0276] Examples of the polybutadiene-based polyol include copolymers having butadiene as a hydrocarbon backbone and having hydroxyl groups at the molecular terminals thereof.

[0277] The polybutadiene polyol may be a hydrogenated polybutadiene polyol in which all or part of the ethylenically unsaturated groups contained in the structure are hydrogenated.

[0278] Examples of the polyisoprene-based polyol include copolymers having isoprene as a hydrocarbon backbone and having hydroxyl groups at the molecular terminals thereof.

[0279] The polyisoprene-based polyol may be a hydrogenated polyisoprene polyol in which all or part of the ethylenically unsaturated groups contained in the structure are hydrogenated.

[0280] Examples of the (meth)acrylic polyol include those having at least two hydroxyl groups in the molecule of a polymer or copolymer of (meth)acrylic acid ester, and examples of the (meth)acrylic acid ester include alkyl (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate. In addition, copolymers of (meth)acrylic acid ester and hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate may be used.

[0281] As said polysiloxane polyol, a dimethyl polysiloxane polyol, a methylphenyl polysiloxane polyol, etc. are mentioned, for example.

[0282] The above-mentioned polyol compounds can be used alone or in combination of two or more.

[0283] In the addition reaction of the isocyanate compound and the hydroxyl-containing (meth)acrylate compound, or the addition reaction of the isocyanate compound, the hydroxyl-containing (meth)acrylate compound and the polyol, the reaction is terminated when the residual isocyanate group content of the reaction system becomes 0.5% by mass or less, thereby obtaining (meth)acrylate urethane.

[0284] When the (meth)acrylic acid urethane includes a product obtained by reacting an isocyanate compound, a polyol compound, and a hydroxyl-containing (meth)acrylic acid ester compound, it is preferably a (meth)acrylic acid urethane obtained by reacting an isocyanate compound with a polyol compound to obtain a reaction product having an isocyanate group, or a mixture of the reaction product and an isocyanate compound with a hydroxyl-containing (meth)acrylic acid ester compound. The (meth)acrylic acid urethane obtained by such a reaction may also be a product obtained by reacting an isocyanate compound with a hydroxyl-containing (meth)acrylic acid ester compound, or a mixture of a product obtained by reacting an isocyanate compound with a hydroxyl-containing (meth)acrylic acid ester compound, and a product obtained by reacting an isocyanate compound, a polyol compound, and a hydroxyl-containing (meth)acrylic acid ester compound.

[0285] In the reaction of the isocyanate compound with the hydroxyl-containing (meth)acrylate compound, it is also preferred to use a catalyst to promote the reaction. Examples of the catalyst include: organic metal compounds such as dibutyltin dilaurate, dibutyltin diacetate, trimethyltin hydroxide, tetra-n-butyltin, zinc diacetylacetonate, tri(acetylacetonato)ethyl acetoacetic acid zirconium, and tetraacetylacetonate zirconium; metal salts such as tin octenate, zinc hexanoate, zinc octenate, zinc stearate, 2-ethylhexanoic acid zirconium, cobalt naphthenate, stannous chloride, tin tetrachloride, and potassium acetate; triethylamine, triethylenediamine, benzyldiethylamine, 1,4-diazabicyclo[2, Amine catalysts such as bismuth nitrate, bismuth bromide, bismuth iodide, bismuth sulfide, etc.; organic bismuth compounds such as dibutyl bismuth dilaurate and dioctyl bismuth dilaurate; bismuth catalysts such as bismuth salts of organic acids such as bismuth salts of bismuth 2-ethylhexanoate, bismuth salts of bismuth cycloalkane, bismuth salts of isodecanoate, bismuth salts of bismuth neodecanoate, bismuth salts of bismuth laurate, bismuth salts of bismuth maleate, bismuth salts of bismuth stearate, bismuth salts of bismuth oleate, bismuth salts of bismuth linoleate, bismuth salts of bismuth acetate, bismuth salts of bismuth neodecanoate, bismuth salts of bismuth digallate. Among them, dibutyltin dilaurate and 1,8-diazabicyclo[5,4,0]undecene are suitable as catalysts. These can be used alone or in combination of two or more.

[0286] In addition, in the reaction of the isocyanate compound and the hydroxyl-containing (meth)acrylate compound, an organic solvent having no functional group reactive with an isocyanate group may be used, such as esters such as ethyl acetate and butyl acetate; ketones such as methyl ethyl ketone and methyl isobutyl ketone; aromatic organic solvents such as toluene and xylene. In addition, a polymerization inhibitor may be used as appropriate.

[0287] In addition, (meth)acrylic acid carbamate is a reaction product of a hydroxyl-containing (meth)acrylate compound and an isocyanate compound, or a hydroxyl-containing (meth)acrylate compound, an isocyanate compound, and a polyol compound, and can also be generated by reacting a mixture of a (meth)acrylate having a hydroxyl group and a (meth)acrylate having no hydroxyl group with an isocyanate compound. Alternatively, it can also be generated by reacting a mixture of a (meth)acrylate having a hydroxyl group and a (meth)acrylate having no hydroxyl group, an isocyanate compound, and a polyol compound. At this time, the (meth)acrylate having no hydroxyl group remains as an unreacted product, or it can be directly included in the curable resin composition.

[0288] In the reaction of the isocyanate compound and the hydroxyl group-containing (meth)acrylate compound described above, part or all of the isocyanate compound described above may be a reaction product of the isocyanate compound and the polyol compound.

[0289] The (meth)acryloyl equivalent of (X) (meth)acrylic acid urethane is, for example, preferably 120 g / eq or more and 250 g / eq or less, more preferably 135 g / eq or more and 220 g / eq or less, and further preferably 150 g / eq or more and 200 g / eq or less. If the (meth)acryloyl equivalent of (X) (meth)acrylic acid urethane is within the above range, it becomes easy to adjust the crosslinking point, and a cured resin layer with a moderate crosslinking density can be formed. Thus, high hardness can be imparted to the cured resin layer.

[0290] The content of the (X) urethane (meth)acrylate in the curable resin composition (B') is preferably 50% by mass or more, more preferably 60% by mass or more, based on the total nonvolatile content (total solid content) in the curable resin composition (B').

[0291] When forming the curable resin (B), it is preferred that the above-mentioned (X) (meth)acrylic acid urethane is polymerized alone or in a mixture of two or more to prepare a base polymer. It is preferred that the base polymer is dissolved or dispersed in a solvent or the like described below, and then applied onto the curable resin layer (A) and cured to form the curable resin layer (B).

[0292] (Solvent)

[0293] The curable resin composition (B') can be diluted with a solvent to form a coating liquid. The curable resin composition (B') is preferably applied to the curable resin layer (A) in the form of a liquid coating liquid and dried, and cured to form a cured resin layer (B). The components constituting the curable resin composition (B') can be dissolved in a solvent or dispersed in a solvent.

[0294] As the solvent, an organic solvent is preferred. Examples of the organic solvent include aromatic solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone (MEK), acetone, methyl isobutyl ketone (MIBK), cyclohexanone, and diisobutyl ketone; ether solvents such as diethyl ether, isopropyl ether, tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether (PGM), anisole, and phenethyl ether; ester solvents such as ethyl acetate, butyl acetate, isopropyl acetate, and ethylene glycol diacetate; amide solvents such as dimethylformamide, diethylformamide, dimethylacetamide, and N-methylpyrrolidone; cellosolve solvents such as methyl cellosolve, ethyl cellosolve, and butyl cellosolve; alcohol solvents such as methanol, ethanol, propanol, isopropanol, and butanol; halogen solvents such as dichloromethane and chloroform, and the like. These organic solvents may be used alone or in combination of two or more. Among these organic solvents, it is preferred to use at least one selected from the group consisting of ester solvents, ether solvents, alcohol solvents, and ketone solvents.

[0295] The amount of organic solvent used is not particularly limited, and is appropriately determined in consideration of the coating properties of the prepared curable resin composition, liquid viscosity and surface tension, compatibility of the solid components, etc. The curable resin composition is prepared using the above-mentioned solvent to form a coating liquid having a solid content concentration of preferably 15 to 80% by mass, more preferably 20 to 70% by mass. It should be noted that the "solid content" in the curable resin composition refers to the components excluding the solvent as a volatile component, and includes not only solid components but also semi-solids and viscous liquids.

[0296] ((Y) Compound having a cyclic siloxane skeleton)

[0297] The curable resin composition (B') contains (Y) a compound having a cyclic siloxane skeleton. The compound having a cyclic siloxane skeleton is preferably a compound represented by the following general formula.

[0298]

[0299] In the above formula, R 1 and R 2 Each independently represents a hydrogen atom or a substituent, and n represents an integer of 1 to 50. Examples of the substituent include a hydrocarbon group, an organic group containing a fluorine atom, an organic group containing a (meth)acrylic group, etc. From the viewpoint of scratch resistance, n is preferably an integer of 1 to 30, and more preferably an integer of 2 to 20.

[0300] Examples of the hydrocarbon group include aliphatic hydrocarbon groups (e.g., alkyl, alkenyl, alkynyl, and cycloalkyl), aromatic hydrocarbon groups (e.g., phenyl, naphthyl, anthracenyl, phenanthryl, and biphenyl), and the like. The hydrocarbon group is preferably a linear or branched alkyl or phenyl group having a carbon number of 1 to 18, such as a methyl group, an ethyl group, a propyl group, and an isopropyl group. It should be noted that the hydrocarbon group may further have a substituent, and as a substituent, may have a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom).

[0301] As the organic group containing a fluorine atom, for example, C x F 2x+1 (CH2) p -(wherein x is an integer of 1 to 8, and p is an integer of 2 to 10) represented by a group, C x F 2x+1 C(CF3)2(CH2) p - (wherein x is an integer of 1 to 8, and p is an integer of 2 to 10) or a group having a perfluoroether structure (e.g., a perfluoropolyether substituted alkyl group). Specific examples of organic groups containing fluorine atoms include: CF3C2H4-, C4F9C2H4-, C4F9C3H6-, C8F 17 C2H4-、C8F 17 C3H6-, C3F7C(CF3)2C3H6-, C3F7OC(CF3)FCF2OCF2CF2C3H6-, C3F7OC(CF3)FCF2OC(CF3)FC3H6-, CF3CF2CF2OC(CF3)FCF2OC(CF3)FCONHC3H6-, etc.

[0302] Examples of the organic group containing a (meth)acrylic group include: CH2=CHCOO-, CH2=C(CH3)COO-, CH2=CHCOOC3H6-, CH2=C(CH3)COOC3H6-, CH2=CHCOOC2H4O-, CH2=C(CH3)COOC2H4O-, etc. When an organic group containing a (meth)acrylic group is provided as a substituent, it is more preferred that the bond to the Si atom is a Si-OC bond from the viewpoint of ease of industrial synthesis.

[0303] Among them, the compound (Y) having a cyclic siloxane skeleton preferably contains an organic group containing at least one fluorine atom, and more preferably contains a group having a perfluoroether structure. That is, the compound (Y) having a cyclic siloxane skeleton is preferably a fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure. By having the above structure, the sliding property of the cured resin layer can be further improved, and the water drop contact angle of the cured resin layer can be increased, so that high scratch resistance can be exerted.

[0304] Specifically, the compound (Y) having a cyclic siloxane skeleton is preferably a fluorine compound represented by the following formula.

[0305]

[0306] In the above formula, R is a hydrogen atom, a methyl group, an ethyl group, a propyl group or a phenyl group, Rf is an organic group containing a fluorine atom, Rx is an organic group containing a (meth)acrylic acid group, and n is n≥2.

[0307] Specific examples of the fluorine-containing organic group and (meth)acrylic group include the above-mentioned specific examples. In addition, n is preferably an integer of 2 to 20, and more preferably an integer of 2 to 10, from the viewpoint of scratch resistance.

[0308] The content of the compound having a cyclic siloxane skeleton in (Y) of the curable resin composition (B') is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, further preferably 0.15 parts by mass or more, particularly preferably 0.2 parts by mass or more, and more preferably 0.3 parts by mass or more. In addition, the content of the compound having a cyclic siloxane skeleton in (Y) of the curable resin composition (B') is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, further preferably 10 parts by mass or less, and particularly preferably 5 parts by mass or less. By setting the content of the compound having a cyclic siloxane skeleton to within the above range, it is easy to take into account the softness, curability and scratch resistance of the cured resin layer (B).

[0309] (Other ingredients)

[0310] The curable resin composition (B′) may contain a photopolymerizable compound such as (meth)acrylate in addition to the above-mentioned (X) urethane (meth)acrylate and (Y) the compound having a cyclic siloxane skeleton.

[0311] In addition, various additives may be appropriately blended into the curable resin composition (B') as required within the scope not impairing the gist of the present invention. As additives, for example, photoinitiators, light stabilizers, antioxidants, antistatic agents, flame retardants, leveling agents, dispersants, thixotropy imparting agents (thickeners), defoaming agents, etc. may be used in combination.

[0312] Here, as the leveling agent, for example, fluorine-based leveling agents, silicone-based leveling agents, acrylic-based leveling agents, etc. Among them, from the viewpoint of imparting good water-repellent and oil-repellent functions to the surface of the cured resin layer (B) and preventing the adhesion of dirt such as fingerprints, the leveling agent is preferably a fluorine-based leveling agent.

[0313] (Photoinitiator (photopolymerization initiator))

[0314] When the curable resin composition (B') is a photocurable resin composition, it is preferred to contain a photoinitiator (photopolymerization initiator) in order to improve curability. The photoinitiator is a photopolymerization initiator, and a known one can be used. Examples of the photopolymerization initiator include a photoradical generator, a photoacid generator, and the like.

[0315] Examples of the photoradical generator that can be used in the photopolymerization initiator of the curable resin composition (B') include benzoin and its alkyl ethers such as benzoin, benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether; acetophenone, 2,2-dimethoxy-2-phenylacetophenone [for example, trade name "Omnirad (registered trademark) 651", manufactured by IGM RESINS], 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexyl phenyl ketone [for example, trade name "Omnirad (registered trademark) 184", manufactured by IGM RESINS], 2-hydroxy-2-methyl-1-phenylpropane-1-one [for example, trade name "Omnirad (registered trademark) 1173", manufactured by IGM RESINS], RESINS], 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropane-1-one [for example, trade name "Omnirad (registered trademark) 127, manufactured by IGM RESINS"], 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propane-1-one [for example, trade name "Omnirad (registered trademark) 2959, manufactured by IGM RESINS], 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one [for example, trade name "Omnirad (registered trademark) 907, manufactured by IGM RESINS], 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone and other alkyl phenones; 2,4,6-trimethylbenzoyldiphenylphosphine oxide [for example, trade name "Omnirad (registered trademark) TPO", IGM RESINS], bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide [for example, trade name "Omnirad (registered trademark) 819", IGM RESINS] and other phosphine oxides; anthraquinones such as 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-pentylanthraquinone; benzophenone and its various derivatives; formic acid derivatives such as methyl benzoylformate and ethyl benzoylformate, etc. These can be used alone or in combination of two or more.

[0316] Among these photoradical generating agents, from the viewpoint of light resistance of the cured product, alkylphenones, phosphine oxides, and formic acid derivatives are preferred; 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and methyl benzoylformate are more preferred; 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropane-1-one are particularly preferred.

[0317] As the photoacid generator, known ones can be used, among which diaryliodonium salts and triarylsulfonium salts are preferred from the viewpoints of curability, acid generation efficiency, etc. Specific examples include anionic salts of di(alkyl-substituted)phenyliodonium (specifically, PF6 salt, SbF5 salt, tetrakis(perfluorophenyl)borate, etc.).

[0318] As a specific example of the anion salt of (alkyl-substituted)phenyliodonium, PF6 salt of dialkylphenyliodonium [trade name "Omniad (registered trademark) 250", manufactured by IGM RESINS] is particularly preferred. These photoacid generators may be used alone or in combination of two or more.

[0319] From the viewpoint of improving curability, the content of the photoinitiator is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and particularly preferably 1 parts by mass or more, relative to 100 parts by mass of the (X) (meth) urethane acrylate in the curable resin composition (B'). On the other hand, from the viewpoint of maintaining the stability of the coating solution when the curable resin composition (B') is made into a solution and the viewpoint of the planarity of the cured coating film, the content of the photoinitiator is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, further preferably 7 parts by mass or less, and particularly preferably 5 parts by mass or less.

[0320] (Viscosity of Curable Resin Composition)

[0321] Regarding the curable resin composition (A') and the curable resin composition (B') used to form the cured resin layer (A) and the cured resin layer (B), in order to improve the coating property, the viscosity at 25°C measured by an E-type viscometer is preferably 60 mPa·s or less, more preferably 30 mPa·s or less, further preferably 20 mPa·s or less, more preferably 15 mPa·s or less, and particularly preferably 12 mPa·s or less. It should be noted that the viscosity of the curable resin composition is preferably 10 mPa·s or more.

[0322] <<Method for producing laminated film>>

[0323] The cured resin layer (A) and the cured resin layer (B) (hereinafter, both are collectively referred to as "cured resin layer") can be formed by curing a curable resin composition, i.e., a composition having curable properties. For example, the cured resin layer is formed by coating a curable resin composition on a substrate film and curing it.

[0324] More specifically, the present laminated film can be produced by coating a curable resin composition (A') on at least one side of a substrate film and curing it to form a cured resin layer (A), and then coating a curable resin composition (B') thereon and curing it to form a cured resin layer (B). In this case, the curing of the cured resin layer (A) and the cured resin layer (B) can also be performed simultaneously.

[0325] In addition, after forming the cured resin layer (A), the film may be temporarily wound into a roll, the film may be unwound again, and a curable resin composition (B') may be applied to the cured resin layer (A) and cured to form a cured resin layer (B). In addition, after forming the cured resin layer (A) on the surface of the substrate film, a curable resin composition (B') may be continuously applied and cured to form a cured resin layer (B). It should be noted that the method for manufacturing the laminated film is not limited in any way by the above method.

[0326] As a method for applying the curable resin composition, for example, conventionally known coating methods such as air knife coating, knife coating, rod coating, bar coating, blade coating, extrusion coating, dip coating, reverse roll coating, transfer roll coating, gravure coating, lick roll coating, cast coating, spray coating, curtain coating, calender coating, and extrusion coating can be used.

[0327] The drying conditions are not particularly limited, and the drying can be carried out at about room temperature or by heating, for example, at about 25 to 120° C., preferably 50 to 100° C., and more preferably 60 to 90° C. In addition, the drying time is not particularly limited as long as the solvent can be fully volatilized, for example, about 10 seconds to 30 minutes, preferably about 15 seconds to 10 minutes.

[0328] The curing method of the curable resin composition may be appropriately selected according to the curing mechanism of the curable resin composition. If the curable resin composition is a thermosetting resin composition, it may be cured by heating. If it is a photocurable resin composition, it may be cured by irradiating with energy rays.

[0329] In the laminated film of the present invention, active energy rays that can be used to cure the photocurable resin composition include ultraviolet rays, electron beams, X-rays, infrared rays, and visible rays. Among these active energy rays, ultraviolet rays and electron beams are preferred from the viewpoint of curability and prevention of resin degradation.

[0330] Regarding the curing method of the curable resin composition, it is preferred to cure by irradiation with energy rays from the viewpoints of molding time and productivity, and from the viewpoint of preventing thermal shrinkage and thermal degradation of each component caused by heating. Irradiation with energy rays can be performed from any side, from the substrate film side, or from the opposite side of the substrate film.

[0331] When the laminated film of the present invention is manufactured, when the curable resin composition is cured by ultraviolet irradiation, various ultraviolet irradiation devices can be used. As the light source, a xenon lamp, a high-pressure mercury lamp, a metal halide lamp, an LED-UV lamp, etc. can be used. The irradiation amount of ultraviolet rays (unit: mJ / cm 2 ) is preferably 50 to 3,000 mJ / cm 2 From the viewpoint of the curability of the curable resin composition and the flexibility of the cured product (cured film), 100 to 1,000 mJ / cm 2 From the viewpoint of the planarity of the laminated film, 100 to 500 mJ / cm 2 In addition, the irradiation amount of ultraviolet rays is appropriately determined according to the reaction rate of the (meth)acryloyl group required in each curing step.

[0332] In particular, when the laminated film is used under a severe environment, it is preferred to increase the amount of ultraviolet irradiation to adjust the surface hardness of the cured product of the curable resin composition.

[0333] In addition, when manufacturing the laminated film of the present invention, various electron beam irradiation devices can be used when the curable resin composition is cured by electron beam irradiation. The irradiation amount (Mrad) of the electron beam is preferably 0.5 to 20 Mrad, and is more preferably 1 to 15 Mrad from the viewpoints of the curability of the curable resin composition, the flexibility of the cured product, and preventing damage to the substrate. It should be noted that the irradiation amount of the electron beam is appropriately determined according to the reaction rate of the (meth)acryloyl group required in each curing step.

[0334] <<Physical properties of laminated films>>

[0335] (Steel wool resistance (SW resistance))

[0336] Since the present laminate film has the above-mentioned structure, it has excellent scratch resistance. Specifically, the scratch resistance can be evaluated by a steel wool resistance (SW resistance) test. For the surface hardness of the present laminate film, specifically the SW resistance of the surface of the cured resin layer (B), when the rate of change of the haze after 2000 reciprocating times of the steel wool is small, it can be evaluated as having excellent scratch resistance. It should be noted that the steel wool resistance (SW resistance) test is implemented by the following method. First, a friction tester (RT-300 manufactured by Daiei Kagaku Seiki Mfg. Co., Ltd.) and steel wool #0000 (trade name: BONSTAR, manufactured by NIPPON STEELWOOL CO., LTD.) are used, and the sides are 2 cm square (area 4 cm 2 ) A load of 1 kg is applied to the outermost surface of the cured resin layer (B), and the cured resin layer (B) is rubbed back and forth 2000 times at a speed of 50 mm / sec, and the presence or absence of scratches on the surface of the cured resin layer (B) is visually confirmed. At this time, the haze value of the laminated film before and after rubbing is measured. The change rate of the film haze after 2000 reciprocations compared to the initial film haze (film haze before rubbing) is calculated. When the change rate is less than 1%, it is evaluated as excellent scratch resistance.

[0337] Change rate (%) = (film haze after friction - initial film haze) / initial film haze × 100

[0338] (Water drop contact angle)

[0339] The water droplet contact angle on the cured resin layer side of the laminated film is preferably 100° or more, more preferably 105° or more, and even more preferably 110° or more.

[0340] In addition, using a friction tester (manufactured by Daiei Kagaku Seiki Mfg. Co., Ltd., RT-300) and using #0000 steel wool (trade name: BONSTAR, manufactured by NIPPON STEEL WOOL CO., LTD.), a load of 1 kg is applied to the outermost surface of the cured resin layer (B) in a 2 cm square and the layer is rubbed back and forth 1000 times at a speed of 50 mm / sec. The water droplet contact angle is preferably 90° or more, more preferably 95° or more, and even more preferably 100° or more. Furthermore, using a friction tester (manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd., RT-300) and using #0000 steel wool (trade name: BONSTAR, NIPPON STEEL WOOL CO., LTD.), a load of 1 kg is applied to the outermost surface of the cured resin layer (B) with a 2 cm square, and after rubbing back and forth 2000 times at a speed of 50 mm / sec, the water drop contact angle is preferably 70° or more, more preferably 75° or more, and further preferably 80° or more. The water drop contact angle after 1000 or 2000 reciprocating rubbings is within the above range, indicating that the water repellency above the prescribed value is maintained even after reciprocating rubbing, indicating that the steel wool resistance (SW resistance) of the cured resin layer is good. It should be noted that the water drop contact angle on the cured resin layer side of the laminated film is the value of the contact angle measured after 60 seconds of dripping water drops on the outermost surface (cured resin layer) of the laminated film using an automatic contact angle meter.

[0341] (Repeated bending)

[0342] Since the laminated film has the above-mentioned structure, it has excellent repeated bending properties (bending resistance). By providing a cured resin layer (A) and a cured resin layer (B) on the surface of the substrate film, and designing the structure of the cured resin layer (B) to a specific range, the substrate film can exert repeated bending properties in actual use. The repeated bending properties (bending resistance) can be evaluated specifically by the following method. The repeated bending test uses a bending tester (manufactured by YUASA SYSTEM Machine Co., Ltd., DLDMLH-FS), and the test is carried out with a minimum radius R = 1.5 in a manner such that the cured resin layer side of the laminated film becomes the inner surface. Then, visually confirm whether cracks occur in the cured resin layer on the inner surface, and measure the number of repeated bendings until cracks occur. At this time, if cracks do not occur even if the film is bent more than 200,000 times, it is evaluated that the repeated bending properties (bending resistance) are good.

[0343] (Total light transmittance)

[0344] When the laminated film is assumed to be used for optical purposes, the total light transmittance is preferably 85% or more, more preferably 86% or more, and particularly preferably 88% or more. It should be noted that the total light transmittance of the laminated film is measured using a haze meter. The details of the measurement method are based on the method described in the examples.

[0345] (Film haze)

[0346] When the laminated film is used for optical applications, the haze of the film is preferably 1.0% or less, and more preferably 0.8% or less. The haze of the laminated film is measured using a haze meter. The details of the measurement method are based on the method described in the Examples.

[0347] (Interference fringes)

[0348] Since the present laminated film has the above-mentioned structure, the generation of interference fringes is suppressed. Interference fringes can be evaluated by the fluctuation range of the light reflectance of 500 to 600 nm. The fluctuation range of the light reflectance of 500 to 600 nm is preferably less than 1.1%, more preferably less than 1.0%, and particularly preferably less than 0.6%. By setting the fluctuation range of the light reflectance of 500 to 600 nm to the above-mentioned range, a film in which interference fringes are difficult to see can be obtained. It should be noted that the fluctuation range of the light reflectance of 500 to 600 nm is the fluctuation range of the reflectance of light with a wavelength of 500 to 600 nm in the reflection simulation.

[0349] <<Features and uses of laminated films>>

[0350] As described above, the present laminated film is a laminated film that is excellent in repeated bending characteristics and abrasion resistance in practical use, and interference fringes are difficult to see. The present laminated film combines surface hardness (SW resistance, for example, reciprocating more than 2,000 times) and repeated bending (bending durability, inward folding, bending 200,000 times under the condition of R = 1.5) at a high level. It is speculated that these effects are derived from the following aspects, that is, by adjusting the composition of the cured resin layer (B), the stress propagation into the cured resin layer (B) applied when the present laminated film is bent can be reduced.

[0351] Furthermore, when the cured resin layer (B) described above is used, it is not necessary to extremely increase the tensile modulus of elasticity of the base film used.

[0352] In the past, for laminated films with a surface layer having a high surface hardness, when designing the target surface hardness to the required level (SW resistance, such as more than 2000 reciprocating times), the structural design of the raw materials constituting the substrate film used must be reconsidered as needed to further increase the tensile elastic modulus.

[0353] In contrast, if the above-mentioned cured resin layer (B) is used, a general base film circulated in the market can be appropriately selected, which has the advantage of increased freedom in base film selection. In addition, in the present embodiment, other layers can also be provided between the cured resin layer (A) and the cured resin layer (B).

[0354] The laminated film has excellent scratch resistance and repeated bending performance in practical use, and can also obtain abrasion resistance and transparency, so it can be preferably used for the following purposes: surface protection, display, especially front panel, etc. For example, it can be suitably used as a surface protection film, a surface protection film for a display, and a surface protection film for a flexible display. However, the use of the laminated film is not limited to these uses.

[0355] [Second embodiment]

[0356] The laminated film of the present invention according to the second embodiment is a laminated film having a structure in which a cured resin layer (C), a cured resin layer (A), and a cured resin layer (B) are sequentially laminated on at least one surface of a base film.

[0357] It should be noted that the present laminated film may include other layers as long as it has the above-mentioned configuration.

[0358] <Base film>

[0359] The base film is the same as that described in the first embodiment.

[0360] <Cured resin layers (C), (A) and (B)>

[0361] The present laminated film has a laminated structure in which a cured resin layer (C) is provided on at least one surface of a base film, and a cured resin layer (A) and a cured resin layer (B) are further provided on the surface side thereof.

[0362] <Curable resin composition>

[0363] The curable resin composition (C'), the curable resin composition (A'), and the curable resin composition (B') for forming the cured resin layer (C), the cured resin layer (A), and the cured resin layer (B) are described below.

[0364] [Curable resin composition (C')]

[0365] The cured resin layer (C) is formed from a curable resin composition (C'). The curable resin composition (C') is characterized in that it contains an antistatic agent. The antistatic agent is not particularly limited as long as it has antistatic properties, but preferably contains the following compound (Ca). As the curable resin composition (C'), it is further preferably formed from a resin composition containing (Cb) and (Cc) on the basis of the following compound (Ca).

[0366] (Ca) A polymer containing a compound of thiophene and / or a thiophene derivative doped with an anionic compound

[0367] (Cb) (meth)acrylic polymer having a styrene structure

[0368] (Cc) one or more compounds selected from (C-c1) polyglycerol and (C-c2) alkylene oxide adducts of polyglycerol, or derivatives thereof

[0369] The compound (Ca) is (C-a1) a polymer in which other anionic compounds are doped in a compound containing thiophene or a thiophene derivative, or (C-a2) a polymer in which anionic groups are self-doped in a compound containing thiophene or a thiophene derivative. It is preferable that these substances exhibit excellent conductivity. One or more of the compounds (Ca) may be used.

[0370] As compound (Ca), for example, a compound obtained by polymerizing a compound of the following formula (C-1) or (C-2) in the presence of a polyanion is exemplified. A polymer obtained by polymerizing the following formula (C-1) in the presence of a polyanion and a polymer obtained by polymerizing the following formula (C-2) in the presence of a polyanion may also be used in combination.

[0371]

[0372] In the above formula (C-1), R 1 and R 2 Each independently represents hydrogen or an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, or the like having 1 to 20 carbon atoms.

[0373]

[0374] In the above formula (C-2), n represents an integer of 1-4.

[0375] Examples of the polyanion used in the polymerization include poly(meth)acrylic acid, polymaleic acid, polystyrenesulfonic acid, polyvinylsulfonic acid, etc. As a method for producing the polymer, for example, the method disclosed in Japanese Patent Application Laid-Open No. 7-90060 can be used.

[0376] In the present invention, it is preferable to use a compound of the above formula (2) in which n is 2 and polystyrene sulfonic acid is used as the polyanion.

[0377] Furthermore, when these polyanions are acidic, they may be partially or completely neutralized. The base used for neutralization is preferably ammonia, organic amines, or alkali metal hydroxides.

[0378] The compound (Cb) is a (meth)acrylic polymer having a styrene structure.

[0379] The styrene structure refers to styrene and styrene derivatives, for example, alkyl groups such as methyl and ethyl groups, phenyl groups, etc. may be introduced into styrene as substituents. From the viewpoint of preventing the precipitation of oligomers due to heat treatment, styrene substituted with an alkyl group having less than 4 carbon atoms or styrene without a substituent is preferred, and styrene is more preferred.

[0380] The (meth)acrylic polymer is a polymer having (meth)acrylic acid or an alkyl (meth)acrylate as a constituent unit, and the compound (Cb) is a copolymer of styrene or a styrene derivative and (meth)acrylic acid or an alkyl (meth)acrylate.

[0381] It should be noted that, in the present invention, when the expression "(meth)acrylic acid" is used, it refers to one or both of "acrylic acid" and "methacrylic acid". In addition, similarly, "(meth)acrylate" refers to one or both of "acrylate" and "methacrylate", and "(meth)acryloyl" refers to one or both of "acryloyl" and "methacryloyl".

[0382] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate. In addition, alkyl (meth)acrylates containing a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate may be used.

[0383] These can be used alone or in combination of two or more. Among these, from the viewpoint of preventing the oligomer from being precipitated due to heat treatment, (meth)acrylic acid is preferred, and acrylic acid is more preferred. That is, the acrylic structure of the (meth)acrylic polymer is preferably a (meth)acrylic structure.

[0384] In addition, the (meth)acrylic-based polymer may have a double bond that can be radically polymerized.

[0385] In addition, other polymerizable monomers copolymerizable with the (meth)acrylic polymers having a styrene structure may be combined. Examples of copolymerizable monomers include: dibasic acid ester compounds containing hydroxyl groups such as monobutyl hydroxyfumarate and monobutyl hydroxyitaconate; various nitrogen-containing compounds such as (meth)acrylamide, diacetone acrylamide, N-hydroxymethyl acrylamide or (meth)acrylonitrile; various vinyl esters such as vinyl propionate and vinyl acetate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane; phosphorus-containing vinyl monomers; various halogenated vinyls such as vinyl chloride and vinylidene chloride; various conjugated dienes such as butadiene, etc.

[0386] The ratio of (meth)acrylic acid or (meth)acrylic acid alkyl ester in the (meth)acrylic acid polymer having a styrene structure is based on the total amount of monomers constituting the (meth)acrylic acid polymer having a styrene structure, for example, 3 mol% or more, preferably 5 to 40 mol%, more preferably 10 to 30 mol%, and further preferably 15 to 25 mol%. If the ratio of (meth)acrylic acid or (meth)acrylic acid alkyl ester is 3 mol% or more, the effect of preventing oligomer precipitation due to heat treatment is shown. In addition, if it is below the above-mentioned upper limit, the ratio of the styrene structure increases, and the durability of the antistatic performance can be ensured.

[0387] The ratio of styrene and styrene derivatives in the (meth) acrylic polymer having a styrene structure is, for example, 50 to 97 mol%, preferably 60 to 95 mol%, more preferably 70 to 90 mol%, and further preferably 75 to 85 mol%, based on the total amount of monomers constituting the (meth) acrylic polymer having a styrene structure. If the ratio of styrene and styrene derivatives is above the aforementioned lower limit, the durability of the antistatic performance is ensured, and if it is below the aforementioned upper limit, the effect of preventing oligomers from precipitating from the substrate film (polyester film) due to heat treatment is ensured.

[0388] The mechanism by which the precipitation of oligomer components contained in the polyester film is suppressed is presumed to be as follows. When the polyester film is heated to a temperature above the glass transition point, the oligomer components are precipitated on the surface of the polyester film, but it is presumed that by forming a cured resin layer formed from a resin composition using a (meth) acrylic polymer having a styrene structure on the polyester film, a structure is formed in which aromatic rings contained in styrene are deposited in parallel with the film, thereby preventing the precipitation of the oligomer components.

[0389] Compound (Cc) is one or more compounds selected from (C-c1) polyglycerol and (C-c2) alkylene oxide adducts of polyglycerol, or derivatives thereof. Polyglycerol is a compound represented by the following general formula (C-3).

[0390]

[0391] In the above formula, n is 2 or more. In the present invention, n in the formula is usually in the range of 2-20, preferably 3-15, and more preferably 3-12.

[0392] The alkylene oxide adduct of polyglycerol means a product having a structure in which alkylene oxide is addition-polymerized to the hydroxyl group of polyglycerol represented by the general formula (C-3).

[0393] Here, the structure of the alkylene oxide added to each hydroxyl group of the polyglycerol skeleton may be different. In addition, as long as the alkylene oxide or its derivative is added to at least one hydroxyl group in the molecule, it is not necessary to add the alkylene oxide or its derivative to all hydroxyl groups.

[0394] The preferred alkylene oxide added to the polyglycerol is ethylene oxide or propylene oxide. If the alkylene chain of the alkylene oxide becomes too long, the hydrophobicity becomes stronger, the dispersibility in the coating liquid deteriorates, and the antistatic property and transparency of the cured resin layer tend to deteriorate. Ethylene oxide is particularly preferred.

[0395] The number of addition is preferably in the range of 200 to 2,000, more preferably in the range of 300 to 1,000, and even more preferably in the range of 400 to 900, based on the number average molecular weight of the final compound.

[0396] The above-mentioned polyglycerol or alkylene oxide adduct of polyglycerol may be used alone or in combination of two or more.

[0397] The resin composition (C') of the present invention may contain a crosslinking agent to improve the durability of the cured resin layer (C), especially the durability of the antistatic property.

[0398] As the crosslinking agent, various known crosslinking agents can be used, for example, melamine compounds, epoxy compounds, isocyanate compounds, carbodiimide compounds, oxazoline compounds, silane coupling compounds, etc. can be listed. Among these, from the viewpoint of suppressing the reduction of antistatic property after exposure to air, melamine compounds, epoxy compounds, isocyanate compounds, and carbodiimide compounds are preferred, and from the viewpoint of more effectively suppressing the precipitation of oligomers, melamine compounds are more preferred. Regarding crosslinking agents such as melamine compounds, as described in the first embodiment above, they can also be used in the resin composition (C') in the same manner.

[0399] The resin composition (C') of the present invention may contain various conventionally known polymers such as polyester resins, acrylic resins, urethane resins, etc. as a binder to improve the coating appearance and transparency of the cured resin layer (C).

[0400] Furthermore, within the scope not impairing the gist of the present invention, particles may be used in combination with the resin composition (C') of the present invention to improve the adhesion, sliding properties, etc. of the cured resin layer (C).

[0401] The proportion of the compound (Ca) in the total non-volatile components in the resin composition (C') of the present invention is usually 2 to 30% by mass, more preferably 3 to 15% by mass, and further preferably 5 to 12% by mass. If the ratio of the compound (Ca) is below the aforementioned upper limit, the strength and transparency of the cured resin layer are good. On the other hand, if the ratio of the compound (Ca) is above the lower limit, sufficient antistatic performance can be obtained, and the antistatic property after exposure to air will not decrease.

[0402] The proportion of the compound (Cb) in the total nonvolatile components in the resin composition (C') of the present invention is usually in the range of 5 to 80% by mass, preferably 10 to 50% by mass, and more preferably 15 to 40% by mass.

[0403] If the ratio of the compound (Cb) is below the above upper limit, the ratio of other components becomes high, so sufficient antistatic properties can be obtained, and the coating appearance becomes good. On the other hand, if the ratio of the compound (Cb) is above the above lower limit, oligomer precipitation can be sufficiently suppressed, sufficient film-forming properties can be ensured, and a uniform coating can be obtained.

[0404] The proportion of the total non-volatile components of the compound (Cc) in the resin composition A of the present invention is usually 10 to 85% by mass, preferably 40 to 70% by mass, and more preferably 45 to 65% by mass. If the ratio of the compound (Cc) is below the aforementioned upper limit, the ratio of other components becomes high, so antistatic properties and film-forming properties become sufficient. On the other hand, if the ratio of the compound (Cc) is above the aforementioned lower limit, the transparency of the cured resin layer becomes good.

[0405] When a crosslinking agent is used in combination with the resin composition (C') of the present invention, the proportion of the crosslinking agent in the total non-volatile components in the resin composition (C') is usually 30% by mass or less, preferably 1 to 25% by mass, and more preferably in the range of 3 to 20% by mass. By using the crosslinking agent within this range, sufficient antistatic performance can be obtained, and the deterioration of antistatic properties after exposure to air can be suppressed, and the strength of the cured resin layer (C) can be improved.

[0406] (Thickness of Cured Resin Layer (C))

[0407] The thickness of the cured resin layer (C) is preferably 0.002 μm to 1.0 μm, more preferably 0.005 μm to 0.25 μm, and further preferably 0.02 μm to 0.10 μm. If the thickness of the cured resin layer is within the above range, precipitation of oligomer components can be suppressed and good antistatic properties can be imparted.

[0408] It is to be noted that it is presumed that unreacted products of various compounds of the resin composition (C′), reacted compounds, or a mixture thereof are present in the cured resin layer (C).

[0409] [Curable resin composition (A')]

[0410] The cured resin layer (A) is formed from a curable resin composition (A'). The curable resin composition (A') is as described in the first embodiment.

[0411] ((Ac) particles)

[0412] The curable resin composition (A') preferably contains (Ac) particles. The particles preferably contain metal oxides from the viewpoint of imparting a high refractive index to the cured resin layer (A). By increasing the refractive index, interference fringes can be suppressed.

[0413] (Metal Oxide)

[0414] As the metal oxide, it is preferred to use a metal oxide with a high refractive index, preferably a metal oxide with a refractive index of 1.7 or more at 550nm. As a specific example of the metal oxide, for example, zirconium oxide, aluminum oxide, titanium oxide, tin oxide, yttrium oxide, antimony oxide, indium oxide, zinc oxide, antimony tin oxide, indium tin oxide, etc. can be listed, and these can be used alone or in combination. Among these, zirconium oxide and titanium oxide are more suitable, and zirconium oxide is more suitable from the viewpoint of weather resistance.

[0415] There is the worry that the adhesion of metal oxide is reduced according to the use form, and it is preferably used in a particle state. In addition, its average particle size is preferably below 100nm, more preferably below 50nm, and further preferably below 25nm from the viewpoint of transparency. In addition, for the lower limit of average particle size, there is no particular limitation, and from the viewpoint of dispersibility, it is preferably more than 5nm, and further preferably more than 10nm.

[0416] In addition, the curable resin composition (A') may also contain particles other than the above-mentioned metal oxides to improve the fixation and sliding properties of the cured resin layer (A). From the perspective of the transparency of the laminated film, the average particle size of the particles other than the metal oxides is preferably 1.0 μm or less, more preferably 0.5 μm or less, and particularly preferably 0.2 μm or less. In addition, there is no particular limitation on the lower limit of the average particle size, but from the perspective of dispersibility, it is preferably 20 nm or more, and more preferably 40 nm or more.

[0417] Specific examples of particles other than the above-mentioned metal oxides include silica, kaolin, calcium carbonate, zirconium oxide, organic particles, and the like. Among these, silica is preferably used from the viewpoint of sliding properties.

[0418] In addition, from the viewpoint of imparting lubricity, it is preferred to use two kinds of particles having different particle sizes as the particles, and it is more preferred to use a combination of metal oxides having different particle sizes and particles other than metal oxides.

[0419] The average particle size is a value measured by, for example, laser diffraction / scattering, dynamic light scattering (DLS), centrifugal sedimentation, particle tracking analysis (PTA), scanning electron microscopy (SEM), etc. If it is a commercial product, the catalog value can be used.

[0420] The ratio of the particles (Ac) to the total non-volatile components in the curable resin composition (A') forming the cured resin layer (A) is usually 5 to 80% by mass, preferably 10 to 80% by mass, more preferably 20 to 80% by mass, and particularly preferably 40 to 80% by mass. By satisfying the above range, both film transparency and low interference effect can be achieved.

[0421] In particular, a more excellent low interference effect can be obtained by combining particles of a metal compound or the like with the polycyclic polyester resin.

[0422] The content of the binder resin (Aa) in the curable resin composition (A') is usually 1 to 60% by mass, preferably 3 to 40% by mass, and more preferably 5 to 30% by mass. When the content is within the above range, good film-forming properties can be ensured.

[0423] The content of the crosslinking agent (Ab) in the curable resin composition (A') is usually 2 to 80% by mass, preferably 2 to 60% by mass, and more preferably 2 to 40% by mass. When the content is within the above range, the adhesion with the cured resin layer (B) becomes good.

[0424] The content of acrylic resin in the curable resin composition (A') is preferably 80% by mass or less, more preferably 5 to 70% by mass, and in particular 10 to 50% by mass. By satisfying the above range, it becomes easy to adjust the refractive index of the cured resin layer (A) itself, and it becomes easy to reduce the interference unevenness after the formation of the cured resin layer (B). It should be noted that the proportion of acrylic resin can be obtained, for example, by dissolving and extracting the coating layer using an appropriate solvent or warm water, separating using chromatography, analyzing the structure using NMR and IR, and then analyzing using thermal decomposition GC-MS (gas chromatography mass spectrometry), optical analysis, etc.

[0425] [Curable resin composition (B')]

[0426] The cured resin layer (B) is formed of a curable resin composition (B'). The curable resin composition (B') contains (X) urethane (meth)acrylate and a fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure.

[0427] The mass average molecular weight of the curable resin composition (B') is preferably 100 or more, more preferably 200 or more, more preferably 400 or more. On the other hand, the upper limit is preferably 500,000 or less, more preferably 400,000 or less, more preferably 250,000 or less.

[0428] It should be noted that in the present invention, when the expression "(meth)acrylic acid" is used, it refers to one or both of "acrylic acid" and "methacrylic acid". The same applies to "(meth)acrylate" and "(meth)acryloyl". In addition, "(poly)propylene glycol" refers to one or both of "propylene glycol" and "polypropylene glycol". "(Poly)ethylene glycol" also has the same meaning.

[0429] (X) urethane (meth)acrylate in the curable resin composition (B′) is the same as described in the first embodiment.

[0430] (Fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure)

[0431] The curable resin composition (B') forming the cured resin layer (B) contains a fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure. Examples of the fluorine compound include fluorine compounds represented by the following general formula (4).

[0432]

[0433] In formula (4), R 3 and R 4Each is independently an organic group having 1 to 12 carbon atoms which may have a substituent; and m is an integer of 3 to 10.

[0434] In the formula (4), m is preferably an integer of 3 to 6, and particularly preferably 3 or 4, from the viewpoint of scratch resistance.

[0435] As R 3 , R 4 The organic groups in the group include: chain alkyl groups such as methyl, ethyl, n-propyl, isopropyl, butyl, isobutyl, sec-butyl, and tert-butyl; alkoxy groups such as methoxy and ethoxy; cyclic alkyl groups such as cyclohexyl and norbornene; alkenyl groups such as vinyl, 1-propenyl, allyl, butenyl, and 1,3-butadienyl; alkynyl groups such as ethynyl, propynyl, and butynyl; halogenated alkyl groups such as trifluoromethyl; alkyl groups having a saturated heterocyclic group such as 3-pyrrolidinylpropyl; aryl groups such as phenyl which may optionally have an alkyl substituent; aralkyl groups such as phenylmethyl and phenylethyl; and the like.

[0436] In addition, R 3 , R 4 The organic group in may have an oxygen atom between carbon atoms and may have an amide bond between carbon atoms. 3 , R 4 The organic group in may be a perfluorinated organic group in which all hydrogen atoms bonded to the carbon atoms are substituted by fluorine atoms.

[0437] When water repellency is imparted to the coating layer, R 3 , R 4 At least a part of the alkylene group is preferably a perfluoroorganic group optionally having an oxygen atom between carbon atoms, and more preferably a perfluoroalkylene group optionally having an oxygen atom between carbon atoms.

[0438] As R 3 , R 4 The substituent that the organic group in may have includes a hydroxyl group, a halogen atom (for example, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom), a (meth)acryloyl group, etc. Among them, a hydroxyl group, a halogen atom, and a (meth)acryloyl group are preferred.

[0439] In addition, the fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure is preferably a compound having a perfluoroether structure at the end, that is, preferably a fluorine compound having a single-terminal structure of the perfluoroether skeleton and bonded to the cyclic siloxane skeleton. By having the aforementioned structure, the sliding property of the cured resin layer can be further improved, and the wiping resistance is excellent.

[0440] The fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure may be a reactive siloxane compound or a non-reactive siloxane compound.

[0441] The reactive siloxane compound is a compound having a reactive functional group and a siloxane bond. Examples of the reactive functional group include an amino group, an epoxy group, a carboxyl group, a carbinol group, a (meth)acrylic group, a mercapto group, and a phenol group.

[0442] The non-reactive siloxane compound is a compound having a siloxane bond but not a reactive functional group, and examples thereof include polyether-modified siloxane compounds, methylstyryl-modified siloxane compounds, alkyl-modified siloxane compounds, higher fatty acid ester-modified siloxane compounds, hydrophilic special modified siloxane compounds, higher alkoxy-modified siloxane compounds, and fluorine-modified siloxane compounds.

[0443] Examples of methods for synthesizing fluorine compounds having a cyclic siloxane skeleton and a perfluoroether structure include: a method of subjecting a siloxane compound having an organic group containing three or more fluorine atoms and three or more Si-H groups to an addition reaction with allyl (meth)acrylate or the like; a method of subjecting a siloxane compound having an organic group containing three or more fluorine atoms and three or more Si-H groups to a dehydrogenation reaction with a (meth)acrylic compound having an OH group such as hydroxyethyl acrylate; and the like.

[0444] Among these methods, the method based on addition reaction is preferred. (Meth)acrylic acid groups may also undergo addition reaction, but since the reaction is carried out while the (meth)acrylic acid groups are maintained using a catalyst such as amine in the dehydrogenation reaction, the target compound can be easily obtained.

[0445] In the cured resin layer (B), i.e., in the curable resin composition (B'), the fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure is preferably mixed in the range of 0.1 to 30 parts by mass, more preferably in the range of 0.15 to 20 parts by mass, further preferably in the range of 0.2 to 10 parts by mass, and particularly preferably in the range of 0.3 to 5 parts by mass, relative to 100 parts by mass of (X) (meth) urethane acrylate. By making the content of the fluorine compound within the above range, curability and abrasion resistance can be particularly well balanced.

[0446] (Solvent)

[0447] The curable resin composition (B') can be made into a coating liquid by diluting with a solvent. The curable resin layer (B) can be made by applying the curable resin composition (B') as a liquid coating liquid on the curable resin layer (A), drying it, and curing it. The components constituting the curable resin composition (B') can be dissolved in a solvent or dispersed in a solvent.

[0448] As the solvent, the same solvent as that used in the curable resin composition (B') in the first embodiment can be used. In addition, the amount of the organic solvent used is also the same as that of the curable resin composition (B') in the first embodiment.

[0449] Furthermore, the other components described in the first embodiment may be added to the curable resin composition (B'). In addition, regarding the photoinitiator, photopolymerization initiator, and photoacid generator, their types and contents may be the same as those of the curable resin composition (B') of the first embodiment.

[0450] Furthermore, the viscosity of the curable resin compositions (A') and (B') is also the same as that of the curable resin compositions (A') and (B') in the first embodiment.

[0451] (particle)

[0452] The curable resin composition (B′) preferably contains fine particles from the viewpoint of improving the surface hardness (scratch resistance) of the cured resin layer (B).

[0453] Examples of the fine particles include inorganic particles such as silicon dioxide, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, alumina, and titanium oxide; and organic particles such as acrylic resins, styrene resins, urea-formaldehyde resins, phenolic resins, epoxy resins, and benzoguanamine resins. Among them, inorganic particles are preferably used, and alumina is particularly preferred from the viewpoint of easy adjustment of abrasion resistance.

[0454] In addition, the average particle size of the above-mentioned microparticles is preferably below 25nm, more preferably below 20nm, and further preferably below 15nm from the viewpoint of transparency. In addition, the lower limit of the average particle size is not particularly limited, and is preferably above 5nm, and further preferably above 10nm from the viewpoint of dispersibility.

[0455] The content of the microparticles in the curable resin composition (B') is preferably 5 to 40% by mass or more, more preferably 10 to 35% by mass or more, and further preferably 15 to 30% by mass or more relative to the total amount (solid content) of the (X) (meth)acrylic urethane and the microparticles. By making the content of the microparticles within the above range, the excellent scratch resistance and antistatic properties of the laminated film can be achieved while satisfying the transparency.

[0456] (Thickness of cured resin layer)

[0457] The thickness of the cured resin layer (B) is the same as that of the cured resin layer (B) in the above-mentioned embodiment 1. In addition, the total thickness of the cured resin layer (A) and the cured resin layer (B) is the same as that in embodiment 1. From the viewpoint of easily adjusting the balance between the excellent scratch resistance and antistatic properties of the laminated film, the thickness of the cured resin layer (C) is preferably 5.0 μm or less.

[0458] The light transmittance at a wavelength of 380 nm on the surface of the cured resin layer (B) is preferably 3.0% or less. If the light transmittance is 3.0% or less, it is advantageous from the viewpoint of preventing the degradation of the bonded counterpart member due to ultraviolet rays. From the above viewpoints, the light transmittance at a wavelength of 380 nm is more preferably 2.8% or less.

[0459] In addition, the maximum reflectivity difference at a wavelength of 500 to 600 nm on the surface of the cured resin layer (B) is preferably 1.5% or less. If the maximum reflectivity difference (variation range of light transmittance) is 1.5% or less, it is advantageous from the viewpoint that interference fringes are difficult to see. From the above viewpoints, the maximum reflectivity difference is more preferably 1.0% or less, further preferably 0.5% or less, and particularly 0.3% or less.

[0460] It should be noted that the maximum reflectivity difference in the present invention refers to the difference between the maximum value and the minimum value of the reflectivity at a wavelength of 500 to 600 nm.

[0461] <Surface conditions of each layer>

[0462] The surface of the cured resin layer (C) and the surface of the cured resin layer (A) may be uneven or flat, but are preferably flat from the viewpoint of appearance (surface gloss).

[0463] In addition, the surface of the cured resin layer (B) may be concavoconvex or flat, preferably flat from the viewpoint of appearance (surface gloss). On the other hand, from the viewpoint of imparting anti-glare properties, it may be concavoconvex. It may be arbitrarily selected according to the required characteristics.

[0464] <<Method for producing laminated film>>

[0465] The cured resin layer (C), the cured resin layer (A) and the cured resin layer (B) can be formed by curing a curable resin composition. That is, the cured resin layer is formed by applying a curable resin composition having a mass average molecular weight in the range of 1,000 to 500,000 on a substrate film and curing the composition.

[0466] More specifically, the present laminated film can be manufactured by coating a curable resin composition (C') on at least one side of a substrate film and curing it to form a cured resin layer (C), then coating a curable resin composition (A') and curing it to form a cured resin layer (A), and then coating a curable resin composition (B') thereon and curing it to form a cured resin layer (B). In this case, the curing of the cured resin layer (C), the cured resin layer (A) and the cured resin layer (B) can be performed separately when each layer is formed, or they can be cured simultaneously after coating multiple layers.

[0467] In addition, after forming the cured resin layer (C) or after forming the cured resin layer (C) and the cured resin layer (A), the film can be temporarily rolled up into a roll, the film can be unwound again, and a curable resin composition (B') can be applied on the cured resin layer (A) and cured to form a cured resin layer (B). In addition, a cured resin layer (C) can be formed on the surface of a substrate film, and after forming a cured resin layer (A) thereon, a curable resin composition (B') can be continuously applied and cured to form a cured resin layer (B). It should be noted that the method for manufacturing a laminated film is not limited by the above method in any way.

[0468] <Method for forming a cured resin layer>

[0469] The same method and conditions as those described in the first embodiment can be used for the method of applying the curable resin composition, the drying conditions, and the curing method.

[0470] <<Physical properties of laminated films>>

[0471] (SW resistance)

[0472] In the present laminated film, the surface hardness of the film, specifically, the SW resistance (#0000 steel wool, load 1 kg) of the surface of the cured resin layer (B) can be set to 2000 times or more.

[0473] (Repeated bending)

[0474] The laminated film having the above-mentioned structure can be provided with a cured resin layer (C), a cured resin layer (A) and a cured resin layer (B) on the surface of the substrate film, and then a cured resin layer (B) containing specific constituents can be prepared, thereby further improving the repeated bending characteristics in actual use. Specifically, the laminated film can obtain a durability that does not generate cracks even when bent more than 200,000 times in the repeated bending evaluation (inward folding, R = 1.5).

[0475] (Total light transmittance)

[0476] When the laminated film is used for optical purposes, the total light transmittance is preferably 85% or more, more preferably 86% or more, and particularly preferably 88% or more. It should be noted that the total light transmittance is measured using a haze meter. The details of the measurement method are based on the method described in the examples.

[0477] (Film haze)

[0478] When the laminated film is used for optical applications, the haze of the film is preferably 1.0% or less, more preferably 0.8% or less, and particularly preferably 0.6% or less. It should be noted that the haze of the film is measured using a haze meter. The details of the measurement method are based on the method described in the Examples.

[0479] (Interference fringes)

[0480] By setting the fluctuation range of the light transmittance at 500 to 600 nm to 1.5% or less, preferably 1.0% or less, and more preferably 0.5% or less, a thin film in which interference fringes are hardly seen can be obtained.

[0481] (Antistatic Properties)

[0482] The surface resistivity of the cured resin layer (B) is not particularly limited, and is, for example, 1×10 12 Ω / □ or less, preferably 1×10 11 Ω / □ or less. The lower limit of the surface resistivity is not particularly limited, but is preferably 1×10 4 Ω / □ or more. The lower the surface resistivity of the cured resin layer (B), the better the antistatic property is. For example, the peeling static electricity in the process of peeling off the functional layer such as the adhesive layer provided on the cured resin layer (B) can be suppressed, thereby preventing the adhesion of foreign matter, etc. The surface resistivity of the cured resin layer (B) can be set within the above range by, for example, containing an antistatic agent in the cured resin layer (C).

[0483] <<Features and uses of laminated films>>

[0484] The laminated film can achieve both high-level surface hardness (SW resistance, for example, reciprocating 2,000 times or more) and repeated bending resistance (bending durability, inward folding, 200,000 times under the condition of R = 1.5). It is speculated that by adjusting the composition of the cured resin layer (B), the propagation of stress applied to the cured resin layer (B) when the laminated film is bent can be reduced.

[0485] Furthermore, by using the above-mentioned cured resin layer (B), it is not necessary to extremely increase the tensile elastic modulus of the base film to be used.

[0486] In the past, for laminated films with a surface layer having a high surface hardness, when designing the target surface hardness to the required level (SW resistance, such as more than 2000 reciprocating times), the structural design of the raw materials constituting the substrate film used must be reconsidered as needed to further increase the tensile elastic modulus.

[0487] On the other hand, when the above-mentioned cured resin layer (B) is configured, a general-purpose base film available on the market can be appropriately selected, which has the advantage of increasing the degree of freedom in selecting the base film.

[0488] The laminated film has excellent scratch resistance and repeated bending properties in practical use, and can also obtain transparency and antistatic properties, so it can be used for the following purposes: surface protection, display, especially front panel, etc. For example, it can be suitably used as a surface protection film, a surface protection film for a display, and a surface protection film for a flexible display. However, the use of the laminated film is not limited to these uses.

[0489] <<Description of statement>>

[0490] In the present invention, the term "film" also includes a "sheet", and the term "sheet" also includes a "film".

[0491] In the present specification, "X to Y" (X and Y are arbitrary numbers) includes "X or more and Y or less" and "preferably greater than X" or "preferably less than Y" unless otherwise specified.

[0492] Furthermore, when “X or more” (X is an arbitrary number), unless otherwise specified, it includes the meaning of “preferably greater than X”, and when “Y or less” (Y is an arbitrary number), unless otherwise specified, it includes the meaning of “preferably less than Y”.

[0493] [Third Embodiment]

[0494] The third embodiment of the laminated film of the present invention is a laminated film having a structure in which a cured resin layer (A) and a cured resin layer (D) are sequentially laminated on at least one side of a substrate film, wherein the cured resin layer (A) is a cured product of a curable resin composition (A') comprising a binder (Aa), a cross-linking agent (Ab) and particles (Ac), and the cured resin layer (D) is a cured product of a curable resin composition (D') comprising a trifunctional or higher-functional (meth)acrylate (Da), a quaternary ammonium salt-containing polymer (Db) and a compound (Dc) having a fluorine atom structure and a cyclic siloxane structure.

[0495] The laminated film of the present invention has the above-mentioned structure and can have both excellent antistatic and antifouling properties, and interference fringes are difficult to see. It can also meet the repeated bending characteristics and wipe resistance required for practical use. In particular, by containing specific compounds, that is, by containing a polymer (Db) containing a quaternary ammonium salt group and a compound (Dc) having a fluorine atom structure and a cyclic siloxane structure in the curable resin composition (D'), it can have both antistatic and antifouling properties and excellent wear resistance.

[0496] The cured resin layer (A) is the same as that described in Embodiment 1. That is, the cured resin layer (A) is a cured product of a curable resin composition (A') containing a binder (Aa), a crosslinker (Ab) and particles (Ac), and the binder (Aa), the crosslinker (Ab) and particles (Ac) are the same as those described in Embodiment 1. The cured resin layer (D) is described below.

[0497] [Curable resin composition (D')]

[0498] The curable resin composition (D') contains a trifunctional or higher-functional (meth)acrylate (Da), a quaternary ammonium salt group-containing polymer (Db), and a compound (Dc) having a fluorine atom-containing structure and a cyclic siloxane structure.

[0499] (Trifunctional or higher (meth)acrylate (Da))

[0500] The trifunctional or higher-functional (meth)acrylate (Da) is not particularly limited as long as it is a compound having three or more (meth)acryloyl groups in one molecule. The trifunctional or higher-functional (meth)acrylate (Da) may be a monomer or an oligomer.

[0501] In the present invention, from the viewpoint of the balance between repeated folding characteristics and scratch resistance and adjustment of the refractive index, urethane (meth)acrylate (Dau) is preferably used.

[0502] Examples of the trifunctional or higher-functional (meth)acrylate (Dam) of the monomer include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tri(meth)acryloyloxyethoxy trimethylolpropane, glycerol Oil polyglycidyl ether poly(meth)acrylate, isocyanuric acid ethylene oxide modified poly(meth)acrylate, ethylene oxide modified dipentaerythritol penta(meth)acrylate, ethylene oxide modified dipentaerythritol hexa(meth)acrylate, ethylene oxide modified pentaerythritol tri(meth)acrylate, ethylene oxide modified pentaerythritol tetra(meth)acrylate, succinic acid modified pentaerythritol poly(meth)acrylate, caprolactone modified pentaerythritol poly(meth)acrylate, etc.

[0503] Examples of the trifunctional or higher-functional (meth)acrylate (Dao) of the oligomer include trifunctional or higher-functional (meth)acrylate urethane (Dau). The trifunctional or higher-functional (meth)acrylate urethane is a compound having three or more (meth)acryloyl groups and one or more urethane bonds.

[0504] Urethane (meth)acrylate is obtained by reacting an isocyanate compound and a hydroxyl-containing (meth)acrylate compound, or by reacting an isocyanate compound, a polyol compound, and a hydroxyl-containing (meth)acrylate compound. Urethane (meth)acrylate can be used alone or in combination of two or more.

[0505] Examples of trifunctional or higher-functional (meth)acrylic urethanes include: (1) a reaction product of a hydroxyl-containing (meth)acrylate compound (D-a1) containing one or more (meth)acryloyl groups and a polyisocyanate compound (D-a2); (2) a reaction product of the aforementioned (D-a1), (D-a2) and a polyol compound (D-a3); (3) a reaction product of a hydroxyl-containing (meth)acrylate compound (D-a4) containing a hydroxyl group and three or more (meth)acryloyl groups and a monoisocyanate compound (D-a5); and the like.

[0506] Among them, from the viewpoints of antifouling properties, abrasion resistance, etc., the trifunctional or higher-functional (meth)acrylic urethane (Dau) is preferably a reaction product of (1) a hydroxyl-containing (meth)acrylate compound (D-a1) and a polyisocyanate compound (D-a2).

[0507] Regarding the hydroxyl-containing (meth)acrylate-based compound (D-a1) containing one or more (meth)acryloyl groups, examples of the hydroxyl-containing (meth)acrylate-based compound containing one (meth)acryloyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate, 2-hydroxyethyl acryloyl phosphate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, dipropylene glycol (meth)acrylate, fatty acid-modified glycidyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate.

[0508] Examples of the hydroxyl group-containing (meth)acrylate compound containing two (meth)acryloyl groups include glycerol di(meth)acrylate, 2-hydroxy-3-acryloyloxypropyl methacrylate, and pentaerythritol di(meth)acrylate.

[0509] The hydroxyl group-containing (meth)acrylate compound (D-a1) containing one or more (meth)acryloyl groups may be used alone or in combination of two or more.

[0510] Examples of the polyisocyanate compound (D-a2) include aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic polyisocyanates such as pentamethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate; alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and norbornene diisocyanate; trimer compounds and polymer compounds of these polyisocyanates; allophanate-type polyisocyanates; biuret-type polyisocyanates; water-dispersible polyisocyanates, and the like.

[0511] Among them, from the viewpoint of stability during the urethanization reaction, diisocyanate compounds are preferred, and more preferred are aliphatic diisocyanates such as pentamethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate; and alicyclic diisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, and 1,3-bis(isocyanatemethyl)cyclohexane.

[0512] From the viewpoint of small cure shrinkage, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, and norbornene diisocyanate are preferred, and from the viewpoint of excellent reactivity and versatility, isophorone diisocyanate is particularly preferred.

[0513] The polyvalent isocyanate compound (D-a2) may be used alone or in combination of two or more.

[0514] The polyol compound (D-a3) is not particularly limited as long as it is a compound containing two or more hydroxyl groups. Examples thereof include aliphatic polyols, alicyclic polyols, polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, polybutadiene polyols, polyisoprene polyols, (meth)acrylic polyols, and the like.

[0515] Examples of the aliphatic polyol include aliphatic alcohols having two hydroxyl groups, such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, dimethylolpropane, neopentyl glycol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-tetramethylene glycol, 1,3-tetramethylene glycol, 2-methyl-1,3-trimethylene glycol, 1,5-pentamethylene glycol, 1,6-hexamethylene glycol, 3-methyl-1,5-pentamethylene glycol, 2,4-diethyl-1,5-pentamethylene glycol, pentaerythritol diacrylate, 1,9-nonanediol, and 2-methyl-1,8-octanediol; sugar alcohols, such as xylitol and sorbitol; and aliphatic alcohols having three or more hydroxyl groups, such as glycerol, trimethylolpropane, and trimethylolethane.

[0516] Examples of the alicyclic polyol include cyclohexanediols such as 1,4-cyclohexanediol and cyclohexyl dimethanol, hydrogenated bisphenols such as hydrogenated bisphenol A, and tricyclodecanedimethanol.

[0517] Examples of the polyether polyol include polyether polyols having an alkylene structure, such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polybutylene glycol, polypentamethylene glycol, and polyhexamethylene glycol; and random copolymers and block copolymers of these polyalkylene glycols.

[0518] Examples of the polyester polyol include polycondensates of a polyol and a polycarboxylic acid; ring-opening polymers of cyclic esters (lactones); and reaction products of three components of a polyol, a polycarboxylic acid, and a cyclic ester.

[0519] Examples of the polyol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene glycol, 1,3-tetramethylene glycol, 2-methyl-1,3-trimethylene glycol, 1,5-pentamethylene glycol, neopentyl glycol, 1,6-hexamethylene glycol, 3-methyl-1,5-pentamethylene glycol, 2,4-diethyl-1,5-pentamethylene glycol, glycerol, trimethylolpropane, trimethylolethane, cyclohexanediols (1,4-cyclohexanediol, etc.), bisphenols (bisphenol A, etc.), sugar alcohols (xylitol, sorbitol, etc.), etc. These may be used alone or in combination of two or more.

[0520] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids such as malonic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 2,6-naphthalene dicarboxylic acid, terephthalic acid, and trimellitic acid. These may be used alone or in combination of two or more.

[0521] Examples of the cyclic ester include propiolactone, β-methyl-δ-valerolactone, and ε-caprolactone.

[0522] Examples of the polycarbonate polyol include a reaction product of a polyol and phosgene, a ring-opening polymer of a cyclic carbonate (alkylene carbonate, etc.), etc. These may be used alone or in combination of two or more.

[0523] The polyol in the polycarbonate polyol can be the same compound as the polyol in the polyester polyol. As the alkylene carbonate, for example, ethylene carbonate, trimethylene carbonate, tetramethylene carbonate, hexamethylene carbonate, etc. can be listed. These can be used alone or in combination of two or more.

[0524] The polycarbonate polyol is not particularly limited as long as it is a compound having a carbonate bond in the molecule and a hydroxyl group at a molecular terminal. The polycarbonate polyol may further have an ester bond in addition to the carbonate bond.

[0525] Examples of the polyolefin polyol include a homopolymer or copolymer of ethylene, propylene, butene, etc. as a saturated hydrocarbon skeleton and a hydroxyl group at the molecular terminal thereof.

[0526] Examples of the polybutadiene polyol include copolymers having butadiene as a hydrocarbon backbone and having hydroxyl groups at molecular terminals. The polybutadiene polyol may be a hydrogenated polybutadiene polyol in which all or part of the ethylenically unsaturated groups contained in the structure are hydrogenated.

[0527] Examples of the polyisoprene polyol include copolymers having isoprene as a hydrocarbon backbone and having hydroxyl groups at the molecular ends thereof. The polyisoprene polyol may be a hydrogenated polyisoprene polyol in which all or part of the ethylenically unsaturated groups contained in the structure are hydrogenated.

[0528] As the (meth)acrylic polyol, for example, there can be mentioned those having at least two hydroxyl groups in the molecule of the polymer or copolymer of (meth)acrylate. As the (meth)acrylate, there can be mentioned hydroxyl-containing (meth)acrylate compounds containing one of the above-mentioned ethylenically unsaturated groups. If necessary, it can also be copolymerized with other comonomers.

[0529] Examples of the comonomer include acrylic acid esters such as alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; and styrene compounds such as styrene and methylstyrene.

[0530] Furthermore, it may be a hydroxyl-containing (meth)acrylic polyol obtained by reacting a (meth)acrylic polymer having a glycidyl group in a side chain with a carboxylic acid such as (meth)acrylic acid, or it may be a hydroxyl-containing (meth)acrylic polyol obtained by reacting a (meth)acrylic polymer having a carboxylic acid in a side chain with a glycidyl group-containing compound.

[0531] Among them, polyester polyols and polyether polyols are preferred. From the viewpoint of the flexibility of the cured product (adhesiveness) and the compatibility with the photopolymerizable compound, polyether polyols are particularly preferred, and polytetramethylene glycol is most preferred. The polyol compound (a3) ​​may be used alone or in combination of two or more.

[0532] The number average molecular weight of the polyol compound (D-a3) is preferably 200 to 3,000, more preferably 250 to 2,000, and further preferably 300 to 1,000. If the number average molecular weight of the polyol compound (D-a3) is too small, there is a tendency that the crosslinking density is excessively increased and the adhesion with the substrate becomes poor. If the number average molecular weight of the polyol compound (D-a3) is too large, there is a tendency that the crystallinity becomes high and the viscosity becomes high.

[0533] The number average molecular weight is the number average molecular weight converted based on the standard polystyrene molecular weight. For example, a high performance liquid chromatograph (manufactured by Waters Japan, "Waters 2695 (main body)" and "Waters 2414 (detector)") with three columns connected in series can be used: Shodex GPC KF-806L (exclusion limit molecular weight: 2×10 7 , Separation range: 100~2×10 7 , theoretical plate number: 10,000 plates / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm) for measurement.

[0534] Examples of the hydroxyl-containing (meth)acrylate compound (D-a4) containing three or more (meth)acryloyl groups include pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, and ethylene oxide-modified dipentaerythritol penta(meth)acrylate.

[0535] Among them, dipentaerythritol penta(meth)acrylate and pentaerythritol tri(meth)acrylate are preferred.

[0536] Examples of the monoisocyanate compound (D-a5) include monoisocyanates such as butane isocyanate, 3-chlorophenyl isocyanate, cyclohexane isocyanate, and 3-isoacryloyl-α,α-dimethylbenzyl isocyanate.

[0537] (Meth)acrylic acid urethane (Dau) can be synthesized according to a known method. For example, the reaction product of a hydroxyl-containing (meth)acrylate compound (D-a1) and a polyisocyanate compound (D-a2) can be synthesized according to the method described in paragraphs

[0036] to

[0042] of Japanese Patent Application Publication No. 2020-152786.

[0538] The weight average molecular weight of the (meth)acrylic acid urethane (Dau) that can be used in the present invention is preferably 1,000 to 60,000, more preferably 1,500 to 50,000, and further preferably 1,800 to 30,000. If the weight average molecular weight is above the lower limit, the curing shrinkage of the cured product during curing will not become too large, and if it is below the upper limit, the viscosity is kept low and the handling is easy.

[0539] The weight average molecular weight is a weight average molecular weight converted based on the standard polystyrene molecular weight. It can be measured by connecting three pillars in series on a high performance liquid chromatograph (manufactured by Waters Japan, "Waters 2695 (main body)" and "Waters 2414 (detector)"): Shodex GPC KF-806L (exclusion limit molecular weight: 2×10 7 , Separation range: 100~2×10 7 , theoretical plate number: 10,000 plates / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm) for measurement.

[0540] The viscosity of (meth) urethane acrylate (Dau) at 60°C is preferably 500 to 100,000 mPa·s, more preferably 800 to 50,000 mPa·s, and further preferably 1,00 to 35,000 mPa·s. When the viscosity is within the above range, workability is good. The viscosity is a value measured by an E-type viscometer.

[0541] The curable resin composition (D') of the present invention may contain a (meth)acrylate compound in addition to the trifunctional or higher-functional (meth)acrylate (Da). Examples of the (meth)acrylate compound include monofunctional (meth)acrylate and its derivatives, bifunctional (meth)acrylate and its derivatives, and the like.

[0542] The content of the (meth)acrylate compounds other than the trifunctional or higher-functional (meth)acrylate (Da) is usually 20 parts by mass or less, preferably 10 parts by mass or less, based on 100 parts by mass of the trifunctional or higher-functional (meth)acrylate (Da).

[0543] Examples of monofunctional (meth)acrylates and derivatives thereof include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-decyl (meth)acrylate, lauryl (meth)acrylate, n-tridecyl (meth)acrylate, stearyl (meth)acrylate, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrofuranyl (meth)acrylate, ethoxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, butoxyethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and cationizing agents thereof. Modified products, diethylaminoethyl (meth)acrylate and modified products based on its cationizing agent, cyanoethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, alkoxypolyalkylene glycol (meth)acrylate such as methoxypolypropylene glycol (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-butoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, (meth)acrylic acid, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloylpropyl phthalate, (meth)acryloyloxyethyl succinate, 2-isocyanateethyl (meth)acrylate, and the like.

[0544] Examples of the bifunctional (meth)acrylate and its derivatives include bifunctional (meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, bifunctional (meth)acrylic urethanes, bifunctional epoxy acrylates, and bifunctional polyester acrylates.

[0545] (Quaternary ammonium salt group-containing polymer (Db))

[0546] The quaternary ammonium salt group-containing polymer (Db) is a polymer having one or more quaternary ammonium salt groups (however, excluding trifunctional or higher-functional (meth)acrylates (Da)).

[0547] Examples of the polymer constituting the main skeleton of the quaternary ammonium group-containing polymer (Db) include quaternary ammonium group-containing acrylic polymers, quaternary ammonium group-containing olefin polymers, quaternary ammonium group-containing ester polymers, quaternary ammonium group-containing cellulose polymers, quaternary ammonium group-containing styrene polymers, and copolymers thereof.

[0548] In the present invention, by containing a polymer (Db) containing a quaternary ammonium salt group, the antistatic property of the laminated film can be efficiently improved, and excellent wear resistance can also be taken into account. Among them, the acrylic polymer containing a quaternary ammonium salt group is excellent in compatibility with (meth) acrylates and the balance of segregation on the surface for expressing antistatic properties, and is preferred from the viewpoint of obtaining antistatic performance at a high level. The polymer (Db) containing a quaternary ammonium salt group can be used alone or in combination of two or more.

[0549] The quaternary ammonium salt group-containing polymer (Db) can be obtained, for example, by copolymerizing a monomer having a quaternary ammonium salt group and an unsaturated group with a compound having another unsaturated group (eg, a monomer or an oligomer).

[0550] Examples of the monomer having a quaternary ammonium salt group and an unsaturated group include (meth)acryloyloxyethyltrimethylammonium chloride, 2-hydroxy-3-(meth)acryloyloxypropyltrimethylammonium chloride, 2-hydroxy-3-(meth)acryloyloxypropyltriethylammonium bromide, 2-hydroxy-3-(meth)acryloyloxypropyltributylammonium chloride, 2-hydroxy-3-(meth)acryloyloxypropylmethylethylbutylammonium chloride, 2-hydroxy-3-(meth)acryloyloxypropyldimethylphenylammonium chloride, and 2-hydroxy-3-(meth)acryloyloxypropyldimethylcyclohexylammonium chloride.

[0551] Examples of compounds having other unsaturated groups include alkyl (meth)acrylates such as cyclohexyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; 2-(meth)acryloyloxyethylsuccinic acid; and 2-(meth)acryloyloxyethylhexahydrophthalic acid.

[0552] The number average molecular weight of the polymer (Db) containing quaternary ammonium salt groups can be obtained, for example, by using a polystyrene standard of a gel permeation chromatograph (GPC). The number average molecular weight of the polymer (Db) containing quaternary ammonium salt groups is generally in the range of 5000 to 500000, preferably 7000 to 300000. If the number average molecular weight of the polymer (Db) containing quaternary ammonium salt groups is above the lower limit of the aforementioned numerical range, no oozing out will occur on the surface of the coating layer. On the other hand, if the number average molecular weight of the polymer (Db) containing quaternary ammonium salt groups is below the upper limit of the aforementioned numerical range, the compatibility in this coating agent composition becomes good.

[0553] The quaternary ammonium salt group-containing polymer (Db) can be produced, for example, by polymerizing a monomer component containing a monomer having a quaternary ammonium salt group and an unsaturated group. The monomer component may further contain a compound having other unsaturated groups, a polymerization initiator, etc. as required.

[0554] (Compound having a fluorine atom-containing structure and a cyclic siloxane structure (Dc))

[0555] The curable resin composition (D') forming the cured resin layer (D) contains a compound having a fluorine atom-containing structure and a cyclic siloxane structure. Examples of the compound include fluorine compounds represented by the following general formula.

[0556]

[0557] In formula (1), R 1 and R 2 Each is independently an organic group having 1 to 12 carbon atoms which may have a substituent; and m is an integer of 3 to 10.

[0558] In the formula (1), m is preferably an integer of 3 to 6, and particularly preferably 3 or 4, from the viewpoint of scratch resistance and abrasion resistance.

[0559] As R 1 , R 2 The organic groups in the group include: chain alkyl groups such as methyl, ethyl, n-propyl, isopropyl, butyl, isobutyl, sec-butyl, and tert-butyl; alkoxy groups such as methoxy and ethoxy; cyclic alkyl groups such as cyclohexyl and norbornene; alkenyl groups such as vinyl, 1-propenyl, allyl, butenyl, and 1,3-butadienyl; alkynyl groups such as ethynyl, propynyl, and butynyl; halogenated alkyl groups such as trifluoromethyl; alkyl groups having a saturated heterocyclic group such as 3-pyrrolidinylpropyl; aryl groups such as phenyl which may optionally have an alkyl substituent; aralkyl groups such as phenylmethyl and phenylethyl, etc.

[0560] In addition, R 1 , R 2The organic group in may optionally have an oxygen atom between carbon atoms, and may also optionally have an amide bond between carbon atoms. 1 , R 2 The organic group in may be a perfluorinated organic group in which all hydrogen atoms bonded to the carbon atoms are substituted with fluorine atoms.

[0561] When water repellency is imparted to the coating layer, R 2 , R 3 At least a part of is preferably a perfluoroorganic group optionally having an oxygen atom between carbon atoms, and more preferably a perfluoroalkylene group optionally having an oxygen atom between carbon atoms.

[0562] As R 1 , R 2 The substituent that the organic group in may have includes a hydroxyl group, a halogen atom (for example, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom), a (meth)acryloyl group, etc. Among them, a hydroxyl group, a halogen atom, and a (meth)acryloyl group are preferred.

[0563] In the present invention, the compound (Dc) having a fluorine-containing atom structure and a cyclic siloxane structure is preferably a fluorine compound having a perfluoroether structure and a cyclic siloxane structure. It is further preferably a compound having a perfluoroether structure at the end. That is, it is preferably a fluorine compound in which the perfluoroether skeleton is a single-terminal structure and is bonded to the cyclic siloxane skeleton. By having the aforementioned structure, the sliding property of the cured resin layer can be further improved, and in addition, the water drop contact angle of the cured resin layer can be increased. That is, due to the excellent water repellency, excellent antifouling property, and practical wiping resistance can also be used on the basis of excellent wear resistance.

[0564] The compound (Dc) may be a reactive siloxane compound or a non-reactive siloxane compound.

[0565] The reactive siloxane compound is a compound having a reactive functional group and a siloxane bond. Examples of the reactive functional group include an amino group, an epoxy group, a carboxyl group, a carbinol group, a (meth)acrylic group, a mercapto group, and a phenol group.

[0566] The non-reactive siloxane compound is a compound having a siloxane bond but not a reactive functional group, and examples thereof include polyether-modified siloxane compounds, methylstyryl-modified siloxane compounds, alkyl-modified siloxane compounds, higher fatty acid ester-modified siloxane compounds, hydrophilic special modified siloxane compounds, higher alkoxy-modified siloxane compounds, and fluorine-modified siloxane compounds.

[0567] Examples of the method for synthesizing the compound (Dc) include a method of subjecting a siloxane compound having an organic group containing 3 or more fluorine atoms and 3 or more Si—H groups to an addition reaction with allyl (meth)acrylate or the like, and a method of subjecting a siloxane compound having an organic group containing 3 or more fluorine atoms and 3 or more Si—H groups to a dehydrogenation reaction with a (meth)acrylic compound having an OH group such as hydroxyethyl acrylate.

[0568] Among these methods, addition reaction is preferred. (Meth)acrylic acid groups may also undergo addition reaction, but since the reaction is carried out while the (meth)acrylic acid groups are maintained using a catalyst such as amine in the dehydrogenation reaction, the target compound can be easily obtained.

[0569] (Composition of Curable Resin Composition (D'))

[0570] The content of the trifunctional or higher (meth)acrylate (Da) is preferably 50 to 99 parts by mass, and more preferably 60 to 97 parts by mass, relative to 100 parts by mass of the solid content of the curable resin composition (D'). If the content of the trifunctional or higher (meth)acrylate (Da) is above the above lower limit, the scratch resistance of the cured resin layer (D) becomes sufficient. On the other hand, if the content of the trifunctional or higher (meth)acrylate (Da) is below the above upper limit, a sufficient concentration of the quaternary ammonium salt-containing polymer (Db) can be obtained, thereby obtaining good antistatic properties.

[0571] The content of the polymer (Db) containing quaternary ammonium salt groups is preferably 0.5 to 30 parts by mass, and more preferably 1 to 20 parts by mass, relative to 100 parts by mass of (meth) acrylate (Da). If the content of the polymer (Db) containing quaternary ammonium salt groups is above the above lower limit, the effect of improving antistatic properties can be obtained by using the polymer containing quaternary ammonium salt groups. On the other hand, if the content of the polymer (Db) containing quaternary ammonium salt groups is below the above upper limit, the transparency of the coating layer becomes good. In addition, if the content of the compound (Dc) is in the range of above the above lower limit and below the upper limit, the wear resistance can also be improved.

[0572] In the cured resin layer (D), that is, in the curable resin composition (D'), the content of the compound (Dc) is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, and particularly preferably 0.1 to 1 part by mass relative to 100 parts by mass of (meth)acrylate (Da). If the content of the compound (Dc) is above the above lower limit, the effect of improving the antifouling property can be fully obtained by using the compound (Dc). On the other hand, if the content of the compound (Dc) is below the above upper limit, the transparency of the coating layer is maintained and sufficient antistatic properties are exhibited. In addition, if the content of the compound (Dc) is in the range of above the above lower limit and below the upper limit, the wear resistance can also be improved.

[0573] (Solvent)

[0574] The curable resin composition (D') can be made into a coating liquid by diluting with a solvent. The curable resin composition (D') can be made into a cured resin layer (A) by applying the curable resin composition (D') as a liquid coating liquid, drying it, and curing it. Each component constituting the curable resin composition (D') can be dissolved in a solvent or dispersed in a solvent.

[0575] As a solvent, the same type and usage amount as those described in the curable resin composition (B') can be used. In addition, other components described in the first embodiment can also be added to the curable resin composition (D'). In addition, the type and content of the photoinitiator, photopolymerization initiator, and photoacid generator can be the same as those of the curable resin composition (B') of the first embodiment.

[0576] Furthermore, the viscosity of the curable resin compositions (A') and (D') is also the same as that of the curable resin compositions (A') and (B') in the first embodiment.

[0577] (Viscosity of Curable Resin Compositions (A') and (D'))

[0578] Regarding the curable resin compositions (A') and (D') used to form the cured resin layer (A) and the cured resin layer (D), in order to improve the coating properties, the viscosity at 25°C measured by an E-type viscometer is preferably 10 to 60 mPa·s, more preferably 30 mPa·s or less, more preferably 20 mPa·s or less, more preferably 15 mPa·s or less, and more preferably 12 mPa·s or less.

[0579] (Thickness of Cured Resin Layer (D))

[0580] The thickness of the cured resin layer (D) is preferably 10.0 μm or less, more preferably 8.0 μm or less, further preferably 6.0 μm or less, and particularly preferably 5.0 μm or less.

[0581] When the thickness of the cured resin layer (D) is at most the above upper limit, in a laminate structure having the cured resin layer (D) such as a laminate film, curling and heat wrinkling can be prevented and good planarity can be secured.

[0582] On the other hand, the lower limit of the thickness of the cured resin layer (D) is not particularly limited, but is preferably 1.0 μm or more from the viewpoint of appropriately protecting the substrate film.

[0583] From the viewpoint of bendability, the total thickness of the cured resin layer (A) and the cured resin layer (D) is preferably 10.0 μm or less, more preferably 8.0 μm or less, particularly 6.0 μm or less, and particularly 5.0 μm or less.

[0584] The light transmittance at a wavelength of 380 nm on the surface of the cured resin layer (D) is preferably 3.0% or less. If the light transmittance is 3.0% or less, it is advantageous from the viewpoint of preventing the degradation of the bonded counterpart member due to ultraviolet rays. From the above viewpoints, the light transmittance at a wavelength of 380 nm is more preferably 2.8% or less.

[0585] In addition, the maximum reflectivity difference at a wavelength of 500 to 600 nm on the surface of the cured resin layer (D) is preferably 1.5% or less. If the maximum reflectivity difference (variation range of light transmittance) is 1.5% or less, it is advantageous from the viewpoint that interference fringes are not easily visible. From the above viewpoints, the maximum reflectivity difference is more preferably 1.0% or less, further preferably 0.5% or less, and particularly 0.3% or less.

[0586] (Surface conditions of each layer)

[0587] The surface of the cured resin layer (A) may be uneven or flat, but is preferably flat from the viewpoint of appearance (surface gloss).

[0588] In addition, the surface of the cured resin layer (D) may be concavoconvex or flat, preferably flat from the viewpoint of appearance (surface gloss). On the other hand, from the viewpoint of imparting anti-glare properties, it may be concavoconvex. It can be arbitrarily selected according to the required characteristics.

[0589] <<Method for producing laminated film>>

[0590] The cured resin layer (A) and the cured resin layer (D) (hereinafter, the two may be collectively referred to as "cured resin layer") can be formed by curing a curable composition, that is, a composition having curable properties (curable resin composition). That is, the cured resin layer is formed by, for example, applying a curable resin composition having a mass average molecular weight in the range of 1,000 to 500,000 on a substrate film and curing it.

[0591] More specifically, the present laminated film can be produced by coating a curable resin composition (A') on at least one side of a substrate film and curing it to form a cured resin layer (A), and then coating a curable resin composition (D') thereon and curing it to form a cured resin layer (D). In this case, the cured resin layer (A) and the cured resin layer (D) can be cured simultaneously.

[0592] In addition, after forming the cured resin layer (A), the film may be temporarily wound into a roll, the film may be unwound again, and the curable resin composition B may be coated on the cured resin layer (A) and cured to form a cured resin layer (D). In addition, after forming the cured resin layer (A) on the surface of the substrate film, the curable resin composition (D') may be continuously coated and cured to form a cured resin layer (D). It should be noted that the method for producing the laminated film is not limited by the method in any way.

[0593] <Method for forming a cured resin layer>

[0594] The method for forming the cured resin layer can be the same as that of the first embodiment. The drying conditions and the curing method can be the same as those of the first embodiment.

[0595] <<Physical properties of laminated films>>

[0596] (SW resistance)

[0597] In the present laminated film, the surface hardness of the film, specifically, the SW resistance of the surface of the cured resin layer (D) can be set to 1000 times or more. Specifically, when measured by the method described in the Examples, the number of reciprocations at which no scratches are visually confirmed and the change in haze of the initial film is less than 1% can be set to 1000 times or more.

[0598] (Repeated bending)

[0599] The laminated film has excellent repeated bending properties (bending resistance). Specifically, the laminated film is tested with a minimum radius R = 1.5 in a manner such that the cured resin layer side of the laminated film becomes the inner surface, and the number of repeated bending times until cracks are generated in the cured resin layer on the inner surface is measured. If no cracks are generated even after bending for more than 200,000 times, it can be evaluated as having good repeated bending properties (bending resistance).

[0600] (Water drop contact angle)

[0601] The water droplet contact angle on the cured resin layer side of the laminated film is preferably 100° or more, more preferably 105° or more, and even more preferably 110° or more.

[0602] In addition, using a friction tester (manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd., RT-300) and using #0000 steel wool (trade name: BONSTAR, manufactured by NIPPON STEEL WOOL CO., LTD.), a load of 1 kg is applied to the outermost surface of the cured resin layer (D) in a 2 cm square, and the surface is reciprocated at a speed of 50 mm / sec for 1000 times. The water drop contact angle is preferably 90° or more, and more preferably 95° or more. The water drop contact angle after reciprocating friction is within the above range, indicating that the water repellency above the prescribed value is maintained even after reciprocating friction, indicating that the cured resin layer has good steel wool resistance (SW resistance).

[0603] And then, an eraser (product number: ER-KM, circular portion diameter 6.7mm, Tombow Pencil company system) is installed in a friction tester (Ohira Rika Industry Co., Ltd. system) with the front end of the eraser extending 1~3mm from the mounting portion and the circular portion uniformly contacting the outermost surface of the cured resin layer (D), a 0.5kg load is applied to the outermost surface of the cured resin layer (D), and after reciprocating 100 times in the zone of 5cm with a speed of 1 reciprocating / second, the water drop contact angle is preferably more than 90 °, more preferably more than 95 °.

[0604] (Total light transmittance)

[0605] When the laminated film is used for optical purposes, the total light transmittance is preferably 85% or more, more preferably 86% or more, and particularly preferably 88% or more. It should be noted that the total light transmittance is measured using a haze meter. The details of the measurement method are based on the method described in the examples.

[0606] (Film haze)

[0607] When the laminated film is used for optical applications, the haze of the film is preferably 1.0% or less, more preferably 0.8% or less, and particularly preferably 0.6% or less. It should be noted that the haze of the film is measured using a haze meter. The details of the measurement method are based on the method described in the Examples.

[0608] (Interference fringes)

[0609] By setting the fluctuation range of the light transmittance at 500 to 600 nm to 1.5% or less, preferably 1.0% or less, and more preferably 0.5% or less, it is possible to obtain a thin film in which interference fringes are less likely to be seen.

[0610] (Antistatic Properties)

[0611] The surface resistivity of the cured resin layer (B) is not particularly limited, and is, for example, 1×10 12 Ω / □ or less, preferably 1×10 11 Ω / □ or less. There is no particular lower limit for the surface resistivity, but if the cost of the antistatic agent is taken into consideration, it is preferably set to 1×10 4 Ω / □ or more. The lower the surface resistivity of the cured resin layer (B), the better the antistatic property is. For example, it is possible to suppress peeling static electricity in the process of peeling off a functional layer such as an adhesive layer provided on the cured resin layer (B), and prevent the adhesion of foreign matter, etc. The surface resistivity of the cured resin layer (B) can be set within the above range, for example, by containing an antistatic agent in the cured resin layer (B).

[0612] (Fluorine atomic concentration)

[0613] The ratio (F2 / F1) of the fluorine atom concentration (F2; atomic %) at the position where Ar etching was performed at an acceleration voltage of 200 eV for 10 seconds measured by X-ray photoelectron spectroscopy (XPS) to the fluorine atom concentration (F1: atomic %) at the outermost surface of the laminated film (the surface on the cured resin layer (B) side) measured by X-ray photoelectron spectroscopy (XPS) is preferably 0.2 or less, more preferably 0.0001 to 0.10, and particularly preferably 0.001 to 0.02.

[0614] If the above ratio (F2 / F1) is small, it means that the fluorine atom occupancy of the fluorine compound (Y) having a cyclic siloxane skeleton on the surface of the laminated film is higher. By segregating the fluorine atoms to the surface of the laminated film and setting (F2 / F1) to a specific range, a laminated film with excellent scratch resistance and abrasion resistance can be made.

[0615] The details of the method for measuring the fluorine atom concentration of the laminated thin film are based on the method described in Examples.

[0616] <<Features and uses of laminated films>>

[0617] The present laminated film has a high level of surface hardness (SW resistance, for example, 2000 or more reciprocating cycles).

[0618] In addition, the laminated film has excellent antistatic and antifouling properties, interference fringes are not easily visible, and the wear resistance is excellent. It also satisfies the repeated bending property in actual use, so it can be used for surface protection, display, and especially for front panels. For example, it can be suitably used as a surface protection film, especially a surface protection film for displays. However, the use of the laminated film is not limited to these uses.

[0619] Example

[0620] Hereinafter, the present invention will be described in further detail using Examples, Comparative Examples, and Reference Examples. However, the present invention is not limited to the following Examples, Comparative Examples, and Reference Examples unless it departs from the gist of the present invention.

[0621] In addition, in an example, "part" and "%" are a mass basis.

[0622] <Evaluation Method>

[0623] The measuring methods and evaluation methods used in the Examples are as follows.

[0624] (1) Method for measuring film thickness of cured resin layer

[0625] Using the "Aron Alpha Series" manufactured by Toagosei Co., Ltd., each laminated film was bonded to a glass slide to prepare a sample for SAICS (SAICAS). The obtained SAICS sample was placed in SAICAS (DN-01 manufactured by DAIPLA WINTESCO., LTD.), and a cut with a width of 300 μm and a depth of 1 μm was first cut using a diamond tip. When cutting the cut, a single crystal diamond knife with a V angle of 80°, a front angle of 5°, and a back angle of 5° was used. During the measurement, a boron nitride cutter with a width of 300 μm was placed on a sample with a pre-cut cut of a width of 300 μm, and the film thickness of each cured resin layer was measured at an arbitrary depth, a horizontal speed of 1 μm / s, and a vertical speed of 0.5 μm / s. During the measurement, a boron nitride knife with a blade width of 0.3 mm, a front angle of 20°, and a back angle of 10° was used. The material strength was measured based on the vertical displacement position and the cutting force to calculate the thickness of each layer.

[0626] (2) Film haze

[0627] The film haze of each laminated film was measured using a haze meter HM-150 manufactured by Murakami Color Research Laboratory in accordance with JIS K 7136: 2000. The evaluation criteria are as follows.

[0628] (Judgment Criteria)

[0629] ○: 1.0% or less

[0630] △: more than 1.0% and less than 1.5%

[0631] ×: 1.5% or more

[0632] (3) Retardation of the substrate film (Re)

[0633] When measuring the retardation (Re) of the substrate film, a "phase difference measuring device (KOBRA-21ADH)" manufactured by Oji Measuring Instruments Co., Ltd. was used. A sample of 3.5 cm × 3.5 cm was cut from the center of the film in the width direction at intervals of 10 cm along the film width direction, and the film width direction was set on the device in such a way that the angle defined in this measuring device became 0°, and the retardation (Re) in the fast axis direction (width direction) of the wavelength 590 nm set at an incident angle of 0° was measured.

[0634] The difference between the maximum and minimum values ​​of the delay amount obtained from each substrate film sample was calculated, and the difference was divided by the distance (m) in the fast axis direction (width direction) between the positions where the maximum and minimum values ​​were obtained in the film sample (3.5 cm × 3.5 cm sample). The resulting value was calculated as the "change (ΔRe) in the delay amount (Re) in the fast axis direction (width direction)".

[0635] Change in the retardation (Re) in the fast axis direction (width direction) (nm / m) = (maximum retardation value - minimum retardation value) / distance between the maximum value position and the minimum value position in the fast axis direction (width direction) (m)

[0636] (4) Steel wool (SW resistance) test (wipe resistance)

[0637] A friction tester (manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd., RT-300) and #0000 steel wool (trade name: BONSTAR, NIPPON STEEL WOOL CO., LTD.) were used to apply a load of 1 kg to a 2 cm square of the outermost surface (cured resin layer surface) of the laminated film while rubbing back and forth at a speed of 50 mm / sec, and visually confirm whether there are scratches on the surface of the cured resin layer. In addition, the haze value of the laminated film before and after friction was measured. Confirm that there are no visually identifiable scratches on the surface of the cured resin layer, and confirm the rate of change of the film haze after 2000 reciprocations compared to the initial film haze (film haze before friction), and judge according to the following judgment criteria. It should be noted that the rate of change of the haze is calculated by the following formula.

[0638] Change rate (%) = (film haze after abrasion - initial film haze) / initial film haze × 100

[0639] (Judgment Criteria)

[0640] A: The change rate is less than 1%.

[0641] B: The change rate is 1% or more.

[0642] (5) Bending durability

[0643] A bending tester (DLDMLH-FS manufactured by Yusa System Co., Ltd.) was used to test the cured resin layer side of the laminated film at a minimum radius of R = 1.5, with the cured resin layer side being the inner surface, and visually confirming whether cracks occurred in the cured resin layer on the inner surface. Then, the number of repeated bendings until cracks occurred was measured, and the determination was made based on the results and the following criteria.

[0644] (Judgment Criteria)

[0645] A: Repeated bending times more than 200,000 times

[0646] B: The number of repeated bending is more than 100,000 times and less than 200,000 times

[0647] C: Repeated bending times more than 1,000 times and less than 100,000 times

[0648] D: Repeated bending times less than 1000 times

[0649] (6) Elongation at break of cured resin layer

[0650] The laminated film was cut into a strip with a width of 10 mm and a length of 150 mm to prepare a test piece. A tensile tester with a constant temperature and humidity chamber (Intesco, 201X tester) was used, and the test piece was clamped by the clamps of the tensile tester in such a way that the initial distance between the clamps was 50 mm. Then, the sample was stretched at a stretching speed of 5 m / min, and the displacement of the cracks in the cured resin layer was visually confirmed, and the elongation was calculated.

[0651] Elongation (%) = (length at break - initial length) / initial length × 100

[0652] (7) Total light transmittance

[0653] The total light transmittance of each laminated film was measured using a haze meter HM-150 manufactured by Murakami Color Research Laboratory in accordance with JIS K 7136:2000.

[0654] (8) Light transmittance

[0655] The light transmittance of each laminated film at each measuring wavelength of 380 nm, 400 nm, and 500 to 600 nm was measured using a spectrophotometer (U-3900H manufactured by Hitachi High-Tech Corporation).

[0656] (9) Absolute reflectivity

[0657] A black tape (Scotch 117 manufactured by 3M) was attached to the surface of the laminated film on which the cured resin layer was not laminated, and the absolute reflectance at a wavelength of 550 nm on the cured resin layer side was measured using a spectrophotometer (U-3900H manufactured by Hitachi High-Tech Corporation).

[0658] The absolute reflectance is calculated by the ratio of the amount of light reflected by the cured resin layer of the laminate film to the amount of light directly measured from the light source without using a reference plate.

[0659] Absolute reflectivity (%) = the amount of light reflected by the cured resin layer of the laminated film / the amount of light used × 100

[0660] (10) Interference fringes

[0661] In a film laminate in which a black tape (Scotch 117 manufactured by 3M) was adhered to the side of the laminated film on which the cured resin layer was not laminated, interference fringes were visually confirmed from the cured resin layer side under a three-wavelength fluorescent lamp and evaluated according to the following criteria. It should be noted that the fluctuation range of the transmittance at 500 to 600 nm refers to the fluctuation range of the reflectance of light with a wavelength of 500 to 600 nm in the reflection simulation.

[0662] (Judgment Criteria)

[0663] A: Interference fringes are almost invisible (particularly good)

[0664] (The fluctuation range of transmittance at 500-600nm is less than 0.6%)

[0665] B: Interference fringes are not easily visible (good)

[0666] (The fluctuation range of the light transmittance at 500 to 600 nm is 0.6% or more and less than 1.1%)

[0667] C: Interference fringes are visible (slightly poor)

[0668] (The fluctuation range of the light transmittance at 500 to 600 nm is 1.1% or more and 1.5% or less)

[0669] D: Interference fringes are clearly visible (bad)

[0670] (The fluctuation range of transmittance between 500 and 600 nm exceeds 1.5%)

[0671] (11) Antistatic properties

[0672] The sample was humidified for 30 minutes in a measurement atmosphere of 23°C and 50% RH using a high resistance resistivity meter: Hiresta UX MCP-HT800 and a measuring electrode: UR-100 manufactured by Nittoseiko Analytech, and then measured at an applied voltage of 500 V. The value after 1 minute was taken as the surface resistivity. When the resistivity exceeded the upper limit of the measurable range, it was recorded as unmeasurable (over).

[0673] (12) Water drop contact angle (1)

[0674] Using an automatic contact angle meter (manufactured by Data Physics, Model OCA20), water was dropped onto the outermost surface (cured resin layer surface) of the laminated film, and the contact angle after 60 seconds was measured. The measurement was repeated 5 times, and the average value was used.

[0675] The measurement was performed after 1000 reciprocating frictions and 2000 reciprocating frictions by the method described in the above steel wool test and before the steel wool test.

[0676] (12) Water drop contact angle (2)

[0677] Using an automatic contact angle meter (manufactured by Data Physics, Model OCA20), water was dropped onto the outermost surface (cured resin layer surface) of the laminated film, and the contact angle after 30 seconds was measured. The measurement was repeated 5 times, and the average value was used.

[0678] The measurement was performed after 500 reciprocating frictions and 1000 reciprocating frictions by the method described in the above steel wool test and before the steel wool test.

[0679] (13) Fluorine atomic concentration

[0680] The measurement was performed by X-ray photoelectron spectroscopy (XPS) using the following apparatus.

[0681] Test equipment: XPS Thermo K-Alpha

[0682] Experimental conditions: X-ray monochromatization Al Kα

[0683] :Analysis area 400μmφ

[0684] : Grazing angle 90°

[0685] A narrow scan is performed with the elements detected by the wide scan as the target, and the fluorine ratio among the ratios of the detected elements is determined as the fluorine element concentration.

[0686] (14) Wear resistance

[0687] An eraser (product number: ER-KM, circular portion diameter 6.7mm, Tombow Pencil Co., Ltd. system) was installed in a friction tester (Ohira Rika Kogyo Co., Ltd. system) with the eraser front end extending 1~3mm from the mounting portion and the circular portion evenly contacting the cured resin layer surface. A 0.5kg load was applied to the outermost surface (cured resin layer surface) of the laminated film, and the water drop contact angle on the cured resin layer surface was measured by reciprocating 100 times in a region of 5cm at a speed of 1 reciprocating / second.

[0688] The water drop contact angle was measured by using a contact angle meter (Kyowa Interface Science Co., Ltd., Model DMo-501) by dropping 1.0 μL of water on the outermost surface (cured resin layer surface) of the laminated film and measuring the contact angle after 60 seconds by the θ / 2 method.

[0689] If the measured water drop contact angle was 90° or more, it was judged as ○ (good abrasion resistance).

[0690] Various materials used in Examples and Comparative Examples were prepared as follows.

[0691] Various materials used in Examples and Comparative Examples were prepared as follows.

[0692] <Polyester raw materials>

[0693] (PET-A)

[0694] Solid phase polymerization of homopolyethylene terephthalate (using Ti polymerization catalyst)

[0695] (PET-B)

[0696] Homopolyethylene terephthalate (using Sb polymerization catalyst)

[0697] (PET-C)

[0698] A masterbatch prepared by blending 5% by mass of silica particles having an average particle size of 2.3 μm into homopolyethylene terephthalate (using a Ti polymerization catalyst)

[0699] (PET-D)

[0700] A masterbatch prepared by blending 10% by mass of a UV absorber (Cyasorb 3638F manufactured by Sun Chemical Co., Ltd.) into homopolyethylene terephthalate (using a Sb polymerization catalyst)

[0701] (PET-E)

[0702] A masterbatch prepared by blending 2% by mass of silica particles having an average particle size of 2.3 μm into homopolyethylene terephthalate (using a Sb polymerization catalyst)

[0703] <Base film>

[0704] (Base film PET1)

[0705] As the surface layer, a raw material prepared by mixing 94% by mass of PET-A and 6% by mass of PET-C was used.

[0706] As the intermediate layer, a raw material obtained by mixing 75% by mass of PET-B and 25% by mass of PET-D was used.

[0707] (Base film PET2)

[0708] As the surface layer, a raw material prepared by mixing 90% by mass of PET-B and 10% by mass of PET-E was used.

[0709] As the intermediate layer, a raw material of 100% by mass of PET-B was used.

[0710] <Curable resin composition (A')>

[0711] (Curable resin composition (A'1))

[0712] The following compounds were mixed at a1:a2:b1:b2:c1:c2=55:17.5:5:15:2.5:5 (mass % of solid content).

[0713] ((Binder Resin))

[0714] (a1) Aqueous dispersion of a polyester resin copolymerized with the following composition

[0715] Monomer composition: (acid component) terephthalic acid / isophthalic acid / sodium 5-sulfonate of isophthalic acid / / (diol component) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol%)

[0716] (a2) Aqueous dispersion of a polyester resin having a condensed polycyclic aromatic group obtained by copolymerization with the following composition:

[0717] Monomer composition: (acid component) 2,6-naphthalene dicarboxylic acid / sodium 5-sulfonate of isophthalic acid / / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%)

[0718] ((Crosslinking agent))

[0719] (b1) Polyglycerol polyglycidyl ether as epoxy compound

[0720] (b2) Oxazoline-containing acrylic polymer ("EPOCROS" (registered trademark) manufactured by Nippon Shokubai Co., Ltd.) Oxazoline group content: 7.7 mmol / g

[0721] ((Particles))

[0722] (c1) Silica particles with an average particle size of 70 nm

[0723] (c2) Zirconium oxide sol with an average particle size of 20 nm

[0724] (Curable resin composition (A'2))

[0725] The following compounds were mixed at a2:a3:b1:b2:b3=60:10:10:10:10 (mass %) of solid content.

[0726] ((Binder Resin))

[0727] (a2) Aqueous dispersion of a polyester resin having a condensed polycyclic structure obtained by copolymerization with the following composition

[0728] Monomer composition: (acid component) 2,6-naphthalene dicarboxylic acid / sodium 5-sulfonate of isophthalic acid / / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%)

[0729] (a3) an acrylic resin aqueous dispersion prepared by polymerization with the following composition

[0730] Emulsified polymer of ethyl acrylate / n-butyl acrylate / methyl methacrylate / N-methylol acrylamide / acrylic acid = 65 / 21 / 10 / 2 / 2 (mass %) (emulsifier: anionic surfactant)

[0731] ((Crosslinking agent))

[0732] (b3) Hexamethoxymethylol melamine

[0733] (b4) Water-soluble polyglycerol polyglycidyl ether

[0734] (b5) Oxazoline-containing acrylic polymer ("EPOCROS" (registered trademark) manufactured by Nippon Shokubai Co., Ltd.) Oxazoline group content: 4.5 mmol / g

[0735] <Curable resin composition (B')>

[0736] (Curable resin composition (B'1))

[0737] 0.5 parts by mass of a fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure (KY1203 manufactured by Shin-Etsu Chemical Co., Ltd.) and 5 parts by mass of a photopolymerization initiator (Omnirad127 manufactured by IGM Resins BV) were added to 100 parts by mass of acrylic urethane (UV1700B manufactured by Mitsubishi Chemical Co., Ltd.) to prepare a curable resin composition (B'1). The mass average molecular weight of the acrylic urethane in the curable resin composition (B'1) was 2,000, and the cured product of the curable resin composition (B'1) prepared above, i.e., the cured resin layer (B1), had a refractive index of 1.53.

[0738] (Curable resin composition (B'2))

[0739] To 100 parts by mass of urethane acrylate (UV1700B manufactured by Mitsubishi Chemical Co., Ltd.), 0.5 parts by mass of a compound having an urethane acrylate skeleton (RS-90 manufactured by DIC) and 5 parts by mass of a photopolymerization initiator (Omnirad127 manufactured by IGM Resins BV) were added to prepare a curable resin composition (B'2). The mass average molecular weight of the urethane acrylate in the curable resin composition (B'2) was 2,000, and the cured product of the curable resin composition (B'2) prepared above, i.e., the cured resin layer (B2), had a refractive index of 1.53.

[0740] (Curable resin composition (B'3))

[0741] To 100 parts by mass of acrylic urethane (Mitsubishi Chemical's UV "UV1700B"), 0.5 parts by mass of a fluorine compound containing a long-chain siloxane skeleton (RS-58 manufactured by DIC) and 5 parts by mass of a photopolymerization initiator (Omnirad127 manufactured by IGM Resins BV) were added to prepare a curable resin composition (B'3). The mass average molecular weight of the acrylic urethane in the curable resin composition (B'3) was 2,000, and the cured product of the curable resin composition (B'3) prepared above, i.e., the cured resin layer (B3), had a refractive index of 1.53.

[0742] (Curable resin composition (B'4))

[0743] To 60 parts by mass of acrylic urethane (UV-1700B manufactured by Mitsubishi Chemical), 40 parts by mass of fine alumina particles (surface modified nanoparticles, ALMIBK-M114 manufactured by CIK-Nano Tek, average particle size 13 nm), 5 parts by mass of a photopolymerization initiator (Omnirad127 manufactured by IGM Resins BV), and 0.5 parts by mass of a leveling agent (MEGAFACE "RS-90" manufactured by DIC Corporation) were added to prepare a curable resin composition (B'4). The mass average molecular weight of the acrylic urethane in the curable resin composition (B'4) was 2,000, and the cured product of the curable resin composition (B'4) prepared above, i.e., the cured resin layer (B4), had a refractive index of 1.56.

[0744] [Example 1]

[0745] The raw materials for the surface layer and the middle layer in the above-mentioned base film PET1 are respectively put into different melt extruders, and the respective extrusion temperatures are set to 280°C for co-extrusion, and cooled and solidified on a casting drum cooled to 25°C, thereby obtaining two types of three-layer (surface layer / middle layer / surface layer = 3 / 59 / 3 ejection amount (mass ratio)) non-oriented sheets (unstretched sheets).

[0746] Next, the curable resin composition (A'1) was stretched to 3.3 times in the machine direction (longitudinal direction) at 80°C using a roll stretching machine to a coating thickness (after drying) of 0.04 g / m 2 After coating in a manner, the film was further stretched to 3.5 times in the width direction at 110°C in a tenter. Finally, a heat treatment was performed at 200°C and 5% relaxation was performed in the transverse direction. In this way, a laminated polyester film (base film PET1 / cured resin layer (A1)) having a cured resin layer (A1) and a thickness of 65 μm (each surface layer: 3 μm, intermediate layer: 59 μm) was obtained.

[0747] The curable resin composition (B'1) prepared in the above manner was applied by a bar coater to a coating thickness (after drying) of 5 μm so as to cover the cured resin layer (A1) of the laminated film. After heating at 90°C for 1 minute to dry, the cumulative light intensity was 400 mJ / cm in a nitrogen atmosphere. 2 The curable resin composition (B'1) is cured by ultraviolet irradiation to obtain a laminated film having a laminated structure of substrate film PET1 / cured resin layer (A1) / cured resin layer (B1).

[0748] [Comparative Example 1]

[0749] In Example 1, except that the curable resin composition (B'1) was changed to the curable resin composition (B'2) prepared in the above manner, the same method as Example 1 was carried out to obtain a laminated film having a laminated structure of base film PET1 / cured resin layer (A1) / cured resin layer (B2).

[0750] [Comparative Example 2]

[0751] In Example 1, except that the curable resin composition (B'1) was changed to the curable resin composition (B'3), the same method as in Example 1 was carried out to obtain a laminated film having a laminated structure of base film PET1 / cured resin layer (A1) / cured resin layer (B3).

[0752] [Comparative Example 3]

[0753] In Example 1, the substrate film PET1 is changed to the following substrate film PET2, and the laminated polyester film in Example 1 is changed to the laminated polyester film obtained below. Except for this, the manufacturing is carried out in the same manner as Example 1, thereby obtaining a laminated film having a laminated structure of substrate film PET2 / cured resin layer (A2) / cured resin layer (B1).

[0754] <Base film PET2>

[0755] The raw materials of the surface layer and the middle layer in the base film PET1 are respectively put into different melt extruders, and the respective extrusion temperatures are set to 285°C for co-extrusion, and cooled and solidified on a casting drum cooled to 40°C, thereby obtaining two types of three-layer (surface layer / middle layer / surface layer = 1 / 8 / 1 ejection amount (mass ratio)) non-oriented sheets (unstretched sheets).

[0756] Next, the curable resin composition (A'2) was stretched to 3.4 times in the machine direction (longitudinal direction) at 85°C using a roll stretching machine to a coating thickness (after drying) of 0.1 g / m 2 After coating in a manner of , the film was further stretched to 4.3 times in the width direction at 110°C in a tenter. Finally, a heat treatment was performed at 235°C and 2% relaxation was performed in the transverse direction. In this way, a laminated polyester film (base film PET2 / cured resin layer (A2)) having a cured resin layer (A2) and a thickness of 50 μm (each surface layer: 5 μm, intermediate layer: 40 μm) was obtained.

[0757] [Comparative Example 4]

[0758] In Example 1, except that the curable resin composition (B'1) was changed to the curable resin composition (B'4), the same method as in Example 1 was carried out to obtain a laminated film having a laminated structure of base film PET1 / cured resin layer (A1) / cured resin layer (B4).

[0759] <Evaluation Results>

[0760] The properties of the laminated films obtained in the above-mentioned Examples and Comparative Examples are shown in Table 1 below.

[0761] [Table 1]

[0762] Table 1

[0763]

[0764] <Investigation>

[0765] According to the results of the above-mentioned embodiments and comparative examples, it can be seen that by having a structure in which a cured resin layer (A) and a cured resin layer (B) are sequentially stacked on the surface of a base film, and the cured resin layer (A) is a cured product of a curable resin composition (A') containing a compound having a condensed polycyclic aromatic structure as a binder (Aa), a cross-linking agent (Ab) and particles (Ac), and the cured resin layer (B) is a cured product of a curable resin composition (B') containing (X) acrylic urethane and (Y) a compound having a cyclic siloxane skeleton, it has flexibility and can achieve both high levels of scratch resistance (SW resistance, for example, the number of reciprocations at which the change in haze of the initial film is less than 1% is more than 2000 times) and repeated bending properties (can be bent 200,000 times under the condition of R=1.5), and the contact angle is also large, and thus the low interference property is also excellent.

[0766] In contrast, it is known that it is difficult to achieve both the desired scratch resistance and repeated bending resistance if only a cured resin layer without (X) acrylic urethane and (Y) a compound having a cyclic siloxane skeleton is provided as shown in Comparative Examples 1, 2, and 4. It should be noted that, according to Comparative Example 4, even if particles are contained in the curable resin composition (B'), the desired scratch resistance cannot be obtained.

[0767] Furthermore, it was found that in Comparative Example 3 in which the curable resin composition (A′) did not contain particles, sufficient low interference properties were not obtained.

[0768] It is speculated that the reason for this difference lies in the composition of the cured resin layer (A) and the cured resin layer (B). Due to the composition of the cured resin layer (A), the light interference with the substrate film is reduced, thereby making the interference fringes less visible. In addition, by adopting a composition of the cured resin layer (B) whose refractive index is pre-adjusted in a manner that is not easily affected by light interference (the refractive index is set to 1.53 in the embodiment of the present application), the required scratch resistance and repeated bending resistance can be taken into account.

[0769] In the past, the following research has been conducted on laminated films with a surface layer having high SW resistance: when the target SW resistance is designed to a required level (e.g., 2000 times or more), the structural design of the raw materials constituting the substrate film used is reconsidered as needed, and the tensile elastic modulus is further increased.

[0770] On the other hand, if the cured resin layer (A) and the cured resin layer (B) are made into a specific structure, it is also possible to appropriately select a general-purpose base film distributed on the market, which can provide an advantage of increased freedom in selecting the base film.

[0771] <Curable resin composition (C'1)>

[0772] The following compounds (CI) to (CV) were mixed to prepare a curable resin composition C1. The mixing ratio of (CI), (CII), (CIII), (CIV), and (CV) was 7:69:12:10:2.

[0773] (Compound (Ca))

[0774] (CI): Conductive agent containing polyethylene dioxythiophene and polystyrene sulfonic acid (Orgacon ICP1010 manufactured by Agfa-Gevaert) neutralized with concentrated ammonia water to a pH of 9, non-volatile component: 1.2 mass%, solvent; water

[0775] (CII) A polyester resin aqueous dispersion obtained by copolymerization with the following composition

[0776] Monomer composition:

[0777] (Acid component) 2,6-naphthalene dicarboxylic acid / sodium 5-sulfonate of isophthalic acid = 92 / 8 (molar ratio) / / (Diol component) ethylene glycol / diethylene glycol = 80 / 20 (molar ratio)

[0778] (Compound (Cc))

[0779] (AIII): polyglycerol having an average n of 4 in the following formula (3)

[0780]

[0781] (CIV): In the following formula (5), the average of m+n is 10, and the nonionic surfactant has a polyethylene oxide structure in the side chain

[0782]

[0783] (CV): A fluorine-based nonionic surfactant having a structure in which a branched perfluoroalkenyl group is present on the hydrophobic group and a polyethylene oxide chain (average chain length 8 units) is present on the hydrophilic group

[0784] <Curable resin composition (A'1)>

[0785] The following compounds were mixed at a1:a2:b1:b2:c1:c2=55:17.5:5:15:2.5:5 (mass % of solid content).

[0786] ((Aa) Binder)

[0787] (a1) Aqueous dispersion of a polyester resin copolymerized with the following composition

[0788] Monomer composition: (acid component) terephthalic acid / isophthalic acid / sodium 5-sulfonate of isophthalic acid / / (diol component) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol%)

[0789] (a2) Aqueous dispersion of a polyester resin having a condensed polycyclic aromatic group obtained by copolymerization with the following composition: (acid component) 2,6-naphthalene dicarboxylic acid / sodium 5-sulfonate of isophthalic acid / / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%)

[0790] ((Ab) Cross-linking agent)

[0791] (b1) Polyglycerol polyglycidyl ether as epoxy compound

[0792] (b2) Oxazoline-containing acrylic polymer ("EPOCROS" (registered trademark) manufactured by Nippon Shokubai Co., Ltd.) Oxazoline group content: 7.7 mmol / g

[0793] ((Ac) particles)

[0794] (c1) Silica particles with an average particle size of 70 nm

[0795] (c2) Zirconium oxide sol with an average particle size of 20 nm

[0796] <Curable resin composition (A'3)>

[0797] 27.5 parts by mass of acrylic binder (ELAC medium: manufactured by Toyo Ink Co., Ltd.), 2.5 parts by mass of isocyanate curing agent (Z202S: manufactured by Toyo Ink Co., Ltd.), 70 parts by mass of zirconium particles (ZP153: manufactured by Nippon Shokubai Co., Ltd.)

[0798] <Curable resin composition (B'5)>

[0799] (Synthesis of fluorine compounds)

[0800] 69.4 parts by mass (0.1 mol) of the compound represented by the following formula (6), 36.5 parts by mass (0.315 mol) of 2-hydroxyethyl acrylate, and 111.9 parts by mass of toluene were mixed in a reaction container and uniformly mixed. Then, 1.12 parts by mass (0.0126 mol) of N,N-diethylhydroxylamine as a catalyst was added. Then, the mixture was reacted at 70°C for 8 hours. After washing with water, toluene and the like were distilled off to obtain the following compound (7) having a fluorine-containing atom structure and a cyclic siloxane structure.

[0801]

[0802] To 80 parts by mass of (X) (meth) urethane acrylate (UV1700B manufactured by Mitsubishi Chemical Co., Ltd.), 0.5 parts by mass of the fluorine compound (7) having a cyclic siloxane skeleton and a perfluoroether structure, 20 parts by mass of fine alumina particles (surface-modified nanoparticles, ALMIBK-M115 manufactured by CIK-NANO TEK Co., Ltd., average particle size 13 nm), and 5 parts by mass of a photopolymerization initiator (Omnirad127 manufactured by IGM Resins BV) were added to prepare a curable resin composition (B'5). The mass average molecular weight of the curable resin composition (B'5) was 2,000, and the refractive index of the cured resin layer (B5) was 1.53.

[0803] [Example 2]

[0804] The raw materials for the surface layer and the middle layer in the above-mentioned base film PET1 are respectively put into different melt extruders, and the respective extrusion temperatures are set to 280°C for co-extrusion, and cooled and solidified on a casting drum cooled to 25°C, thereby obtaining two types of three-layer (surface layer / middle layer / surface layer = 3 / 59 / 3 ejection amount (mass ratio)) non-oriented sheets (unstretched sheets).

[0805] Next, the curable resin composition (C'1) was stretched 3.3 times in the machine direction (longitudinal direction) at 80°C using a roll stretching machine to a coating thickness (after drying) of 0.03 g / m 2After coating in a manner of , the film was further stretched to 3.5 times in the width direction at 110°C in a tenter. Finally, a heat treatment was performed at 200°C and 5% relaxation was performed in the transverse direction. In this way, a laminated polyester film (PET1 / cured resin layer (C1)) with a cured resin layer (C) having a thickness of 65 μm (each surface layer: 3 μm, intermediate layer: 59 μm) was obtained.

[0806] In order to form a cured resin layer (C1) covering the above-mentioned substrate film PET1, the following curable resin composition (A'3) is applied by a rod coater in a coating thickness (after drying) of 0.06 μm. The cured resin layer (A'3) is dried by heating at 100°C for 30 seconds to obtain a cured resin layer (A'3) (before curing). Next, the above-mentioned curable resin composition (B'5) is applied on the cured resin layer (A'3) by a rod coater in a coating thickness (after drying) of 2.5 μm. The cured resin layer (B'5) is dried by heating at 90°C for 1 minute to obtain a cured resin layer (B'5) (before curing). The accumulated light intensity is 400 mJ / cm in a nitrogen atmosphere. 2 The cured resin layer (A'3) (before curing) and the cured resin layer (B'5) (before curing) are cured by ultraviolet irradiation, thereby obtaining a laminated film having a laminated structure comprising base film PET1 / cured resin layer (C1) / cured resin layer (A3) / cured resin layer (B5).

[0807] Table 2 shows the results of the evaluation by the above method.

[0808] [Comparative Example 5]

[0809] The laminated film was obtained by manufacturing in the same manner as in Example 2 except that the cured resin layer (A) was not provided. The results of evaluations carried out in the same manner as in Example 1 are shown in Table 2.

[0810] [Comparative Example 6]

[0811] In Example 1, no cured resin layer (C) was provided, and a laminated film was obtained by manufacturing according to Example 1. That is, the raw materials of the surface layer and the middle layer in the above-mentioned base film PET2 were respectively put into different melt extruders, and the respective extrusion temperatures were set to 285° C. to melt the above-mentioned raw materials, and then cooled and solidified on a casting roll cooled to 40° C., thereby co-extruded with two kinds of three layers (surface layer / middle layer / surface layer = 1 / 8 / 1 ejection amount (mass ratio)) to obtain a non-oriented sheet (unstretched sheet).

[0812] Next, the curable resin composition (A'1) was stretched to 3.4 times in the machine direction (longitudinal direction) at 85°C using a roll stretching machine to a coating thickness (after drying) of 0.1 g / m 2After coating in a manner of 100° C., the film was stretched to 4.3 times in the width direction at 110° C. in a tenter, and then heat-treated at 235° C. and relaxed by 2% in the transverse direction. In this manner, a laminated polyester film (PET2 / cured resin layer (A1)) with a cured resin layer (A) having a thickness of 50 μm (each surface layer: 5 μm, intermediate layer: 40 μm) was obtained.

[0813] The curable resin composition (B'5) prepared in the above manner was applied by a bar coater to a coating thickness (after drying) of 5 μm so as to cover the cured resin layer (A1) of the laminated film. After heating at 90°C for 1 minute for drying, the cumulative light intensity was 400 mJ / min in a nitrogen atmosphere. c m 2 The curable resin composition (B'5) is cured by ultraviolet irradiation to obtain a laminated film having a laminated structure of substrate film PET2 / cured resin layer (A1) / cured resin layer (B5).

[0814] Table 2 shows the results of the evaluation carried out in the same manner as in Example 1.

[0815] [Table 2]

[0816] Table 2

[0817]

[0818] <Investigation>

[0819] According to the results of the above-mentioned embodiments and comparative examples, it can be seen that by having a structure in which a cured resin layer (C), a cured resin layer (A) and a cured resin layer (B) are sequentially stacked on the surface of a base film, and the aforementioned cured resin layer (B) contains (X) acrylic urethane and (Y) a fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure, it has flexibility and can take into account both surface hardness (SW resistance, for example, the number of reciprocations at which the change in haze of the initial film is less than 1% is more than 2000 times) and repeated bending properties (can be bent 200,000 times under the condition of R=1.5) at a high level.

[0820] In contrast, it is known that if the layer structure is such as that shown in Comparative Example 5 in which only a cured resin layer (B) is provided and there is no cured resin layer (A), or the layer structure is such as that shown in Comparative Example 2 in which there is no cured resin layer (C), it is difficult to take into account the required hard coating, repeated bending and low interference. It is speculated that the reason for such a difference is that the composition of the cured resin layer (A) and the cured resin layer (B) is different. In addition, due to the composition of the cured resin layer (A), the optical interference between it and the cured resin layer (B) becomes smaller, thereby making the interference fringes difficult to see. On the other hand, by adopting the composition of the cured resin layer (B), the required scratch resistance and repeated bending can be taken into account.

[0821] It is also known that by setting the constituent material and thickness ratio of the cured resin layer (B) within specific ranges, it is not necessary to extremely increase the tensile modulus of the base film used, and it is not necessary to use a customized base film.

[0822] In the past, when designing the target SW resistance of a laminated film having a surface layer with high SW resistance to a desired level (e.g., 2000 times or more), the structural design of the raw materials constituting the base film used had to be reconsidered as needed to further increase the tensile elastic modulus.

[0823] On the other hand, when the cured resin layer (B) is made into a specific structure, it is possible to appropriately select a general-purpose base film distributed on the market, and there is an advantage that the degree of freedom in selecting the base film is increased.

[0824] <Curable resin composition>

[0825] (Curable resin composition (A'1))

[0826] The following compounds were mixed at a1:a2:b1:b2:c1:c2=55:17.5:5:15:2.5:5 (mass % of solid content).

[0827] ((Aa) Binder resin)

[0828] (a1) Aqueous dispersion of a polyester resin copolymerized with the following composition

[0829] Monomer composition: (acid component) terephthalic acid / isophthalic acid / sodium 5-sulfonate of isophthalic acid / / (diol component) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol%)

[0830] (a2) Aqueous dispersion of a polyester resin having a condensed polycyclic aromatic group obtained by copolymerization with the following composition:

[0831] Monomer composition: (acid component) 2,6-naphthalene dicarboxylic acid / sodium 5-sulfonate of isophthalic acid / / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%)

[0832] ((Ab) Cross-linking agent)

[0833] (b1) Polyglycerol polyglycidyl ether as epoxy compound

[0834] (b2) Oxazoline-containing acrylic polymer ("EPOCROS" (registered trademark) manufactured by Nippon Shokubai Co., Ltd.) Oxazoline group content: 7.7 mmol / g

[0835] ((Ac) particles)

[0836] (c1) Silica particles with an average particle size of 70 nm

[0837] (c2) Zirconium oxide sol with an average particle size of 20 nm

[0838] [Example 3]

[0839] The curable resin composition (D'1) prepared as described below was applied by a bar coater to cover the cured resin layer (A) of the substrate film PET1 so that the coating thickness (after drying) became 5 μm. After heating at 90°C for 1 minute for drying, the accumulated light intensity was 400 mJ / cm in a nitrogen atmosphere. 2 The cured resin layer (D'1) (before curing) is cured to obtain a laminated film having a laminated structure of base film PET1 / cured resin layer (A1) / cured resin layer (D1).

[0840] The fluorine atom concentration ratio (F2 / F1) of the outermost surface (the surface on the cured resin layer (D) side) of the laminated film measured by X-ray photoelectron spectroscopy (XPS) was 0.013.

[0841] (Curable resin composition (D'1))

[0842] As the component (Da), 80 parts by mass of acrylic urethane (UV1700B manufactured by Mitsubishi Chemical Co., Ltd.) and 20 parts by mass of acrylic urethane (UV7610B manufactured by Mitsubishi Chemical Co., Ltd.), 5 parts by mass of the component (D-b1) described below, 0.2 parts by mass of a fluorine compound (D-c1) having a fluorine atom-containing structure and a cyclic siloxane structure, and 5 parts by mass of a photopolymerization initiator (Omnirad127 manufactured by IGM Resins BV) were added to prepare a curable resin composition (D'1).

[0843] ((D-b1) component)

[0844] B-b1: A quaternary ammonium salt group-containing polymer solution (D-b1) synthesized as follows was used. The synthesis method is as follows.

[0845] First, 83.2 parts of polycaprolactone monool (weight average molecular weight 2,000), 16.7 parts of m-isopropenyl-α,α'-dimethylbenzyl isocyanate, and 0.03 parts of dioctyltin laurate were added to a four-necked flask equipped with a thermometer, a stirrer, a water-cooled condenser, and a nitrogen inlet, and the mixture was reacted at 80°C. The reaction was terminated when the residual isocyanate group content became 0.03% or less, thereby obtaining a polyester macromonomer (b-1m).

[0846] Into a four-necked flask equipped with a thermometer, a stirrer, a water-cooled condenser, and a nitrogen inlet, 10 parts of a polyester macromonomer (b-1m), 15 parts of methacryloyloxyethyltrimethylammonium chloride, 5 parts of cyclohexyl methacrylate, 0.2 parts of azobisisobutyronitrile, 20 parts of methyl ethyl ketone, and 50 parts of isopropanol were added, and polymerization was carried out at 70°C for 8 hours under a nitrogen flow to obtain a polymer (D-b1) solution containing a quaternary ammonium salt group.

[0847] ((D-c1) Synthesis of fluorine compounds)

[0848] 69.4 parts by mass (0.1 mol) of the compound represented by the following formula (2), 36.5 parts by mass (0.315 mol) of 2-hydroxyethyl acrylate, and 111.9 parts by mass of toluene were mixed in a reaction container and uniformly mixed. Then, 1.12 parts by mass (0.0126 mol) of N,N-diethylhydroxylamine as a catalyst was added. Then, the mixture was reacted at 70° C. for 8 hours. After washing with water, toluene and the like were distilled off to obtain the following compound (3) having a fluorine-containing atom structure and a cyclic siloxane structure.

[0849]

[0850]

[0851] [Example 4]

[0852] Except for changing the thickness of the cured resin layer (D), the same method as in Example 1 was carried out to obtain a laminated film having a laminated structure of base film PET1 / cured resin layer (A1) / cured resin layer (D1).

[0853] [Example 5]

[0854] Except for changing the addition amount of the compound (D-c1) having a fluorine atom structure and a cyclic siloxane structure, the same manufacturing method as Example 4 was carried out to obtain a laminated film having a laminated structure of base film PET1 / cured resin layer (A1) / cured resin layer (D2).

[0855] That is, a laminated film is obtained in the same manner as in Example 4 except that a curable resin composition (D'2) is used instead of the curable resin composition (D'1). The curable resin composition (D'2) is the same as (D'1) except that the amount of the fluorine compound (D-c1) having a fluorine atom structure and a cyclic siloxane structure is set to 0.5 parts by mass.

[0856] [Comparative Example 7]

[0857] In Example 3, a laminated film was obtained by the same method as in Example 3 except that a curable resin composition (D'3) was used instead of the curable resin composition (D'1). The curable resin composition (D'3) was the same as (D'1) except that the curable resin composition (D'3) did not contain the component (Db) (quaternary ammonium salt-containing polymer).

[0858] [Comparative Example 8]

[0859] In Example 3, a laminated film is obtained by manufacturing in the same manner as in Example 3 except that a curable resin composition (D'4) is used instead of the curable resin composition (D'1). The curable resin composition (D'4) is the same as (D'1) except that it does not contain the fluorine compound (D-c1) having a cyclic siloxane skeleton and a perfluoroether structure.

[0860] <Evaluation Results>

[0861] The properties of the laminated films obtained in the above-mentioned Examples and Comparative Examples are shown in Table 3 below.

[0862] [Table 3]

[0863] Table 3

[0864]

[0865] The abrasion resistance of the laminated films obtained in Examples 4 and 5 and Comparative Examples 9 to 11 was further evaluated. The results are shown in Table 4 below.

[0866] [Comparative Example 9]

[0867] In Example 4, a laminated film is obtained by the same method as in Example 2 except that a curable resin composition (D'3) is used instead of the curable resin composition (D'1). The curable resin composition (D'3) is the same as (D'1) except that it does not contain the component (D-b1) (a polymer containing a quaternary ammonium salt).

[0868] [Comparative Example 10]

[0869] In Example 5, a laminated film was obtained by the same method as in Example 2 except that a curable resin composition (D'5) was used instead of the curable resin composition (D'2). The curable resin composition (D'5) was the same as (D'2) except that the curable resin composition (D'5) did not contain the component (D-b1) (a polymer containing a quaternary ammonium salt).

[0870] [Comparative Example 11]

[0871] In Example 4, a laminated film is obtained by the same method as in Example 2 except that a curable resin composition (D'4) is used instead of the curable resin composition (D'1). The curable resin composition (D'4) is the same as (D'1) except that it does not contain the fluorine compound (D-c1) having a cyclic siloxane skeleton and a perfluoroether structure.

[0872] [Table 4]

[0873] Table 4

[0874]

[0875] <Investigation>

[0876] According to the results of the above-mentioned embodiments and comparative examples, it can be seen that by having a structure in which a cured resin layer (A) and a cured resin layer (D) are sequentially stacked on at least one surface of a substrate film, and the aforementioned cured resin layer (D) contains a trifunctional or higher (meth)acrylate (Da), a quaternary ammonium salt group-containing polymer (Db), and a compound having a fluorine atom structure and a cyclic siloxane structure (Dc), it is possible to achieve both antistatic and antifouling properties at a high level. In addition, it can be seen that interference fringes are not easily visible, and practical repeated bending characteristics and abrasion resistance are also satisfied.

[0877] In addition, the antifouling property was evaluated by the SW treatment based on the small change in the water drop contact angle before and after the treatment.

[0878] On the other hand, it is understood that when only one of the components is used as in Comparative Examples 7 and 8, it is difficult to achieve both the required antistatic property and antifouling property, and the abrasion resistance is not satisfactory.

[0879] It is speculated that the reason for such a difference is that the composition of the cured resin layer (D) is different. In addition, due to the composition of the cured resin layer (A), the light interference with the cured resin layer (D) becomes smaller, thereby making the interference fringes less visible. Furthermore, it can be seen that the laminated film of Comparative Example 8 also has poor SW resistance.

[0880] Furthermore, Examples 9 to 11 show that the laminated film including the cured resin layer (A) and the cured resin layer (D) having the composition satisfying the provisions of the present invention also has excellent abrasion resistance.

[0881] Industrial Applicability

[0882] The laminated film of the present invention has good scratch resistance (e.g., 2,000 times or more in SW resistance evaluation) and repeated folding resistance (200,000 times under the condition of inward folding, R=1.5), and can be used as various surface protection films. Among them, it can be preferably used for optical applications such as display components (surface protection films, etc.) that require flexibility.

[0883] In addition, the laminated film of the present invention has good scratch resistance (for example, more than 2,000 times in SW resistance evaluation) and repeated bending resistance (folded inward, under the condition of R=1.5, it can be bent 200,000 times) at a high level, and has good antistatic properties, and can be used for various surface protection purposes. Among them, it can be preferably used for optical purposes such as display components (surface protection films, etc.) that require flexibility.

[0884] Furthermore, the laminated film of the present invention can achieve both antistatic and antifouling properties at high levels, and is also excellent in abrasion resistance, so it can be used for various surface protection purposes, and can be preferably used for optical purposes such as display components (surface protection films, etc.).

[0885] Description of Reference Numerals

[0886] 2. Substrate film

[0887] 4 Curing resin layer (A)

[0888] 6 Curing resin layer (B)

[0889] 10 Laminated Film

Claims

1. A laminated film comprising a cured resin layer (A) and a cured resin layer (B) laminated in sequence on at least one side of a substrate film, The cured resin layer (A) is a cured product of a curable resin composition (A') containing a binder (Aa). The cured resin layer (B) is a cured product of a curable resin composition (B′) containing (X) (meth)acrylic urethane and (Y) a compound having a cyclic siloxane skeleton.

2. The laminated film according to claim 1, wherein The curable resin composition (A') further includes (Ab) a crosslinking agent and (Ac) particles, and the (Aa) binder includes a compound having a condensed polycyclic aromatic structure.

3. The laminated film according to claim 1, wherein A cured resin layer (C) is provided between the substrate film and the cured resin layer (A), wherein the cured resin layer (C) is a cured product of a curable resin composition (C') containing an antistatic agent, and the compound (Y) having a cyclic siloxane skeleton is a fluorine compound having a cyclic siloxane skeleton and a perfluoroether structure.

4. A laminated film comprising a cured resin layer (A) and a cured resin layer (D) laminated in sequence on at least one side of a substrate film, wherein the cured resin layer (A) is a cured product of a curable resin composition (A') comprising (Aa) a binder, (Ab) a crosslinking agent and (Ac) particles, and the cured resin layer (D) is a cured product of a curable resin composition (D') comprising (Da) a (meth)acrylate having three or more functional groups, (Db) a polymer containing a quaternary ammonium salt group, and (Dc) a compound having a fluorine atom structure and a cyclic siloxane structure.

5. The laminated film according to claim 2, wherein: The compound (Y) having a cyclic siloxane skeleton is a fluorine compound having a perfluoroether structure.

6. The laminated film according to claim 4 or 5, wherein The ratio (F2 / F1) of the fluorine atom concentration (F2; atomic %) at the position where Ar etching was performed for 10 seconds at an acceleration voltage of 200 eV measured by X-ray photoelectron spectroscopy (XPS) to the fluorine atom concentration (F1: atomic %) at the outermost surface of the stacked film (cured resin layer surface) measured by X-ray photoelectron spectroscopy (XPS) is less than 0.

2.

7. The laminated film according to claim 2, wherein: When the following steel wool resistance test is performed on the surface of the cured resin layer (B), the change rate of the film haze after 2000 reciprocating cycles is less than 1%. (Steel wool resistance test) Using a friction tester and #0000 steel wool, a load of 1 kg was applied to the outermost surface of the cured resin layer (B) in a 2 cm square, and the layer was rubbed back and forth 2000 times at a speed of 50 mm / sec. The haze value of the laminated film before and after the friction was measured, and the change rate compared to the initial film haze (film haze before friction) was calculated. Change rate (%) = (film haze after friction - initial film haze) / initial film haze × 100.

8. The laminated film according to claim 4, wherein The number of reciprocating times of the following scratch resistance evaluation of the cured resin layer (D) is 1000 times or more, (Evaluation of scratch resistance) A friction tester was used with #0000 steel wool to apply a load of 1 kg to the outermost surface of the cured resin layer (D) in a 2 cm square and rub it back and forth at a speed of 50 mm / sec. The presence or absence of scratches on the surface of the cured resin layer (D) was visually confirmed, and the haze value was measured. The number of reciprocations at which no scratches were visually confirmed and the change in haze compared to the initial film was less than 1% was measured.

9. The laminated film according to claim 3, wherein: The number of reciprocating times of the following scratch resistance evaluation of the cured resin layer (B) is 2000 times or more, (Evaluation of scratch resistance) A friction tester was used with #0000 steel wool, and a load of 1 kg was applied to the outermost surface of the cured resin layer (B) in a 2 cm square. The surface of the cured resin layer (B) was rubbed back and forth at a speed of 50 mm / sec. The presence or absence of scratches on the surface of the cured resin layer (B) was visually confirmed, and the haze value was measured. The number of reciprocations at which no scratches were visually confirmed and the change in haze compared to the initial film was less than 1% was measured.

10. The laminated film according to claim 2 or 3, wherein the number of repeated folding times in the following repeated folding test is 200,000 times or more, (Repeated bending test) The laminate film was subjected to a bending test using a bending tester with the cured resin layer side as the inner surface at a minimum radius of R = 1.5, and the presence or absence of cracks in the cured resin layer on the inner surface was visually confirmed. The number of repeated bendings until cracks occurred was measured.

11. The laminated film according to any one of claims 2 to 4, which has a film haze of 1.0% or less.

12. The laminated film according to claim 2, wherein: The elongation at break of the cured resin layer (A) and the cured resin layer (B) (cured resin layer) is 0.5% or more.

13. The laminated film according to claim 2 or 3, wherein: The light transmittance at a wavelength of 380 nm on the surface of the cured resin layer (B) is 3% or less.

14. The laminated film according to claim 2 or 3, wherein: The maximum reflectivity difference of the surface of the cured resin layer (B) at a wavelength of 500 to 600 nm is 1.5% or less.

15. The laminated film according to any one of claims 2 to 4, wherein The substrate film contains an ultraviolet absorber.

16. The laminated film according to any one of claims 2 to 4, wherein The cured resin layer (A) includes (Ac) particles, and the (Ac) particles are two types of particles having different particle sizes.

17. The laminated film according to claim 2, wherein: The compound having a condensed polycyclic aromatic structure is a polyester resin having a condensed polycyclic aromatic structure.

18. The laminated film according to claim 4, wherein The (Aa) binder includes a compound having a condensed polycyclic aromatic structure.

19. The laminated film according to any one of claims 2 to 4, wherein The substrate film is a polyester film.

20. The laminated film according to any one of claims 2 to 4, wherein The substrate film is a polyethylene terephthalate (PET) film.

21. The laminated film according to claim 19, wherein When light having a wavelength of 590 nm is incident on the polyester film surface at an angle of 0°, the retardation (Re) is 1400 nm or less.

22. The laminated film according to claim 19, wherein When light having a wavelength of 590 nm is incident on the polyester film surface at an angle of 0°, a change in retardation (Re) in the fast axis direction is 10 nm / m or more and 600 nm / m or less.

23. The laminated film according to claim 2 or 3, wherein: The thickness of the cured resin layer (B) is 10.0 μm or less.

24. The laminated film according to any one of claims 2 to 4, which is for surface protection.

25. The laminated film according to claim 24, which is used for displays.

26. The laminated film according to claim 25, which is used for a front panel.

Citation Information

Patent Citations

  • New polythiophene dispersion and its preparation

    JP1995090060A

  • Resin composition for hard coat layer formation

    JP2008056872A

  • Antistatic hard coat resin composition, and film having antistatic hard coat layer

    JP2013091698A

  • Surface-hardened article and hardening resin composition for coating film formation

    JP2013132784A

  • Active energy ray-curable resin composition, active energy ray-curable emulsion composition, coating agent composition, and urethane (METH)acrylate-based compound

    JP2020152786A